Manufacturing method of cathode active material particle
Patent Information
- Application Number
- JP2023196888
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-30
- Filing Date
- 2023-11-20
- Publication Date
- 2025-03-14
AI Technical Summary
【0013】 本発明の一態様により、初期特性が向上された正極活物質の製造方法、及び正極活物質を有する二次電池の製造方法を提供することができる。
Smart Images

Figure 2025035979000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing positive electrode active material particles. [Background technology]
[0002] Lithium ion secondary batteries have a high volumetric energy density and are suitable as a power source for electronic devices. With the widespread use of portable electronic devices such as smartphones and tablet terminals, lithium ion secondary batteries are desired to have excellent cycle characteristics. In response to this demand, improvements to the positive electrode active material for lithium ion secondary batteries have been actively carried out (e.g., Patent Document 1 and Patent Document 2).
[0003] Research on the crystal structure of positive electrode active material particles is also being conducted (Non-Patent Documents 1 to 3). X-ray diffraction (XRD) is one of the methods used to analyze the crystal structure of positive electrode active materials. XRD data can be analyzed by using the Inorganic Crystal Structure Database (ICSD) introduced in Non-Patent Document 4. For example, the lattice constant of lithium cobalt oxide described in Non-Patent Document 5 can be referenced from ICSD. For Rietveld analysis, for example, the analysis program RIETAN-FP (Non-Patent Document 6) can be used. VESTA (Non-Patent Document 7) can be used as crystal structure drawing software. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-206747 A [Patent Document 2] Patent Publication No. 2022-070247 [Non-patent literature]
[0005] [Non-Patent Document 1] Toyoki Okumura et.al., “Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation”, Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-Patent Document 2] Motohashi, T. et.al., “Electronic phase diagram of the layered cobalt oxide system LixCoO2(0.0≦x≦1.0)”, Physical Review B, 80(16);165114 [Non-Patent Document 3] Zhaohui Chen et.al., “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society, 2002, 149(12)A1604-A1609 [Non-Patent Document 4] Belsky, A. et.al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., (2002) B58 364-369. [Non-Patent Document 5] Akimoto, J.; Gotoh, Y.; Oosawa, Y. “Synthesis and structural refinement of LiCoO2 single crystals” Journal of Solid State Chemistry (1998) 141, p. 298-302. [Non-Patent Document 6] F.Izumi and K.Momma,,“Three-Dimensional Visualization in Powder Diffraction” Solid State Phenom.130,15-20(2007) [Non-Patent Document 7] K.Momma and F.Izumi, “VESTA 3 for three-dimensional visualization of crystal, volumetric and morphology data” J.Appl.Cryst.(2011).44,1272-1276 Summary of the Invention [Problem to be solved by the invention]
[0006] There is still room for improvement in various aspects of lithium ion secondary batteries, such as initial characteristics, discharge capacity, cycle characteristics, reliability, safety, cost, etc. For example, as an initial characteristic, there is an improvement in the initial discharge capacity in a charge-discharge cycle test.
[0007] In view of the above, an object of one embodiment of the present invention is to provide a method for manufacturing a positive electrode active material with improved initial characteristics, and a method for manufacturing a secondary battery including the positive electrode active material.
[0008] Note that the description of these problems does not preclude the existence of other problems. Note that one embodiment of the present invention does not necessarily solve all of these problems. Note that it is possible to extract problems other than these from the description of the specification, drawings, and claims. [Means for solving the problem]
[0009] In order to solve the above problems, one aspect of the present invention includes a step of heating lithium cobalt oxide, a step of mixing a first additive element source with the heated lithium cobalt oxide to form a first mixture, a step of heating the first mixture to form a first composite oxide, a step of mixing a second additive element source with the first composite oxide to form a second mixture, a step of heating the second mixture to form a second composite oxide, a step of mixing a third additive element source with the second composite oxide to form a third mixture, and a step of heating the third composite oxide to form a second composite oxide. and heating the mixture of the above at 750° C. or more and 850° C. or less for 2 hours or more and 10 hours or less to form a third composite oxide, wherein the first additive element source to the third additive element source each contain one or more elements selected from magnesium, titanium, nickel, aluminum, fluorine, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, tungsten, chromium, molybdenum, rhenium, tantalum, phosphorus, and boron.
[0010] Another aspect of the present invention is a method for producing positive electrode active material particles, comprising the steps of heating lithium cobalt oxide, mixing a first additive element source with the heated lithium cobalt oxide to form a first mixture, heating the first mixture to form a first composite oxide, mixing the first composite oxide with a second additive element source to form a second mixture, heating the second mixture to form a second composite oxide, mixing the second composite oxide with a third additive element source to form a third mixture, and heating the third mixture at 750°C to 850°C and for 2 hours to 10 hours to form a third composite oxide, wherein the first additive element source comprises one or two elements selected from magnesium and fluorine, the second additive element source comprises one or two elements selected from nickel and aluminum, and the third additive element source comprises titanium.
[0011] In the present invention, the third additive element source preferably contains a titanium compound, and the titanium compound is added in an amount of 0.1 mol % to 1 mol % based on the lithium cobalt oxide.
[0012] In the present invention, the titanium compound is preferably lithium titanate (Li2TiO3). Effect of the Invention
[0013] According to one embodiment of the present invention, it is possible to provide a method for manufacturing a positive electrode active material having improved initial characteristics, and a method for manufacturing a secondary battery having the positive electrode active material.
[0014] Note that the description of these effects does not preclude the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of these effects. Note that effects other than these will become apparent from the description in the specification, drawings, claims, etc., and it is possible to extract effects other than these from the description in the specification, drawings, claims, etc. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1(A) is a cross-sectional view of a positive electrode active material, and FIG. 1(B) and FIG. 1(C) are diagrams illustrating the distribution of added elements. [Diagram 2] 2(A) and 2(B) are diagrams illustrating the results of the DSC analysis. [Diagram 3] Figure 3 is an example of a TEM image in which the crystal orientation is roughly consistent. [Figure 4] Figure 4(A) is an example of a STEM image in which the crystal orientations are roughly consistent, Figure 4(B) is an FFT pattern of the region of the rock-salt-type crystal RS, and Figure 4(C) is an FFT pattern of the region of the layered rock-salt-type crystal LRS. [Diagram 5] FIG. 5 is a diagram illustrating the crystal structure of the positive electrode active material. [Figure 6] FIG. 6 is a diagram illustrating the crystal structure of a conventional positive electrode active material. [Figure 7] FIG. 7 shows an XRD pattern calculated from the crystal structure. [Figure 8] FIG. 8 shows an XRD pattern calculated from the crystal structure. [Figure 9]9(A) and 9(B) show XRD patterns calculated from the crystal structure. [Figure 10] FIG. 10 is a cross-sectional view of the positive electrode active material. [Figure 11] FIG. 11 is a diagram illustrating a method for producing a positive electrode active material. [Figure 12] 12A to 12C are diagrams illustrating a method for manufacturing a positive electrode active material. [Figure 13] 13(A) and 13(B) are diagrams illustrating a method for producing a positive electrode active material. [Figure 14] 14(A) and 14(B) are diagrams illustrating a method for producing a positive electrode active material. [Figure 15] FIG. 15 is a diagram showing the external appearance of a secondary battery. [Figure 16] 16A to 16C are diagrams illustrating a method for manufacturing a secondary battery. [Figure 17] 17A to 17H are diagrams illustrating examples of electronic devices. [Figure 18] 18A to 18D are diagrams illustrating examples of electronic devices. [Figure 19] 19A to 19C are diagrams illustrating examples of electronic devices. [Figure 20] 20(A) to 20(C) are diagrams illustrating an example of a vehicle. [Figure 21] 21(A) and 21(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 22] 22(A) and 22(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 23] 23(A) and 23(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 24] 24(A) and 24(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 25] 25(A) and 25(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 26]26(A) and 26(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 27] 27(A) and 27(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 28] 28(A) and 28(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 29] 29(A) and 29(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 30] 30(A) and 30(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 31] 31(A) and 31(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 32] 32(A) and 32(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 33] 33(A) and 33(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 34] 34(A) and 34(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 35] 35(A) and 35(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 36] 36(A) and 36(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 37] 37(A) and 37(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 38] 38(A) and 38(B) show the results of a charge-discharge cycle test of the embodiment. [Figure 39] 39(A) and 39(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 40] 40(A) and 40(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 41] 41(A) and 41(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 42]42(A) and 42(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 43] 43(A) and 43(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 44] 44(A) and 44(B) show the results of a charge-discharge cycle test of the embodiment. [Diagram 45] FIG. 45 is a graph showing the results of XRD analysis of the positive electrode active material in a high-voltage charged state. [Figure 46] FIG. 46 shows the results of a charge-discharge cycle test of the embodiment. [Figure 47] FIG. 47 shows the results of a charge-discharge cycle test of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In the following, examples of embodiments of the present invention will be described with reference to the drawings, etc. However, the present invention should not be interpreted as being limited to the following examples. The embodiments of the present invention can be modified without departing from the spirit of the present invention.
[0017] In this specification, the initial characteristics in a charge-discharge cycle test refer to the characteristics up to the 15th cycle. The initial characteristics being good include the maximum discharge capacity being exhibited up to the 15th cycle in a charge-discharge cycle test, preferably the maximum discharge capacity being exhibited up to the 10th cycle, and more preferably the maximum discharge capacity being exhibited up to the 5th cycle. Furthermore, it is preferable that the initial characteristics are exhibited when no aging treatment is performed before the charge-discharge cycle test.
[0018] In this specification, the aging treatment includes a process of carrying out one or more cycles of charging and discharging at a temperature equal to or higher than room temperature (25°C), or holding the secondary battery at a temperature close to the upper limit of the temperature range in which the secondary battery is used (typically 60°C) for a long period of time. The aging treatment may further include a process of releasing gas generated in the area covered by the exterior body. The aging treatment can detect initial defects in the secondary battery. Furthermore, when one or more cycles of charging and discharging are carried out, a stable coating can be formed on the negative electrode active material.
[0019] In this specification, the space group is expressed using short notation of the international notation (or Hermann-Mauguin symbol). The crystal plane and crystal direction are expressed using Miller indices. In crystallography, the space group, crystal plane, and crystal direction are expressed by adding a superscript bar to the number, but in this specification, due to format restrictions, instead of adding a bar above the number, a - (minus sign) may be added before the number. Individual directions indicating directions within a crystal are expressed with [ ], collective directions indicating all equivalent directions are expressed with < >, individual planes indicating crystal planes are expressed with ( ), and collective planes with equivalent symmetry are expressed with {}. In addition, trigonal crystals expressed by the space group R-3m are generally sometimes expressed as a composite hexagonal lattice of hexagonal crystals for ease of understanding the structure. In addition, not only (hkl) but also (hkil) are sometimes used as Miller indices. Here, i is -(h+k). In this specification, for the space group R-3m, crystal planes and the like are represented as a compound hexagonal lattice unless otherwise specified.
[0020] In this specification etc., the space group of a crystal structure is identified by XRD (X-ray Diffraction), electron diffraction, neutron diffraction, etc. Therefore, in this specification etc., belonging to a certain space group, belonging to a certain space group, or being a certain space group can be rephrased as being identified with a certain space group.
[0021] In this specification, if the arrangement of anions is roughly close to cubic close-packed, it can be considered as cubic close-packed. The arrangement of anions in cubic close-packed refers to a state in which the second layer of anions is arranged on the voids of the anions packed in the first layer, and the third layer of anions is arranged directly above the voids of the second layer of anions, but not directly above the anions in the first layer. Therefore, the anions do not have to be strictly cubic lattices. In addition, since real crystals always have defects, the analysis results do not necessarily have to be theoretical. For example, in an FFT (fast Fourier transform) pattern such as an electron diffraction pattern or a TEM (Transmission Electron Microscope) image, a spot may appear at a position slightly different from the theoretical position. For example, if the deviation from the theoretical position and the orientation is 5 degrees or less, or 2.5 degrees or less, it can be said that the structure has a cubic close-packed structure.
[0022] In this specification, etc., the term "particle" may be used to indicate the shape of an active material or conductive material, and includes a spherical shape (a circular cross-sectional shape). In this specification, etc., the shape of an active material or conductive material is not limited to a spherical shape, and may include a cross-sectional shape of an ellipse, a rectangle, a trapezoid, a triangle, a square with rounded corners, an asymmetric shape, etc., and further, each particle may be of an irregular shape.
[0023] In this specification, when simply referring to a positive electrode active material, there are cases where a plurality of positive electrode active material particles are described, and cases where a single positive electrode active material particle is described, depending on the analytical method, etc. For example, in the case of descriptions regarding line analysis of a scanning transmission electron microscope-energy dispersive X-ray fluorescence detector (STEM; Scanning Transmission Electron Microscope-EDX: Energy Dispersive X-ray Spectroscopy), STEM-electron energy loss spectroscopy (STEM-EELS: Electron Energy Loss Spectroscopy), and electron diffraction, the description is of a single positive electrode active material particle unless otherwise specified. On the other hand, in the case of X-ray photoelectron spectroscopy (XPS: X-Ray Photoelectron Spectroscopy), XRD, various mass analyses, etc., the description is of a plurality of positive electrode active material particles unless otherwise specified.
[0024] In addition, when describing the characteristics of individual particles of the positive electrode active material in the following embodiments, etc., not all particles in the secondary battery necessarily have the characteristics. For example, if three or more randomly selected particles of the positive electrode active material have the characteristics, it can be said that there is a sufficient effect of improving the characteristics of the positive electrode active material and the secondary battery having it.
[0025] Unless otherwise specified, the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) of the secondary battery are described in the state before degradation. Note that a decrease in discharge capacity due to aging treatment in the secondary battery manufacturing stage is not called degradation. For example, a lithium-ion secondary battery having a discharge capacity of 97% or more of its rated capacity can be said to be in a state before degradation. For lithium-ion secondary batteries for portable devices, the rated capacity complies with JIS C 8711:2019. For other lithium-ion secondary batteries, the rated capacity complies with not only the above JIS standard but also with various JIS and IEC standards for electric vehicle propulsion, industrial use, etc.
[0026] In this specification and the like, the state of the material of the secondary battery before deterioration is referred to as the initial product or the initial state, and the state after deterioration (the state when the discharge capacity is less than 97% of the rated capacity of the secondary battery) may be referred to as the in-use product or the in-use state, or the used product or the used state.
[0027] In this specification and the like, the theoretical capacity of the positive electrode active material refers to the amount of electricity when all the insertable and removable lithium in the positive electrode active material has been removed. For example, the theoretical capacity of LiCoO2 is 274 mAh / g per unit weight of the active material, the theoretical capacity of LiNiO2 is 275 mAh / g per unit weight of the active material, and the theoretical capacity of LiMn2O4 is 148 mAh / g per unit weight of the active material.
[0028] In this specification and the like, the degree to which insertable and removable lithium remains in the positive electrode active material is indicated by x in the composition formula, for example, x in Li x CoO2. In the case of the positive electrode active material in the secondary battery, x = (theoretical capacity - charged capacity) / theoretical capacity can be used. For example, when a secondary battery using LiCoO2 as the positive electrode active material is charged to 219.2 mAh / g, it can be said that Li 0.2 CoO2 or x = 0.2. A small x in Li x CoO2 means, for example, 0.1 < x ≤ 0.24. In some cases, the degree of lithium desorbed from the positive electrode active material with respect to the theoretical capacity is indicated as the depth of charge. In this specification and the like, the depth of charge = 1 - x.
[0029] For example, when appropriately synthesized lithium cobaltate before use in the positive electrode approximately satisfies the stoichiometric ratio, it is LiCoO2 and x = 1 (at this time the depth of charge is 0). Also, the lithium cobaltate contained in the secondary battery after discharge is also LiCoO2 and can be said to be x = 1. Here, the end of discharge means, for example, a state where the voltage reaches 3.0 V or 2.5 V at a current of 100 mA / g or less.
[0030] Li xIt is preferable that the charge capacity and / or discharge capacity used to calculate x in CoO2 is measured under conditions that are free of or have little influence from short circuits and / or decomposition of the electrolyte, etc. For example, data from a secondary battery that has experienced a sudden change in capacity that is considered to be due to a short circuit should not be used to calculate x.
[0031] In this specification, the distribution of a certain element refers to a region in which the element is continuously detected in a non-noise range. The detection of the distribution of a certain element in a non-noise range includes the detection of the distribution of a certain element in a non-noise range when an analysis is performed multiple times.
[0032] (Embodiment 1) In this embodiment, a positive electrode active material particle 100 of one embodiment of the present invention will be described with reference to FIGS.
[0033] Fig. 1(A) is a cross-sectional view of a positive electrode active material particle 100 according to one embodiment of the present invention. The positive electrode active material particle 100 preferably has a surface layer portion 100a and an interior portion 100b. An example of the boundary between the surface layer portion 100a and the interior portion 100b is shown by a dashed line in Fig. 1(A).
[0034] In this specification, the surface layer 100a can be referred to as a region within 20 nm in the depth direction from the particle surface, a region within 10 nm in the depth direction from the particle surface, a region within 5 nm in the depth direction from the particle surface, or a region within 3 nm in the depth direction from the particle surface. The depth direction is a direction perpendicular or approximately perpendicular to the particle surface. Perpendicular or approximately perpendicular is a range of 80° to 100° with respect to the surface. Surfaces caused by cracks and / or fissures may also be referred to as the particle surface. The surface layer 100a is synonymous with the surface vicinity, surface vicinity region, or shell.
[0035] The region deeper than the surface layer 100a of the positive electrode active material can be referred to as the interior 100b, which is synonymous with the interior region or core.
[0036] The positive electrode active material particle 100 is preferably composed mainly of lithium cobalt oxide and belongs to the space group R-3m. The inner portion 100b preferably has a layered rock-salt type crystal structure. The surface portion 100a preferably has a rock-salt type crystal structure whose crystal orientation is the same or approximately the same as that of the layered rock-salt type. Of course, the surface portion 100a needs to have a layered rock-salt type crystal structure in order to enable the insertion and desorption of lithium ions. Therefore, it is preferable that the surface portion 100a has both the layered rock-salt type crystal structure and the rock-salt type crystal structure, that is, has the characteristics of both.
[0037] (001) in FIG. 1(A) indicates the (001) plane of lithium cobalt oxide, and the surface layer portion 100a includes a region having a (001) plane (a (001)-oriented region). When the positive electrode active material particle 100 has a layered rock-salt crystal structure, the surface layer portion 100a includes an edge region and a basal region. The edge region is a region having a surface exposed in a direction intersecting the (001) plane, or a region other than the (001)-oriented region. The basal region is a region having a surface parallel to the (001) plane, or a (001)-oriented region.
[0038] FIG. 1(B) and FIG. 1(C) are schematic diagrams showing the distribution of additive elements (additive elements will be described later) contained in the positive electrode active material particle 100. In FIG. 1(B) and FIG. 1(C), the horizontal axis indicates the distance from the measurement point, and the vertical axis indicates the concentration of the element. The distance from the measurement point includes the distance from the particle surface. Schematic diagrams such as FIG. 1(B) and FIG. 1(C) are obtained from graphs of cross-sectional analysis results. The analysis direction of the cross-sectional analysis is from the surface to the inside, and the analysis in this direction can also be called a depth direction analysis. The distance on the horizontal axis can also be called the depth. For the cross-sectional analysis, for example, STEM-EDX line analysis can be used.
[0039] The surface of the positive electrode active material particle 100 refers to the surface of the particle including the surface layer portion 100a and the interior portion 100b. Therefore, the positive electrode active material particle 100 does not include metal oxides such as aluminum oxide that do not have lithium sites that can contribute to charging and discharging, carbonates chemically adsorbed after the preparation of the positive electrode active material, hydroxyl groups, etc. attached to the positive electrode active material particle 100. The attached metal oxide refers to, for example, a metal oxide whose crystal orientation does not match that of the interior portion 100b.
[0040] In addition, the electrolyte, organic solvent, binder, conductive material, or compounds derived therefrom that are attached to the positive electrode active material particles 100 are also not included in the positive electrode active material particles 100. The attached electrolyte, organic solvent, binder, conductive material, or compounds derived therefrom can be removed by washing.
[0041] Although not shown, the positive electrode active material particle 100 may have a crystal grain boundary. The crystal grain boundary refers to, for example, a portion where the particles of the positive electrode active material particle 100 are fixed to each other, a portion where the crystal orientation changes inside the positive electrode active material particle 100, that is, a portion where the repetition of bright and dark lines in a STEM image or the like becomes discontinuous, a portion containing many crystal defects, a portion where the crystal structure is disordered, and the like. The crystal defect refers to a defect that can be observed in a cross-sectional TEM (transmission electron microscope) image, a cross-sectional STEM image, and the like, that is, a structure in which other atoms have entered between lattices, a cavity, and the like. The crystal grain boundary can be said to be one of the plane defects. The vicinity of the crystal grain boundary refers to a region within 10 nm from the crystal grain boundary.
[0042] <Contained elements> The positive electrode active material particles 100 have lithium, a transition metal M, oxygen, and an additive element. The transition metal M is at least one selected from cobalt, nickel, and manganese. When cobalt is selected as the transition metal M, the positive electrode active material particles 100 can be said to be lithium cobalt oxide (LiCoO2) to which the additive element has been added. However, the positive electrode active material particles 100 only need to have a crystal structure described later. Therefore, the composition is not strictly limited to Li:Co:O=1:1:2 (atomic ratio).
[0043] The positive electrode active material of a lithium ion secondary battery needs to have a transition metal M capable of oxidation and reduction in order to maintain charge neutrality even when lithium ions are inserted and removed. The positive electrode active material particle 100 of one embodiment of the present invention preferably uses cobalt as the transition metal M responsible for the oxidation and reduction reaction. If the positive electrode active material particle 100 contains 75 atomic % (sometimes referred to as atomic %) or more of cobalt, preferably 90 atomic % or more, and more preferably 95 atomic % or more of the transition metals contained therein, it is preferable because it has many advantages such as being relatively easy to synthesize and easy to handle, and having excellent cycle characteristics.
[0044] In addition, when the transition metals contained in the positive electrode active material particles 100 are 75 atomic % or more, preferably 90 atomic % or more, and more preferably 95 atomic % or more, the stability when a large amount of lithium is released by charging is superior to that of a composite oxide in which nickel, such as lithium nickel oxide (LiNiO2), accounts for the majority of the transition metal. This is thought to be because cobalt is less affected by distortion due to the Jahn-Teller effect than nickel. The strength of the Jahn-Teller effect in transition metal compounds varies depending on the number of electrons in the d orbital of the transition metal. Layered rock salt type composite oxides in which low-spin nickel (III) in octahedral coordination accounts for the majority of the transition metal M, such as lithium nickel oxide, are greatly affected by the Jahn-Teller effect, and distortion is likely to occur in the layer consisting of octahedra of nickel and oxygen. Therefore, there is a growing concern that the crystal structure will collapse during the charge and discharge cycle. In addition, nickel ions have a larger ionic radius than cobalt ions, and the ionic radius is close to the ionic radius of lithium ions. Therefore, in layered rock-salt complex oxides in which nickel accounts for the majority of the transition metal M, such as lithium nickel oxide, there is a problem in that cation mixing of nickel and lithium is likely to occur.
[0045] <Additional elements> The additive element contained in the positive electrode active material particle 100 is preferably one or more selected from magnesium, titanium, nickel, aluminum, fluorine, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, tungsten, chromium, molybdenum, rhenium, tantalum, phosphorus, and boron. Nickel may be used as the main component of the positive electrode active material particle 100, and nickel may be added to such positive electrode active material particle 100. When the positive electrode active material particle 100 is manufactured, specifically, a compound containing the additive element is prepared. Therefore, the additive element may be called the raw material of the positive electrode active material particle 100.
[0046] The additive element contained in the positive electrode active material particle 100 exhibits a detection value of characteristic X-rays that can be determined not to be noise in terms of intensity and spatial resolution in STEM-EDX line analysis. A region where detection amounts are continuously obtained is called a distribution region. In addition, it is preferable that a maximum value of the detection amount of characteristic X-rays, that is, a peak of the detection amount of characteristic X-rays (sometimes simply referred to as detection amount), is confirmed in the distribution region. A plurality of the above peaks may be confirmed in the distribution region.
[0047] It is more preferable that the positive electrode active material particle 100 has a plurality of additive elements. When the positive electrode active material particle 100 has a plurality of additive elements, the distribution of each additive element may be different. The difference in distribution includes the difference in the position (peak position) showing the peak of the detection amount. In addition, it is preferable that one or more selected from the additive elements contained in the positive electrode active material particle 100 are distributed so as to have a concentration gradient.
[0048] The additive element is preferably dissolved in the positive electrode active material particle 100. Therefore, for example, when a line analysis is performed by STEM-EDX, the additive element is preferably present at a position deeper than the position where cobalt begins to be detected, that is, on the inner side of the positive electrode active material particle 100.
[0049] As described below, these additive elements further stabilize the crystal structure of the positive electrode active material particles 100. The additive elements that exert the effect of further stabilizing the crystal structure are preferably present at a higher concentration in the surface layer portion 100a than in the interior portion 100b. In other words, it is preferable that the detected amount of the additive elements is greater in the surface layer portion 100a than in the interior portion 100b.
[0050] In the case where the additive element is magnesium, fluorine, nickel, or titanium, the peak of the detectable amount is preferably located at a distance of 20 nm or less from the surface layer 100a or the surface. The additive element may have a plurality of detectable amount peaks, but it is preferable that the maximum value of the peaks (maximum peak) is located at a distance of 20 nm or less from the surface layer 100a or the surface.
[0051] The additive element does not necessarily have to include fluorine, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, tungsten, chromium, molybdenum, rhenium, tantalum, phosphorus, or boron.
[0052] For example, if the positive electrode active material particles 100 are substantially free of manganese, the above-mentioned advantages of being relatively easy to synthesize and easy to handle, and having excellent cycle characteristics, will be even greater. The weight of manganese contained in the positive electrode active material particles 100 is preferably, for example, 600 ppm or less, more preferably 100 ppm or less.
[0053] 〔titanium〕 The presence of titanium as an additive element in the surface layer portion 100a can promote the insertion and desorption of lithium ions into and from the positive electrode active material particles 100.
[0054] Although titanium exists stably in the octahedral sites of 6-coordinated oxygen atoms in oxides, titanium oxide and lithium titanate cannot form a stable layered rock-salt crystal structure. For example, titanium oxide TiO2 has the most stable rutile crystal structure, while lithium titanate Li4Ti5O 12has a spinel-type crystal structure. Therefore, when a small amount of titanium is dissolved in the surface layer 100a having a layered rock-salt type or rock-salt type crystal structure, defects are generated in part of the crystal structure of the surface layer 100a.
[0055] Lithium cobalt oxide is in a discharged state (i.e., Li x It is known that when x in CoO2 is 1, the band gap is large and the resistance is high. Therefore, by introducing titanium defects into a part of the surface layer 100a, the band gap can be narrowed and the resistance can be reduced.
[0056] Cobalt is also present in the oxide. 3+ is the most stable, whereas titanium is Ti 4+ is the most stable. Therefore, the charge on the lithium ion is relatively lower around titanium than around cobalt. 4+ Defects may be induced in the cation sites near titanium, and such defects reduce the diffusion resistance of cations, especially lithium ions. Therefore, the diffusion resistance of lithium ions is small around titanium. Note that some of the cobalt around titanium is Co 3+ Not Co 2+ It is.
[0057] Therefore, the presence of titanium in surface layer portion 100a can reduce the diffusion resistance of lithium ions at the interface between the electrolyte and positive electrode active material particles 100.
[0058] If the amount of titanium is too small, the effect of promoting the insertion and desorption of lithium ions described above is not fully exhibited. On the other hand, if the amount of titanium is too large, there is a risk of forming a heterophase (such as Mg2TiO4 with an ilmenite-type crystal structure) with other added elements including magnesium. Furthermore, there is a risk of magnesium being taken away by the formation of a heterophase, which reduces the magnesium concentration in the surface layer 100a, whose crystal structure roughly coincides with that of the interior 100b. 4.6V (vs. Li / Li +For the positive electrode active material particles 100 charged at a high voltage exceeding 100 V, it is preferable for the surface layer 100a to have magnesium in order to suppress phase change. Therefore, the loss of magnesium due to the formation of a different phase is a major disadvantage. In addition, if there are too many defects due to titanium, there is a concern that oxygen will be easily desorbed from the surface. Therefore, it is preferable that titanium, together with magnesium, fluorine, etc., is present at the surface and the area close to the surface of the surface layer 100a at a concentration lower than that of magnesium.
[0059] Specifically, the ratio of Ti atoms to Co atoms in the entire positive electrode active material is preferably 0.0001 (atomic ratio) or more, more preferably 0.001 (atomic ratio) or more, and is preferably less than 0.0075 (atomic ratio), more preferably 0.004 (atomic ratio) or less, and even more preferably 0.003 (atomic ratio) or less.
[0060] Furthermore, in an EDX line analysis of the surface layer 100a, when the denominator is the sum of carbon, oxygen, fluorine, magnesium, aluminum, silicon, phosphorus, sulfur, calcium, titanium, iron, cobalt, nickel, gallium, and molybdenum, the maximum titanium concentration is preferably 0.3 atomic% or more and 3 atomic% or less, and more preferably 0.5 atomic% or more and 2 atomic% or less.
[0061] A compound containing titanium (titanium compound) is used as the titanium source, and examples of the titanium compound include titanium oxide and lithium titanate. Titanium oxide includes a compound represented by TiO2, and lithium titanate includes a compound represented by Li2TiO3 and LiTiO2. One or more of the above compounds can be used as the titanium source.
[0062] The added element for promoting the insertion and desorption of lithium ions is not limited to titanium. Other elements may be added. When using an element other than titanium, it is preferable that the element is stable in the oxide at the octahedral oxygen hexahedral position, but the oxide of lithium and the element does not have a stable layered rock salt type crystal structure. In addition, an element that is stable at a higher oxidation number than cobalt is preferable. For example, niobium, manganese, tungsten, chromium, molybdenum, rhenium, tantalum, etc. can be used.
[0063] 〔distribution〕 Among the additive elements, the distribution of magnesium and titanium will be specifically described. The distribution of magnesium and titanium are illustrated in FIG. 1(B) and the like. The horizontal axis of FIG. 1(B) corresponds to X1 to X2 of the positive electrode active material particle 100 shown in FIG. 1(A). It is preferable that magnesium is distributed so that the concentration of the surface layer 100a is higher than that of the inside 100b. It is preferable that titanium is distributed so that the concentration of the surface layer 100a is higher than that of the inside 100b. The above-mentioned concentration of the surface layer 100a being higher than that of the inside 100b can be said to be that the detection amount of the surface layer 100a is greater than that of the inside 100b. As shown in FIG. 1(B), when the position where the magnesium distribution rises and the position where the titanium distribution rises overlap, and the position where the magnesium distribution falls and the position where the titanium distribution falls overlap, it is said that the distributions of each other overlap. That is, it is preferable that the distributions of magnesium and titanium overlap each other. In addition, when the area between the position where the magnesium distribution rises and the position where the magnesium distribution falls overlaps, and the area between the position where the titanium distribution rises and the position where the titanium distribution falls, it is said that the two distributions have an overlapping region.
[0064] Furthermore, as shown in FIG. 1(B), the magnesium peak, typically the maximum peak, is preferably present in the surface layer 100a, and more preferably in a region closer to the surface of the surface layer 100a. For example, the magnesium concentration peak is preferably present on the surface or within 3 nm from the reference point. Furthermore, the titanium peak, typically the maximum peak, is preferably present in the surface layer 100a, and more preferably in a region closer to the surface of the surface layer 100a, and more preferably in a region closer to the surface of the surface layer 100a. The magnesium peak position and the titanium peak position may overlap each other. Furthermore, when the magnesium peak position and the titanium peak position are different, the difference in the peak positions is preferably within 3 nm, preferably within 1 nm. When the full width at half maximum of the distribution based on the peak can be obtained, it is preferable that the full width at half maximum of the titanium distribution is narrower than the full width at half maximum of the magnesium distribution.
[0065] As shown in Fig. 1(C), the nickel distribution preferably overlaps or has an overlapping region with the magnesium distribution and titanium distribution. The nickel peak position is preferably present in the surface layer portion 100a, and more preferably in a region of the surface layer portion 100a closer to the surface. For example, the nickel concentration peak position is preferably present on the surface or within 3 nm from the reference point. In addition, when the full width at half maximum based on the peak position of the detected amount can be obtained, it is preferable that the full width at half maximum of the nickel distribution is narrower than the full width at half maximum of the magnesium distribution.
[0066] It is preferable that the surface layer 100a has an edge region where the distributions of magnesium and nickel overlap, or where the distributions of magnesium and titanium overlap, or where the distributions of magnesium, nickel, and titanium overlap. On the other hand, the above-mentioned overlapping region is not necessarily required in the basal region of the surface layer 100a.
[0067] The amount of magnesium detected in the interior 100b is small compared to the surface layer 100a, and magnesium is preferably present in a dilute state in the interior 100b. The amount of titanium detected in the interior 100b may be very small compared to the surface layer 100a, not detectable, or 1 atomic % or less. The amount of nickel detected in the interior 100b may be very small compared to the surface layer 100a, not detectable, or 1 atomic % or less.
[0068] Although not shown, it is preferable that the amount of fluorine detected in the surface layer 100a is greater than the amount of fluorine detected in the interior 100b, as with magnesium. It is also preferable that the surface layer 100a has a peak of the amount of detection closer to the surface. For example, it is preferable that the peak of the amount of detection is on the surface or within 3 nm from the reference point. Similarly, it is preferable that the amount of silicon, phosphorus, boron and / or calcium detected in the surface layer 100a is greater than the amount of detection in the interior 100b. It is also preferable that the amount of detection is closer to the surface of the surface layer 100a. For example, it is preferable that the peak of the amount of detection is on the surface or within 3 nm from the reference point.
[0069] Also, the peak position of the detected amount of aluminum is preferably located inside the distribution of magnesium or titanium as shown in FIG. 1(B) or FIG. 1(C). In other words, it is preferable that at least aluminum, among the added elements, has a peak of the detected amount inside magnesium or titanium. The distribution of magnesium or titanium may have an overlapping area with the distribution of aluminum, but there may be almost no overlapping area as in FIG. 1(B) and FIG. 1(C). The peak of the detected amount of aluminum may be present in the surface layer portion 100a, or may be deeper than the surface layer portion 100a. For example, it is preferable that the peak position is located on the surface, or in a region of 5 nm to 30 nm from the reference point toward the inside.
[0070] By distributing aluminum as described above, the layered rock-salt crystal structure of the positive electrode active material particle 100 can be more stabilized. For example, it is expected that the surface layer 100a of the positive electrode active material particle 100 is prevented from changing from the layered rock-salt crystal structure to the spinel crystal structure. The spinel crystal structure generated in the layered rock-salt crystal structure may move or expand with the movement of the charge of the transition metal M. In addition, defects such as grain boundaries in the positive electrode active material particle 100 may become a diffusion path for lithium ions in the c-axis direction. Additive elements such as aluminum may be contained in the vicinity of the defects. In other words, it can be said that the presence of aluminum may make it easier for lithium ions to diffuse.
[0071] The reason why aluminum is distributed deeper into the material than magnesium or titanium is believed to be because the diffusion rate of aluminum is faster than that of magnesium, etc. On the other hand, the reason why the amount of aluminum detected in the region closest to the surface is low is presumably because aluminum exists more stably in regions where magnesium, etc. are not present than in regions where they are dissolved in high concentrations.
[0072] More specifically, in the region of the layered rock-salt type of space group R-3m or the cubic rock-salt type, where magnesium is dissolved at a high concentration, the distance between the cation and oxygen is longer than in the layered rock-salt type LiAlO2, making it difficult for aluminum to exist stably. + Mg 2+ The valence change due to substitution to Co 3+ From Co 2+ However, since Al can only be trivalent, it is thought that it is difficult for it to exist stably near magnesium in the rock salt or layered rock salt structure.
[0073] Although not shown, it is preferable that manganese has a detection amount peak inside magnesium, similar to aluminum.
[0074] However, the additive element does not necessarily have to have the same concentration gradient or distribution throughout the entire surface layer portion 100a of the positive electrode active material particle 100.
[0075] The (001)-oriented surface of the positive electrode active material particle 100 may have a different distribution of additive elements from the other surfaces. For example, the (001)-oriented surface and its surface layer 100a may have a lower detection amount of one or more additive elements selected from the additive elements compared to surfaces other than the (001)-oriented surface. Specifically, the detection amount of one or more of magnesium, nickel, and titanium may be low. Alternatively, the (001)-oriented surface and its surface layer 100a may have one or more additive elements that are not detected or have a detection amount of 1 atomic % or less. Specifically, the detection amount of nickel may be not detected or have a detection amount of 1 atomic % or less. In particular, in the case of an analysis method that detects characteristic X-rays such as EDX, since the energy of Kβ of cobalt and Kα of nickel are close, it is difficult to detect a trace amount of nickel in a material in which cobalt is the main element. Alternatively, the (001)-oriented surface and its surface layer 100a may have a peak of the detection amount of one or more additive elements that are shallower from the surface compared to surfaces other than the (001)-oriented surface. Specifically, the peaks of detected amounts of magnesium and aluminum may be shallower compared to other surfaces.
[0076] In the layered rock-salt crystal structure of R-3m, the cations are arranged parallel to the (001) plane. This means that the MO2 layers and lithium layers are alternately stacked parallel to the (001) plane. Therefore, the diffusion path of lithium ions is also parallel to the (001) plane.
[0077] Since the MO2 layer is relatively stable, it is more stable for the surface of the positive electrode active material particle 100 to have a (001) orientation. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) plane.
[0078] On the other hand, the diffusion path of lithium ions is exposed on the surface other than the (001) orientation. Therefore, the surface and the surface layer 100a other than the (001) orientation are important regions for maintaining the diffusion path of lithium ions, and at the same time, they are regions from which lithium ions are first desorbed and are therefore prone to become unstable. Therefore, it is extremely important to reinforce the surface and the surface layer 100a other than the (001) orientation in order to maintain the crystal structure of the entire positive electrode active material particle 100.
[0079] Therefore, in the positive electrode active material particle 100 according to another embodiment of the present invention, it is important that the distribution of the additive elements in the surface other than the (001) orientation and in the surface layer 100a thereof is, for example, as shown in Fig. 1(B) or 1(C). Of the additive elements, nickel is particularly preferably detected in the surface other than the (001) orientation and in the surface layer 100a thereof. On the other hand, in the (001) oriented surface and in the surface layer 100a thereof, the concentration of the additive element may be low or absent as described above.
[0080] For example, the magnesium distribution in the (001) oriented surface and its surface layer 100a preferably has a full width at half maximum of 10 nm to 200 nm, more preferably 50 nm to 150 nm, and even more preferably 80 nm to 120 nm. Also, the magnesium distribution in the non-(001) oriented surface and its surface layer 100a preferably has a full width at half maximum of more than 200 nm to 500 nm, more preferably more than 200 nm to 300 nm, and even more preferably 230 nm to 270 nm.
[0081] Furthermore, the nickel distribution in the non-(001) oriented surface and in the surface layer 100a thereof preferably has a full width at half maximum of 30 nm to 150 nm, more preferably 50 nm to 130 nm, and even more preferably 70 nm to 110 nm.
[0082] In a manufacturing method described in a later embodiment in which high-purity LiCoO2 is produced, and then additive elements are mixed and heated, the additive elements spread mainly through the diffusion path of lithium ions, and therefore the distribution of the additive elements in the surface other than the (001) orientation and in the surface layer portion 100a thereof is easily controlled to a preferred range.
[0083] 〔magnesium〕 Magnesium ions are divalent cations, and since magnesium ions are more stable at the lithium site than at the cobalt site in the layered rock-salt crystal structure, they are more likely to enter the lithium site. The presence of magnesium at an appropriate concentration at the lithium site of the surface layer 100a makes it easier to maintain the layered rock-salt crystal structure. This is presumably because the magnesium present at the lithium site functions as a pillar supporting the MO2 layers. The presence of magnesium also allows Li x When x in CoO2 is, for example, 0.24 or less, the detachment of oxygen from around magnesium can be suppressed. In addition, the presence of magnesium is expected to increase the density of the positive electrode active material particles 100. In addition, if the magnesium concentration in the surface layer portion 100a is high, it is expected that the corrosion resistance against hydrofluoric acid generated by decomposition of the electrolyte solution will be improved.
[0084] At an appropriate concentration, magnesium does not adversely affect the insertion and desorption of lithium during charging and discharging, and the above benefits can be enjoyed. However, excessive magnesium may adversely affect the insertion and desorption of lithium. Furthermore, the effect of stabilizing the crystal structure may be reduced. This is thought to be because magnesium enters the cobalt site in addition to the lithium site. In addition, unnecessary magnesium compounds (oxides, fluorides, etc.) that do not substitute for either the lithium site or the cobalt site may segregate on the surface of the positive electrode active material, and may become resistance components of the secondary battery. In addition, as the magnesium concentration of the positive electrode active material increases, the discharge capacity of the positive electrode active material may decrease. This is thought to be because too much magnesium enters the lithium site, reducing the amount of lithium that contributes to charging and discharging.
[0085] Therefore, it is preferable that the amount of magnesium contained in the entire positive electrode active material particle 100 is appropriate. For example, the number of magnesium atoms is preferably 0.002 to 0.06 times the number of cobalt atoms, more preferably 0.005 to 0.03 times, and even more preferably about 0.01 times. The amount of magnesium contained in the entire positive electrode active material particle 100 may be a value obtained by performing an elemental analysis of the entire positive electrode active material particle 100 using, for example, Glow Discharge-Mass Spectrometry (GD-MS) or Inductively Coupled Plasma-Mass Spectrometry (ICP-MS), or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material particle 100.
[0086] 〔nickel〕 In the layered rock salt crystal structure of LiCoO2, nickel can exist in either the cobalt site or the lithium site. When nickel exists in the cobalt site, it has a lower redox potential than cobalt, so it is easier to release lithium and electrons during charging, for example. This is expected to result in faster charging and discharging speeds. Therefore, even with the same charging voltage, a larger charge and discharge capacity can be obtained when the transition metal M is nickel than when it is cobalt.
[0087] In addition, when nickel is present at the lithium site, the shift in the layered structure consisting of octahedra of cobalt and oxygen can be suppressed. The change in volume caused by charging and discharging is also suppressed. The elastic modulus also increases, that is, the material becomes harder. This is presumably because the nickel present at the lithium site also functions as a pillar supporting the MO2 layers. Therefore, it is expected that the crystal structure will become more stable, especially at high temperatures, for example, at 45°C or higher when the battery is in a charged state.
[0088] In addition, the distance between cations and anions in nickel oxide (NiO) is closer to the average distance between cations and anions in LiCoO2 than rock-salt MgO and rock-salt CoO, making it easier for the orientation to match that of LiCoO2.
[0089] In addition, the order of ionization tendency is lowest for magnesium, followed by aluminum, cobalt, and nickel (Mg>Al>Co>Ni). Therefore, nickel is thought to be less likely to dissolve into the electrolyte during charging than the other elements listed above. Therefore, it is thought to have a high effect of stabilizing the crystal structure of the surface layer when in a charged state.
[0090] Furthermore, nickel is Ni 2+ , Ni 3+ , Ni 4+ Of which, Ni 2+ is the most stable, and nickel has a higher trivalent ionization energy than cobalt. Therefore, it is known that nickel and oxygen alone do not form a spinel crystal structure. Therefore, nickel is thought to have the effect of suppressing the phase change from the layered rock salt type to the spinel type crystal structure.
[0091] On the other hand, an excess of nickel is undesirable because it increases the influence of distortion due to the Jahn-Teller effect, and too much nickel can also adversely affect the insertion and extraction of lithium.
[0092] Therefore, it is preferable that the amount of nickel contained in the entire positive electrode active material particle 100 is appropriate. For example, the number of nickel atoms contained in the positive electrode active material particle 100 is preferably more than 0% and 7.5% or less of the number of cobalt atoms, more preferably 0.05% to 4%, more preferably 0.1% to 2%, and more preferably 0.2% to 1%. Alternatively, more than 0% and 4% or less is preferable. Alternatively, more than 0% and 2% or less is preferable. Alternatively, more than 0.05% to 7.5% or less is preferable. Alternatively, more than 0.1% to 7.5% or less is preferable. Alternatively, more than 0.1% to 4% is preferable. The amount of nickel shown here may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.
[0093] 〔aluminum〕 Aluminum can also be present at the cobalt site in the layered rock salt crystal structure. Aluminum is a typical trivalent element and its valence does not change, so lithium around the aluminum is less likely to move during charging and discharging. Therefore, aluminum and its surrounding lithium function as columns, and can suppress changes in the crystal structure. Therefore, as described below, even if the positive electrode active material particle 100 is subjected to a force that causes it to expand and contract in the c-axis direction due to the insertion and desorption of lithium ions, that is, even if a force that causes it to expand and contract in the c-axis direction is applied by changing the charge depth or charge rate, deterioration of the positive electrode active material particle 100 can be suppressed.
[0094] Aluminum also has the effect of suppressing the elution of surrounding cobalt and improving the continuous charging resistance. Furthermore, since the Al-O bond is stronger than the Co-O bond, it is possible to suppress the detachment of oxygen from the surroundings of aluminum. These effects improve the thermal stability. Therefore, when aluminum is contained as an additive element, the safety of the positive electrode active material particles 100 used in a secondary battery can be improved. Furthermore, the positive electrode active material particles 100 can be made to have a crystal structure that is not easily broken even when the charge and discharge are repeated.
[0095] On the other hand, an excess of aluminum may adversely affect the insertion and extraction of lithium.
[0096] Therefore, it is preferable that the amount of aluminum contained in the entire positive electrode active material particle 100 is appropriate. For example, the number of aluminum atoms contained in the entire positive electrode active material particle 100 is preferably 0.05% to 4% of the number of cobalt atoms, preferably 0.1% to 2% and more preferably 0.3% to 1.5%. Alternatively, 0.05% to 2% is preferable. Alternatively, 0.1% to 4% is preferable. The amount contained in the entire positive electrode active material particle 100 here may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material particle 100 using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material particle 100.
[0097] [Fluorine] Fluorine is a monovalent anion, and when part of the oxygen in the surface layer portion 100a is replaced by fluorine, the lithium desorption energy is reduced. This is because the redox potential of the cobalt ion accompanying lithium desorption differs depending on the presence or absence of fluorine. In other words, when there is no fluorine, the cobalt ion changes from trivalent to tetravalent as lithium desorption occurs. On the other hand, when there is fluorine, the cobalt ion changes from divalent to trivalent as lithium desorption occurs. The redox potential of the cobalt ion differs between the two. Therefore, when part of the oxygen in the surface layer portion 100a of the positive electrode active material particle 100 is replaced by fluorine, it can be said that the desorption and insertion of lithium ions near the fluorine easily occurs. Therefore, when the positive electrode active material particle 100 is used in a secondary battery, the charge / discharge characteristics, large current characteristics, etc. can be improved. In addition, the presence of fluorine in the surface layer portion 100a having the surface that is in contact with the electrolyte, or the attachment of fluoride to the surface, can suppress excessive reaction between the positive electrode active material particle 100 and the electrolyte. In addition, the corrosion resistance to hydrofluoric acid can be effectively improved.
[0098] In addition, when the melting point of fluorides such as lithium fluoride is lower than that of other additive element sources, it can function as a flux (also called a fluxing agent) that lowers the melting point of the other additive element sources. When the raw materials contain LiF and MgF2, the eutectic point of LiF and MgF2 is around 742°C, so it is preferable to set the heating temperature to 742°C or higher in the heating step after mixing the additive elements.
[0099] Here, the differential scanning calorimetry (DSC) measurement of the fluoride and the mixture will be described with reference to Fig. 2(A) and Fig. 2(B). In Fig. 2(A) and Fig. 2(B), the horizontal axis indicates temperature, and the vertical axis indicates heat flow. The temperature is the temperature of the sample. The DSC measurement apparatus and conditions are not particularly limited, but in this embodiment, the measurement was performed with the following apparatus and conditions. DSC equipment: Rigaku, EVO2 DSC8271 Heating rate: 20℃ / min The measurement results were analyzed using the Thermo prus EVO software to perform background correction and estimate the initial melting temperature T im , melting peak temperature T pm and the end of melting temperature T em The heat flow was calculated as the heat flow rate per sample weight.
[0100] Figure 2(A) shows the results of a DSC measurement of a mixture of lithium fluoride and magnesium fluoride as fluorides with a molar ratio of LiF:MgF2 = 1:3. Figure 2(B) shows the results of a DSC measurement of the mixture with lithium cobalt oxide (C-10N, manufactured by Nippon Chemical Industry Co., Ltd.) added. The mixture was mixed with a molar ratio of LiCoO2:LiF:MgF2 = 100:0.33:1.
[0101] As shown in Figure 2(A), the initial melting temperature T im is 731℃, melting peak temperature T pm is 739℃, and the end temperature of melting T em The T of the mixture of lithium cobalt oxide, lithium fluoride, and magnesium fluoride is 746°C. im is 779℃, T pm is 815℃, T em is 826°C.
[0102] Therefore, the heating temperature after mixing the additive element is preferably 731°C or higher, and more preferably 826°C or higher. It may also be 800°C or higher, which is between these temperatures. A higher heating temperature is preferable because the reaction proceeds more easily, the heating time is shorter, and productivity is high, but if the temperature is too high, there is a risk of decomposition of lithium cobalt oxide. Therefore, the upper limit of the heating temperature is set to be below the melting point of lithium cobalt oxide (1130°C). At temperatures near the melting point, there is a concern that lithium cobalt oxide may decompose, although only in small amounts. Therefore, a temperature of 1000°C or lower is more preferable.
[0103] [Other additive elements] When phosphorus is present in the surface layer 100a, Li xWhen x in CoO2 is kept small, it is preferable because short-circuiting between the positive and negative electrodes can be suppressed. For example, it is preferable that CoO2 exists in the surface layer portion 100a as a compound containing phosphorus and oxygen.
[0104] In the case where the positive electrode active material particles 100 contain phosphorus, it is possible that the hydrogen fluoride generated by decomposition of the electrolytic solution or electrolyte reacts with the phosphorus, thereby decreasing the hydrogen fluoride concentration in the electrolyte, which is preferable.
[0105] When the electrolyte contains LiPF6, hydrogen fluoride may be generated by hydrolysis. In addition, hydrogen fluoride may be generated by a reaction between polyvinylidene fluoride (PVDF), which is used as a component of the positive electrode, and an alkali. By reducing the hydrogen fluoride concentration in the electrolyte, corrosion of the current collector and / or peeling of the coating 104 may be suppressed. In addition, a decrease in adhesion due to gelation and / or insolubilization of PVDF may be suppressed.
[0106] When the positive electrode active material particles 100 contain phosphorus together with magnesium, Li xThis is preferable because the stability is extremely high when x in CoO2 is small. When the positive electrode active material particle 100 contains phosphorus, the number of phosphorus atoms is preferably 1% to 20% of the number of cobalt atoms, more preferably 2% to 10%, and even more preferably 3% to 8%. Or preferably 1% to 10%. Or preferably 1% to 8%. Or preferably 2% to 20%. Or preferably 2% to 8%. Or preferably 3% to 20%. Or preferably 3% to 10%. In addition, the number of magnesium atoms is preferably 0.1% to 10% of the number of cobalt atoms, more preferably 0.5% to 5%, and more preferably 0.7% to 4%. Or preferably 0.1% to 5%. Or preferably 0.1% to 4%. Or preferably 0.5% to 10%. Or preferably 0.5% to 4%. Or preferably 0.7% to 10%. Alternatively, 0.7% or more and 5% or less is preferable. The phosphorus and magnesium concentrations shown here may be values obtained by performing elemental analysis of the entire positive electrode active material particle 100 using, for example, GD-MS, ICP-MS, or the like, or may be based on values of the blending of raw materials in the process of producing the positive electrode active material particle 100.
[0107] Furthermore, when the positive electrode active material particle 100 has a crack, the progression of the crack can be suppressed by the presence of phosphorus, more specifically, a compound containing phosphorus and oxygen, inside the positive electrode active material with the crack on its surface, for example, in the embedded portion.
[0108] [Synergistic effect of multiple added elements] Furthermore, when the surface layer 100a contains both magnesium and nickel, there is a possibility that the divalent nickel can exist more stably near the divalent magnesium. x Even when x in CoO2 is small, the elution of magnesium can be suppressed, which can contribute to the stabilization of the surface layer portion 100a.
[0109] For the same reason, in the manufacturing process, when adding an additive element to lithium cobalt oxide, it is preferable that magnesium is added in a process before nickel. Alternatively, it is preferable that magnesium and nickel are added in the same process. Magnesium has a large ionic radius and tends to remain in the surface layer of lithium cobalt oxide regardless of the process in which it is added, whereas nickel can diffuse widely inside lithium cobalt oxide in the absence of magnesium. Therefore, if nickel is added before magnesium, there is a concern that nickel will diffuse into the lithium cobalt oxide and will not remain in the surface layer in a desired amount.
[0110] Furthermore, when the surface layer 100a contains magnesium, nickel, and titanium, the presence of nickel suppresses the formation of heterogeneous phases, including MgTiO3 with an ilmenite crystal structure. The ilmenite crystal structure has hexagonal close-packed anions, which is different from the cubic close-packed rock salt and layered rock salt crystal structures, and therefore requires a certain amount of activation energy for phase transition. NiO(II) is a compound with low chemical activity, and therefore has the effect of suppressing the formation of MgTiO3.
[0111] For the above reasons, when adding an additive element to lithium cobalt oxide in the manufacturing process, if titanium is added in a process later than magnesium and nickel, the effect of nickel in suppressing the formation of heterogeneous phases can be more pronounced.
[0112] Also, if the positive electrode active material particle 100 has additive elements with different distributions, it is preferable because it can stabilize the crystal structure in a wider region. For example, if the positive electrode active material particle 100 has both magnesium and nickel distributed in a region closer to the surface of the surface layer portion 100a and aluminum distributed in a deeper region, it can stabilize the crystal structure in a wider region than if it had only one of them. In this way, when the positive electrode active material particle 100 has additive elements with different distributions, aluminum is not essential for the surface because the stabilization of the surface can be sufficiently achieved by magnesium, nickel, etc. Rather, it is preferable that aluminum is widely distributed in a deeper region. For example, it is preferable that aluminum is continuously detected in a region from the surface to a depth of 1 nm to 25 nm. It is preferable that aluminum is widely distributed in a region from 0 nm to 100 nm from the surface, preferably from 0.5 nm to 50 nm from the surface, because it can stabilize the crystal structure in a wider region.
[0113] When a plurality of additive elements are contained as described above, the effects of the respective additive elements are synergistic and can contribute to further stabilization of the surface layer portion 100a. In particular, when magnesium, nickel, and aluminum are contained, the effect of providing a stable composition and crystal structure is high, and this is preferable.
[0114] However, if the surface layer 100a is occupied only by a compound of the added element and oxygen, it is not preferable because it makes it difficult to insert and remove lithium. For example, it is not preferable for the surface layer 100a to be occupied only by MgO or a structure in which MgO and MO(II) are solid-solved. Therefore, the surface layer 100a must contain at least a transition metal M such as cobalt, and must also contain lithium in the discharged state, and must have a path for the insertion and removal of lithium.
[0115] In order to ensure sufficient paths for lithium insertion and desorption, it is preferable that the surface layer 100a has a higher cobalt concentration than magnesium. For example, when measured from the surface of the positive electrode active material particle 100 by XPS, the ratio Mg / Co of the number of magnesium atoms Mg to the number of cobalt atoms Co is preferably 0.62 or less. It is also preferable that the surface layer 100a has a higher cobalt concentration than nickel. It is also preferable that the surface layer 100a has a higher cobalt concentration than aluminum. It is also preferable that the surface layer 100a has a higher cobalt concentration than fluorine.
[0116] Furthermore, since too much nickel may hinder the diffusion of lithium, it is preferable that the surface layer portion 100a has a higher concentration of magnesium than nickel. For example, when measured from the surface of the positive electrode active material particle 100 by XPS, the number of nickel atoms is preferably 1 / 6 or less of the number of magnesium atoms.
[0117] In addition, it is preferable that some of the added elements, particularly magnesium, nickel and aluminum, have a higher concentration in the surface layer 100a than in the interior 100b, but it is also preferable that they are present randomly and dilutely in the interior 100b. When magnesium and aluminum are present at an appropriate concentration in the lithium site of the interior 100b, it has the effect of making it easier to maintain the layered rock-salt crystal structure as described above. When nickel is present at an appropriate concentration in the interior 100b, it is possible to suppress the deviation of the layered structure consisting of octahedra of cobalt and oxygen as described above. When magnesium and nickel are present together, a synergistic effect of suppressing the elution of magnesium can be expected as described above.
[0118] It is preferable that the crystal structure changes continuously from the inside 100b toward the surface due to the concentration gradient of the added element as described above, or that the crystal orientation of the surface layer portion 100a and the inside 100b is approximately the same.
[0119] For example, it is preferable that the crystal structure changes continuously from the inside 100b of the layered rock salt type toward the surface and surface layer portion 100a having characteristics of the rock salt type or both the rock salt type and the layered rock salt type. It is also preferable that the crystal orientation of the surface layer portion 100a having characteristics of the rock salt type or both the rock salt type and the layered rock salt type and the inside 100b of the layered rock salt type are approximately the same.
[0120] In this specification, the layered rock-salt type crystal structure belonging to the space group R-3m, which is possessed by a composite oxide containing lithium and a transition metal such as cobalt, refers to a crystal structure having a rock-salt type ion arrangement in which cations and anions are alternately arranged, and in which the transition metal and lithium are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. Defects such as deficiencies of cations or anions may be present. Strictly speaking, the layered rock-salt type crystal structure may have a structure in which the lattice of the rock-salt type crystal is distorted.
[0121] The rock-salt crystal structure is a cubic crystal structure, such as that of the space group Fm-3m, in which cations and anions are arranged alternately. Note that cations or anions may be missing.
[0122] Moreover, the fact that it has both the characteristics of the layered rock salt type and the rock salt type crystal structure can be determined by electron diffraction, TEM images, cross-sectional STEM images, etc.
[0123] In the rock salt type, there is no distinction in the cation sites, but in the layered rock salt type, there are two types of cation sites in the crystal structure, one of which is mostly occupied by lithium and the other by a transition metal. The layered structure in which two-dimensional planes of cations and two-dimensional planes of anions are alternately arranged is the same for both the rock salt type and the layered rock salt type. Among the bright spots in the electron diffraction pattern corresponding to the crystal planes that form this two-dimensional plane, when the central spot (transmitted spot) is set as the origin 000, the bright spot closest to the central spot is, for example, the (111) plane in the ideal rock salt type, and, for example, the (003) plane in the layered rock salt type. For example, when comparing the electron diffraction patterns of rock salt type MgO and layered rock salt type LiCoO2, the distance between the bright spots on the (003) plane of LiCoO2 is observed to be about half the distance between the bright spots on the (111) plane of MgO. Therefore, if the analysis area contains two phases, for example, rock-salt MgO and layered rock-salt LiCoO2, the electron diffraction pattern will have a plane orientation in which bright spots of high brightness and bright spots of low brightness are arranged alternately. Bright spots common to both the rock-salt and layered rock-salt types will have high brightness, while bright spots occurring only in the layered rock-salt type will have low brightness.
[0124] Furthermore, when a layered rock-salt crystal structure is observed from a direction perpendicular to the c-axis in cross-sectional STEM images, layers observed with strong brightness and layers observed with weak brightness are observed alternating. This characteristic is not seen in the rock-salt type, as there is no distinction in the cation sites. In the case of a crystal structure that has characteristics of both the rock-salt type and the layered rock-salt type, when observed from a specific crystal orientation, layers observed with strong brightness and layers observed with weak brightness are observed alternating in cross-sectional STEM images, and furthermore, a metal with an atomic number higher than that of lithium is present in part of the weak brightness layer, i.e., the lithium layer.
[0125] Layered rock-salt crystals and the anions of rock-salt crystals have a cubic close-packed structure (face-centered cubic lattice structure). It is presumed that the anions of the O3' type and monoclinic O1(15) crystals described below also have a cubic close-packed structure. Therefore, when a layered rock-salt crystal and a rock-salt crystal come into contact, there are crystal faces where the cubic close-packed structure composed of anions is aligned.
[0126] Alternatively, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock-salt type has a space group of R-3m and a rhombohedral structure, but to make the structure easier to understand, it is generally represented as a compound hexagonal lattice, and the (0001) plane of the layered rock-salt type has a hexagonal lattice. The triangular lattice of the cubic {111} plane has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock-salt type. When the two lattices are compatible, it can be said that the orientation of the cubic close-packed structure is aligned.
[0127] However, the space group of the layered rock salt crystal and O3' type crystal is R-3m, which is different from the space group Fm-3m (the space group of general rock salt crystals) of the rock salt crystal, so the Miller indices of the crystal planes that satisfy the above conditions are different between the layered rock salt crystal and O3' type crystal and the rock salt crystal. In this specification, when the orientation of the cubic close-packed structure formed by anions in the layered rock salt crystal, O3' type and rock salt crystal is aligned, it may be said that the crystal orientation is approximately the same. In addition, the three-dimensional structural similarity in which the crystal orientation is approximately the same, or the same crystallographic orientation, is called topotaxis.
[0128] The fact that the crystal orientations of the two regions roughly match can be determined from TEM images, STEM images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM) images, ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope) images, electron diffraction patterns, etc. It can also be determined from FFT patterns of TEM images and FFT patterns of STEM images, etc. XRD, neutron diffraction, etc. can also be used as materials for determination.
[0129] An example of a TEM image in which the orientation of the layered rock-salt crystal LRS and the rock-salt crystal RS roughly coincides is shown in Figure 3. Images reflecting the crystal structure can be obtained in TEM, STEM, HAADF-STEM, ABF-STEM, and other images.
[0130] For example, in high-resolution TEM images, contrast originating from crystal planes is observed. When an electron beam is incident perpendicular to the c-axis of a layered rock-salt type composite hexagonal lattice, for example, the contrast originating from the (0003) plane is observed as a repetition of bright and dark bands (bright strips) due to the diffraction and interference of the electron beam. Therefore, a repetition of bright and dark lines is observed in the TEM image, and the bright lines (for example, the L shown in Figure 3) are not clearly distinguishable from each other. RS and L LRS ) is 5 degrees or less, or 2.5 degrees or less, it can be determined that the crystal planes are roughly aligned, that is, that the crystal orientations are roughly aligned. Similarly, when the angle between the dark lines is 5 degrees or less, or 2.5 degrees or less, it can be determined that the crystal orientations are roughly aligned.
[0131] In addition, in HAADF-STEM images, contrast proportional to the atomic number is obtained, and elements with higher atomic numbers are observed brighter. For example, in the case of layered rock-salt lithium cobalt oxide belonging to the space group R-3m, cobalt (atomic number 27) has the highest atomic number, so the electron beam is strongly scattered at the position of the cobalt atom, and the arrangement of the cobalt atoms is observed as a bright line or an arrangement of strongly bright dots. Therefore, when lithium cobalt oxide with a layered rock-salt crystal structure is observed perpendicular to the c-axis, the arrangement of the cobalt atoms is observed as a bright line or an arrangement of strongly bright dots perpendicular to the c-axis, and the arrangements of the lithium atoms and oxygen atoms are observed as dark lines or low-brightness areas. The same is true when lithium cobalt oxide has fluorine (atomic number 9) and magnesium (atomic number 12) as added elements.
[0132] Therefore, when bright and dark lines are repeatedly observed in two regions with different crystal structures in a HAADF-STEM image and the angle between the bright lines is 5 degrees or less or 2.5 degrees or less, it can be determined that the atomic arrangements are roughly the same, that is, the crystal orientations are roughly the same. Similarly, when the angle between the dark lines is 5 degrees or less or 2.5 degrees or less, it can also be determined that the crystal orientations are roughly the same.
[0133] In ABF-STEM, elements with smaller atomic numbers appear brighter; however, like HAADF-STEM, it is possible to obtain contrast according to the atomic number, and therefore it is possible to determine the crystal orientation in the same way as with HAADF-STEM images.
[0134] Figure 4(A) shows an example of a STEM image in which the orientations of the layered rock-salt crystal LRS and the rock-salt crystal RS roughly coincide. Figure 4(B) shows the FFT pattern of the region of the rock-salt crystal RS, and Figure 4(C) shows the FFT pattern of the region of the layered rock-salt crystal LRS. The left side of Figure 4(B) and Figure 4(C) show the composition, JCPDS card number, and the d value and angle calculated from the JCPDS card number. The right side shows the measured values. The spot marked with O is the zeroth order diffraction.
[0135] The spot marked A in Figure 4(B) is due to the 11-1 reflection of the cubic crystal. The spot marked A in Figure 4(C) is due to the 0003 reflection of the layered rock salt type. From Figures 4(B) and 4(C), it can be seen that the orientation of the 11-1 reflection of the cubic crystal and the orientation of the 0003 reflection of the layered rock salt type are roughly aligned. In other words, it can be seen that the line passing through AO in Figure 4(B) is roughly parallel to the line passing through AO in Figure 4(C). Here, roughly aligned and roughly parallel means that the angle is 5 degrees or less, or 2.5 degrees or less.
[0136] In this way, in the FFT pattern and the electron diffraction pattern, when the orientation of the layered rock salt type crystal and the rock salt type crystal roughly coincides, the <0003> orientation of the layered rock salt type and the <11-1> orientation of the rock salt type may roughly coincide. In this case, it is preferable that these reciprocal lattice points are spot-like, that is, not continuous with other reciprocal lattice points. The fact that the reciprocal lattice points are spot-like and not continuous with other reciprocal lattice points means that the crystallinity is high.
[0137] In addition, when the orientation of the 11-1 reflection of the cubic crystal and the orientation of the 0003 reflection of the layered rock salt type are roughly the same as described above, depending on the incidence orientation of the electron beam, a spot not derived from the 0003 reflection of the layered rock salt type may be observed in a reciprocal lattice space different from the orientation of the 0003 reflection of the layered rock salt type. For example, the spot marked B in FIG. 4(C) is derived from the 1014 reflection of the layered rock salt type. This may be observed at an angle of 52° to 56° (i.e., ∠AOB is 52° to 56°) from the orientation of the reciprocal lattice point derived from the 0003 reflection of the layered rock salt type (A in FIG. 4(C)), and at a position where d is 0.19 nm to 0.21 nm. Note that this index is an example, and does not necessarily have to be the same. For example, a reciprocal lattice point equivalent to 0003 and 1014 may be used.
[0138] Similarly, a spot not originating from the 11-1 reflection of a cubic crystal may be observed in a reciprocal lattice space other than the orientation where the 11-1 reflection of a cubic crystal is observed. For example, the spot marked B in Figure 4(B) is originating from the 200 reflection of a cubic crystal. This is a diffraction spot observed at an angle of 54° to 56° (i.e., ∠AOB is 54° to 56°) from the orientation of the reflection originating from the 11-1 of a cubic crystal (A in Figure 4(B)). Note that this index is only an example, and does not necessarily have to be the same. For example, a reciprocal lattice point equivalent to 11-1 and 200 of a cubic crystal may be used.
[0139] It is known that the layered rock salt type positive electrode active material, including lithium cobalt oxide, is likely to have the (0003) plane and its equivalent plane, as well as the (10-14) plane and its equivalent plane as crystal planes. Therefore, for example, when observing the (0003) plane with a TEM or the like, first select a particle of the positive electrode active material in which the shape of the positive electrode active material is observed with a scanning electron microscope (SEM) or the like, and then, for example, the particle of the positive electrode active material may be processed into a thin slice with a FIB (Focused Ion Beam) or the like so that the (0003) plane can be observed with an electron beam incident at [12-10] in the TEM or the like. When it is desired to determine the coincidence of the crystal orientation, it is preferable to slice the layered rock salt type so that the (0003) plane can be easily observed.
[0140] <Crystal structure> <Li x When x in CoO2 is 1≫ The positive electrode active material particle 100 according to one embodiment of the present invention is in a discharged state, i.e., Li x When x=1 in CoO2, it has a layered rock-salt type crystal structure belonging to the space group R-3m. Layered rock-salt type composite oxides have a high discharge capacity, have two-dimensional lithium ion diffusion paths, and are suitable for lithium ion insertion / extraction reactions, making them excellent as positive electrode active materials for secondary batteries. Therefore, it is particularly preferable that the inner part 100b, which occupies most of the volume of the positive electrode active material particle 100, has a layered rock-salt type crystal structure. The layered rock-salt type crystal structure is shown in FIG. 5 with R-3m O3 attached. R-3m O3 has lattice constants a = 2.81610, b = 2.81610, c = 14.05360, α = 90.0000, β = 90.0000, γ = 120.0000, and the coordinates of lithium, cobalt, and oxygen in the unit cell are Li(0, 0, 0), Co(0, 0, 0.5), and O(0, 0, 0.23951) (Non-Patent Document 5).
[0141] On the other hand, the surface layer portion 100a of the positive electrode active material particle 100 according to one embodiment of the present invention preferably has a function of reinforcing the layered structure of the transition metal M and oxygen octahedrons in the interior portion 100b so that it is not broken even if lithium is removed from the positive electrode active material particle 100 by charging. Alternatively, the surface layer portion 100a preferably functions as a barrier film for the positive electrode active material particle 100. Alternatively, the surface layer portion 100a, which is the outer periphery of the positive electrode active material particle 100, preferably reinforces the positive electrode active material particle 100. The reinforcement referred to here means suppressing structural changes in the surface layer portion 100a and interior portion 100b of the positive electrode active material particle 100, such as oxygen elimination and / or deviation of the layered structure of the transition metal M and oxygen octahedrons. And / or means suppressing oxidative decomposition of the electrolyte on the surface of the positive electrode active material particle 100.
[0142] Therefore, it is preferable that the surface layer portion 100a has a different crystal structure from the inner portion 100b. It is also preferable that the surface layer portion 100a has a composition and a crystal structure that are more stable at room temperature (25° C.) than the inner portion 100b. For example, it is preferable that at least a part of the surface layer portion 100a of the positive electrode active material particle 100 of one embodiment of the present invention has a rock salt type crystal structure. Alternatively, it is preferable that the surface layer portion 100a has both a layered rock salt type crystal structure and a rock salt type crystal structure. Alternatively, it is preferable that the surface layer portion 100a has characteristics of both a layered rock salt type crystal structure and a rock salt type crystal structure.
[0143] The surface layer 100a is the region from which lithium ions are first released during charging, and is the region where the lithium concentration is likely to be lower than that of the interior 100b. The atoms on the surface of the particle of the positive electrode active material particle 100 that are in the surface layer 100a can be said to be in a state where some of the bonds are broken. Therefore, the surface layer 100a is likely to become unstable, and is the region where deterioration of the crystal structure is likely to begin. For example, if the crystal structure of the layered structure consisting of the transition metal M and oxygen octahedrons in the surface layer 100a is displaced, the effect will be linked to the interior 100b, causing the layered crystal structure in the interior 100b to also be displaced, leading to deterioration of the crystal structure of the entire positive electrode active material particle 100. On the other hand, if the surface layer 100a can be sufficiently stabilized, Li xEven when x in CoO2 is small, for example, when x is 0.24 or less, the layered structure of the inner 100b composed of the transition metal M and oxygen octahedra can be made less likely to break. Furthermore, the displacement of the layer composed of the transition metal M and oxygen octahedra in the inner 100b can be suppressed.
[0144] Furthermore, the interior 100b of the positive electrode active material particle 100 preferably has a low density of defects including dislocations. Furthermore, the positive electrode active material particle 100 preferably has a large crystallite size measured by XRD. In other words, the interior 100b preferably has high crystallinity. Furthermore, the surface of the positive electrode active material particle 100 preferably is smooth. These characteristics are important factors supporting the reliability of the positive electrode active material particle 100 when used in a secondary battery. If the reliability of the positive electrode active material is high, the upper limit of the charging voltage of the secondary battery can be increased, and a secondary battery with a high charge / discharge capacity can be obtained.
[0145] Dislocations in the interior 100b can be observed, for example, by TEM. If the density of defects including dislocations is sufficiently low, they may not be observed in a specific 1 μm square of the observation sample. Note that dislocations are a type of crystal defect and are different from vacancy defects.
[0146] The larger the crystallite size, the greater the Li x When x in CoO2 is small, the O3' type crystal structure is easily maintained, and the contraction of the c-axis length is easily suppressed.
[0147] It is believed that the fewer defects, including dislocations, observed by TEM, the larger the crystallite size as measured by XRD.
[0148] The XRD diffraction pattern for calculating the crystallite size is preferably obtained from the positive electrode active material alone, but may be obtained from the positive electrode including the current collector, binder, conductive material, etc. in addition to the positive electrode active material. However, in the positive electrode state, the positive electrode active material may be oriented due to the influence of pressure during the manufacturing process. If the orientation is too strong, the crystallite size may not be calculated accurately, so it is more preferable to obtain the pattern by removing the positive electrode active material layer from the positive electrode, removing the binder, etc. in the positive electrode active material layer to a certain extent using a solvent, etc., and then filling the sample holder. Another method is to apply grease to a powder sample on a silicon non-reflective plate and attach the sample to it.
[0149] The crystallite size can be calculated using, for example, a Bruker D8 ADVANCE, a CuKα1 ray source, 2θ between 15° and 90°, increment 0.005, and a LYNXEYE XE-T detector, using a diffraction pattern acquired with ICSD coll.code.172909 as the literature value for lithium cobalt oxide. Analysis can be performed using DIFFRAC.TOPAS ver.6 as crystal structure analysis software, and can be set, for example, as follows. Emission Profile: CuKa5.lam Background:Chebychev polynomial, 5th order Instrument Primary radius: 280mm Secondary radius:280mm Linear PSD 2Th angular range:2.9 FDS angle: 0.3 Full Axial Convolution Filament length: 12mm Sample length: 15mm Receiving Slit Length: 12mm Primary Sollers: 2.5 Secondary Sollers: 2.5 Corrections Specimen displacement:Refine LP Factor:0
[0150] It is preferable to adopt the LVol-IB value, which is the crystallite size corrected by the integral width standard calculated by the above method, as the crystallite size. Note that if the calculated Preferred Orientation is less than 0.8, the orientation of the sample may be too strong and it may not be suitable for determining the crystallite size.
[0151] <Li x CoO2 with small x≫ The positive electrode active material particle 100 according to one embodiment of the present invention has the above-described distribution of the additive element and / or crystal structure in a discharged state, and thus has a high degree of conductivity. x The crystal structure when x in CoO2 is small is different from that of conventional positive electrode active materials. <x≦0.24をいうこととする。
[0152] Using Figs. 5 to 9, Li x The change in crystal structure accompanying the change in x in CoO2 will be described while comparing a conventional positive electrode active material with the positive electrode active material particle 100 according to one embodiment of the present invention.
[0153] The change in the crystal structure of a conventional positive electrode active material is shown in Figure 6. The conventional positive electrode active material shown in Figure 6 is lithium cobalt oxide (LiCoO2) that does not have any added elements. The change in the crystal structure of lithium cobalt oxide that does not have any added elements is described in Non-Patent Documents 1 to 3, etc.
[0154] Figure 6 shows R-3m O3 and Li xThe crystal structure of lithium cobalt oxide with x=1 in CoO2 is shown. In this crystal structure, lithium occupies the octahedral site, and there are three CoO2 layers in the unit cell. For this reason, this crystal structure is sometimes called an O3 type crystal structure. Note that a CoO2 layer is an octahedral structure in which cobalt is coordinated with six oxygen atoms, and the edges are shared to form a continuous plane. This is sometimes called a layer made of octahedra of cobalt and oxygen.
[0155] Conventional lithium cobalt oxide is known to have a crystal structure that belongs to the monoclinic space group P2 / m when the lithium ions are aligned and the symmetry is increased when x is about 0.5. This structure has one CoO2 layer in the unit cell. Therefore, it is sometimes called O1 type, or monoclinic O1 type.
[0156] When x=0, the positive electrode active material has a trigonal space group P-3m1 crystal structure, and there is also one CoO2 layer in the unit cell. Therefore, this crystal structure is sometimes called O1 type, or trigonal O1 type. In addition, the trigonal structure may be converted to a composite hexagonal lattice and called hexagonal O1 type.
[0157] Furthermore, when x=0.12, conventional lithium cobalt oxide has a crystal structure of space group R-3m. This structure can be said to be a structure in which a trigonal O1-type CoO2 structure and an R-3m O3-type LiCoO2 structure are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3-type crystal structure. Note that the actual insertion and desorption of lithium does not necessarily occur uniformly in the positive electrode active material, and the lithium concentration may become spotty, so experimentally, an H1-3-type crystal structure is observed from about x=0.25. In fact, the number of cobalt atoms per unit cell in the H1-3-type crystal structure is twice that of other structures. However, in FIG. 6 and other parts of this specification, in order to make it easier to compare with other crystal structures, the c-axis of the H1-3-type crystal structure is shown as 1 / 2 of the unit cell.
[0158] As an example of the H1-3 type crystal structure, as described in Non-Patent Document 3, the coordinates of cobalt and oxygen in the unit cell can be expressed as Co (0,0,0.42150±0.00016), O1 (0,0,0.27671±0.00045), and O2 (0,0,0.11535±0.00045). O1 and O2 are oxygen atoms. Which unit cell should be used to express the crystal structure of the positive electrode active material can be determined, for example, by Rietveld analysis of the XRD pattern. In this case, it is sufficient to adopt a unit cell with a small GOF (goodness of fit) value.
[0159] Li x When the battery is repeatedly charged and discharged such that x in CoO2 becomes 0.24 or less, conventional lithium cobalt oxide repeatedly undergoes a change in crystal structure (i.e., a non-equilibrium phase change) between the H1-3 type crystal structure and the R-3m O3 structure in the discharged state.
[0160] However, these two crystal structures have a large misalignment of the CoO2 layer. As shown by the dotted line and arrow in Figure 6, in the H1-3 type crystal structure, the CoO2 layer is significantly misaligned from that of R-3m O3 in the discharged state. Such dynamic structural changes can have a negative effect on the stability of the crystal structure.
[0161] Furthermore, there is a large difference in volume between these two crystal structures. The specific volume difference will be described later.
[0162] In addition, the H1-3 crystal structure, which has continuous CoO2 layers like the trigonal O1 type, is likely to be unstable.
[0163] Therefore, when charging and discharging are repeated so that x is 0.24 or less, the crystal structure of conventional lithium cobalt oxide collapses. The collapse of the crystal structure causes a deterioration in cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably and makes it difficult to insert and remove lithium.
[0164] On the other hand, in the positive electrode active material particle 100 according to one embodiment of the present invention shown in FIG. x The change in the crystal structure between the discharged state where x in CoO2 is 1 and the state where x is 0.24 or less is smaller than that of conventional positive electrode active materials. More specifically, the deviation of the MO2 layer between the state where x is 1 and the state where x is 0.24 or less can be reduced. Also, the change in volume compared per cobalt atom can be reduced. Therefore, the positive electrode active material particle 100 of one embodiment of the present invention is unlikely to collapse in crystal structure even when charging and discharging in such a way that x is 0.24 or less are repeated, and excellent cycle characteristics can be achieved. In addition ... x When x in CoO2 is 0.24 or less, the positive electrode active material can have a more stable crystal structure than conventional positive electrode active materials. x When the state where x in CoO2 is kept at 0.24 or less is maintained, short circuits are unlikely to occur. In such a case, the safety of the secondary battery is further improved, which is preferable.
[0165] Li x 5 shows the crystal structures of the interior 100b of the positive electrode active material particle 100 when x in CoO2 is 1, approximately 0.2, and approximately 0.15. The interior 100b occupies the majority of the volume of the positive electrode active material particle 100 and is the part that contributes greatly to charge and discharge, so it can be said that the shift of the MO2 layer and the change in volume are the most problematic parts.
[0166] When x=1, the positive electrode active material particle 100 has the same crystal structure of R-3m O3 as conventional lithium cobalt oxide.
[0167] However, the positive electrode active material particles 100 have a crystal structure different from that of conventional lithium cobalt oxide when x is 0.24 or less, for example, about 0.2 or about 0.15, in which case the lithium cobalt oxide has an H1-3 type crystal structure.
[0168] The positive electrode active material particle 100 according to one embodiment of the present invention when x=0.2 has a crystal structure belonging to the trigonal space group R-3m. The symmetry of the CoO2 layer is the same as that of O3. Therefore, this crystal structure is called an O3' type crystal structure. This crystal structure is shown in FIG. 5 with R-3m O3'.
[0169] The O3' type crystal structure can show the coordinates of cobalt and oxygen in the unit cell within the range of Co(0,0,0.5), O(0,0,x), 0.20≦x≦0.25. The lattice constant of the unit cell is preferably 2.797≦a≦2.837(Å), more preferably 2.807≦a≦2.827(Å), typically a=2.817(Å). The c-axis is preferably 13.681≦c≦13.881(Å), more preferably 13.751≦c≦13.811(Å), typically c=13.781(Å).
[0170] In addition, when x=0.15, the positive electrode active material particle 100 according to one embodiment of the present invention may have a crystal structure belonging to the monoclinic space group P2 / m. In this case, one CoO2 layer exists in the unit cell. In addition, the amount of lithium present in the positive electrode active material particle 100 at this time is about 15 atomic % in the discharged state. Therefore, this crystal structure is called a monoclinic O1(15) type crystal structure. This crystal structure is shown in FIG. 5 with the P2 / m monoclinic O1(15) attached.
[0171] The monoclinic O1(15) crystal structure has the coordinates of cobalt and oxygen in the unit cell as follows: Co1(0.5,0,0.5), Co2(0,0.5,0.5), O1(X O1 ,0,Z O1 ), 0.23≦X O1 ≦0.24, 0.61≦Z O1 ≦0.65, O2(X O2 ,0.5,Z O2 ), 0.75≦X O2 ≦0.78, 0.68≦Z O2The lattice constant of the unit cell is in the range of ≦0.71. a = 4.880 ± 0.05 Å, b = 2.817 ± 0.05 Å, c = 4.839 ± 0.05 Å, α=90°, β=109.6±0.1°, γ=90°.
[0172] It is possible to show the lattice constants of this crystal structure in the space group R-3m if a certain degree of error is allowed. In this case, the coordinates of cobalt and oxygen in the unit cell are Co(0,0,0.5), O(0,0,Z O ), 0.21≦Z O ≦0.23. The lattice constant of the unit cell is a = 2.817 ± 0.02 Å, c=13.68±0.1 Å.
[0173] In both the O3' and monoclinic O1(15) crystal structures, ions of cobalt, nickel, magnesium, etc. occupy 6-coordinate oxygen sites, although lighter elements such as lithium and magnesium may occupy 4-coordinate oxygen sites.
[0174] As shown by the dotted line in FIG. 5, there is almost no deviation in the CoO2 layer between R-3m O3 in the discharged state and O3' and the monoclinic O1(15) type crystal structure.
[0175] Table 1 shows the difference in volume per cobalt atom between R-3m O3 in a discharged state, O3', monoclinic O1(15), H1-3 type, and trigonal O1. For the lattice constants of each crystal structure used in the calculation of Table 1, literature values can be referred to for R-3m O3 and trigonal O1 in a discharged state (ICSD coll.code.172909 and 88721). For H1-3, Non-Patent Document 3 can be referred to. For O3' and monoclinic O1(15), they can be calculated from experimental values of XRD.
[0176] [Table 1]
[0177] Using the volume per cobalt in the above table, the difference in volume between the H1-3 crystal structure and the R-3m O3 crystal structure in a discharged state can be calculated when comparing the same number of cobalt atoms. As shown in the volume change rate (%) in the above table, when the denominator is the R-3m O3 crystal structure in a discharged state, the difference in volume is 3.9%. In other words, the difference in volume exceeds 3.5%, and is extremely large.
[0178] Using the volume per cobalt in the above table, the difference in volume between R-3m O3 in a discharged state and the O3' type crystal structure can be calculated when comparing per the same number of cobalt atoms. As shown in the volume change rate (%) in the above table, when the denominator is the R-3m O3 type crystal structure in a discharged state, the difference in volume is 1.8%. In other words, the difference in volume is less than 2.5%, more specifically less than 2.2%, which is very small.
[0179] Using the volume per cobalt in the above table, the difference in volume between R-3m O3 in a discharged state and the monoclinic O1(15) crystal structure can be calculated when comparing the same number of cobalt atoms. As shown in the volume change rate (%) in the above table, when the denominator is the R-3m O3 crystal structure in a discharged state, the difference in volume is 2.5%. In other words, the difference in volume is less than 3.3%, more specifically less than 3.0%, which is very small.
[0180] In this way, in the positive electrode active material particle 100 according to one embodiment of the present invention, Li xWhen x in CoO2 is small, that is, when a large amount of lithium is released, the change in the crystal structure is suppressed more than in conventional positive electrode active materials. In addition, the change in volume is also suppressed when compared per the same number of cobalt atoms. Therefore, the crystal structure of the positive electrode active material particles 100 is not easily broken even when charging and discharging are repeated so that x is 0.24 or less. Therefore, the positive electrode active material particles 100 are suppressed from decreasing in charge and discharge capacity during charge and discharge cycles. In addition, since more lithium can be stably used than in conventional positive electrode active materials, the positive electrode active material particles 100 have a large discharge capacity per weight and per volume. Therefore, by using the positive electrode active material particles 100, a secondary battery with a high discharge capacity per weight and per volume can be manufactured.
[0181] The positive electrode active material particles 100 are Li x It has been confirmed that when x in CoO2 is 0.15 or more and 0.24 or less, it may have an O3' type crystal structure, and it is presumed that even when x is more than 0.24 and 0.27 or less, it has an O3' type crystal structure. x It has been confirmed that when x in CoO2 is greater than 0.1 and less than 0.2, typically between 0.15 and 0.17, it may have a monoclinic O1(15) type crystal structure. However, the crystal structure is Li x Since it is affected by not only x in CoO2 but also the number of charge / discharge cycles, charge / discharge current, temperature, electrolyte, etc., it is not necessarily limited to the above range of x.
[0182] Therefore, the positive electrode active material particles 100 are Li x When x in CoO2 is more than 0.1 and not more than 0.24, it may have only O3' type, may have only monoclinic O1(15) type, or may have both crystal structures. All particles in the interior 100b of the positive electrode active material particle 100 do not have to have O3' type and / or monoclinic O1(15) type crystal structures. It may contain other crystal structures, or may be partially amorphous.
[0183] Also Li x To make the x in CoO2 small, it is generally necessary to charge at a high charging voltage.x The state where x in CoO2 is small can be said to be a state where the battery is charged at a high charging voltage. For example, when the battery is charged at a constant current and constant voltage (CC / CV) at a voltage of 4.6 V or more based on the potential of lithium metal in a 25°C environment, the H1-3 type crystal structure appears in the conventional positive electrode active material. Therefore, a charging voltage of 4.6 V or more based on the potential of lithium metal can be said to be a high charging voltage. In this specification and the like, unless otherwise specified, the charging voltage is expressed based on the potential of lithium metal.
[0184] Therefore, in other words, the positive electrode active material particle 100 of one embodiment of the present invention is preferable because it can maintain a crystal structure having the symmetry of R-3m O3 even when charged at a high charging voltage, for example, a voltage of 4.6 V or more at 25°C.
[0185] Even with the positive electrode active material particle 100, when the charging voltage is further increased, the H1-3 type crystal structure may finally be observed. As described above, the crystal structure is affected by the number of charge / discharge cycles, the charge / discharge current, the temperature, the electrolyte, and the like, so that when the charging voltage is lower, for example, even when the charging voltage is 4.5 V or more and less than 4.6 V at 25° C., the positive electrode active material particle 100 of one embodiment of the present invention may be able to have the O3' type crystal structure. Similarly, when charging at a voltage of 4.65 V or more and 4.7 V or less at 25° C., the positive electrode active material particle 100 may be able to have the monoclinic O1(15) type crystal structure.
[0186] In addition, when graphite is used as the negative electrode active material in the secondary battery, the voltage of the secondary battery is lower than the above by the potential of the graphite. The potential of graphite is about 0.05 V to 0.2 V based on the potential of lithium metal. Therefore, in the case of a secondary battery using graphite as the negative electrode active material, the battery has the same crystal structure at a voltage obtained by subtracting the potential of graphite from the above voltage.
[0187] In addition, in the O3' and monoclinic O1(15) of FIG. 5, lithium is shown to exist at all lithium sites with equal probability, but this is not limited to this. It may exist biasedly at some lithium sites, for example, in the monoclinic O1(Li0.5 The lithium distribution can be analyzed, for example, by neutron diffraction.
[0188] It can also be said that the O3' and monoclinic O1(15) types have random lithium between the layers, but are similar to the CdCl2 type crystal structure. 0.06 Although the crystal structure is close to that when charged to NiO2, it is known that pure lithium cobalt oxide or layered rock salt type positive electrode active materials containing a large amount of cobalt do not usually adopt a CdCl2 type crystal structure.
[0189] <Grain Boundaries> It is more preferable that the additive element contained in the positive electrode active material particle 100 of one embodiment of the present invention is distributed as described above, and at least a part of the additive element is unevenly distributed in and near the crystal grain boundaries.
[0190] In this specification and the like, uneven distribution refers to the concentration of an element in a certain region being different from that in other regions, and is synonymous with segregation, precipitation, non-uniformity, bias, or the presence of a mixture of areas with high concentration and areas with low concentration.
[0191] For example, it is preferable that the magnesium concentration at and near the grain boundaries of the positive electrode active material particle 100 is higher than that in other regions of the interior 100b. It is also preferable that the fluorine concentration at and near the grain boundaries is higher than that in other regions of the interior 100b. It is also preferable that the nickel concentration at and near the grain boundaries is higher than that in other regions of the interior 100b. It is also preferable that the aluminum concentration at and near the grain boundaries is higher than that in other regions of the interior 100b.
[0192] Grain boundaries are one type of planar defect. Therefore, like the particle surface, they are prone to become unstable and changes in the crystal structure are likely to occur. Therefore, if the concentration of added elements at and near the grain boundaries is high, changes in the crystal structure can be more effectively suppressed.
[0193] In addition, when the magnesium concentration and fluorine concentration are high at and near the grain boundary, even if cracks occur along the grain boundary of the positive electrode active material particle 100 of one embodiment of the present invention, the magnesium concentration and fluorine concentration are high near the surface caused by the cracks. Therefore, even in the positive electrode active material after the cracks occur, the corrosion resistance against hydrofluoric acid can be improved. In addition, even in the positive electrode active material after the cracks occur, the side reaction between the electrolyte and the positive electrode active material can be suppressed.
[0194] <Particle size> If the particle size of the positive electrode active material particle 100 of one embodiment of the present invention is too large, problems arise such as difficulty in diffusing lithium, and the surface of the active material layer becomes too rough when applied to a current collector, etc. On the other hand, if the particle size is too small, problems arise such as excessive reaction with the electrolyte.
[0195] The particle size of the positive electrode active material particles 100 can be measured, for example, by a laser diffraction type particle size distribution measuring device. The particle size of the positive electrode active material particles 100 measured by the laser diffraction type particle size distribution measuring device is preferably a median diameter (D50) of 1 μm or more and 100 μm or less, more preferably 2 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less. Alternatively, 1 μm or more and 40 μm or less is preferable. Alternatively, 1 μm or more and 30 μm or less is preferable. Alternatively, 2 μm or more and 100 μm or less is preferable. Alternatively, 2 μm or more and 30 μm or less is preferable. Alternatively, 5 μm or more and 100 μm or less is preferable. Alternatively, 5 μm or more and 40 μm or less is preferable.
[0196] The median diameter (D50) is the particle diameter when the cumulative amount in the cumulative curve of the particle size distribution measurement result is 50%. The particle diameter when the cumulative amount in the cumulative curve of the particle size distribution measurement result is 10% is called the median diameter (D10), and the particle diameter when the cumulative amount in the cumulative curve of the particle size distribution measurement result is 90% is called the median diameter (D90).
[0197] In addition, when particles having different particle sizes are mixed and used in the positive electrode, the electrode density can be increased, and a secondary battery with high energy density can be obtained, which is preferable. The positive electrode active material particles 100 having a relatively small particle size are expected to have high charge / discharge rate characteristics. The positive electrode active material particles 100 having a relatively large particle size are expected to have high charge / discharge cycle characteristics and to maintain a high discharge capacity.
[0198] <Analysis method> A certain positive electrode active material is Li x When x in CoO2 is small, whether or not the positive electrode active material particle 100 according to one embodiment of the present invention has an O3′ type and / or monoclinic O1(15) type crystal structure is determined by Li x This can be determined by analyzing a positive electrode having a positive electrode active material with a small x in CoO2 using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc.
[0199] In particular, XRD is preferred in that it can analyze the symmetry of transition metals such as cobalt contained in the positive electrode active material with high resolution, it can compare the degree of crystallinity and the orientation of the crystals, it can analyze the periodic distortion of the lattice and the crystallite size, it can obtain sufficient accuracy even when the positive electrode obtained by disassembling the secondary battery is measured as it is, etc. Among XRD, powder XRD can obtain diffraction peaks that reflect the crystal structure of the interior 100b of the positive electrode active material particle 100, which occupies most of the volume of the positive electrode active material particle 100.
[0200] When analyzing the crystallite size by powder XRD, it is preferable to perform the measurement while excluding the influence of orientation due to pressure, etc. For example, it is preferable to take out the positive electrode active material from the positive electrode obtained by disassembling a secondary battery, prepare a powder sample, and then perform the measurement.
[0201] As described above, the positive electrode active material particle 100 according to one embodiment of the present invention is xA characteristic of this material is that there is little change in the crystal structure when x in CoO2 is 1 and when it is 0.24 or less. Materials in which the crystal structure that undergoes large changes when charged at high voltage accounts for 50% or more of the total crystal structure are not desirable because they cannot withstand repeated high-voltage charging and discharging.
[0202] It should also be noted that the addition of an additive element alone may not result in an O3' or monoclinic O1(15) crystal structure. For example, even if lithium cobalt oxide with magnesium and fluorine or lithium cobalt oxide with magnesium and aluminum has something in common, depending on the concentration and distribution of the additive element, Li x In some cases, x in CoO2 is 0.24 or less and the O3' and / or monoclinic O1(15) crystal structures account for 60 wt% or more, and in other cases, the H1-3 crystal structure accounts for 50 wt% or more. The proportion of the crystal structures can be determined by Rietveld analysis.
[0203] Furthermore, even in the case of the positive electrode active material particle 100 of one embodiment of the present invention, an H1-3 type or trigonal O1 type crystal structure may be generated when x is too small, such as 0.1 or less, or under conditions where the charging voltage exceeds 4.9 V. Therefore, in order to determine whether or not the positive electrode active material particle 100 of one embodiment of the present invention is a particle, analysis of the crystal structure, such as XRD, and information on the charging capacity or charging voltage, etc. are required.
[0204] However, when the positive electrode active material has a small x, its crystal structure may change when it is exposed to air. For example, the crystal structure may change from O3' type or monoclinic O1(15) type to H1-3 type. Therefore, it is preferable to handle all samples used for crystal structure analysis in an inert atmosphere such as an argon atmosphere.
[0205] Furthermore, whether or not the distribution of the additive elements in a certain positive electrode active material is in the state described above can be determined by analysis using, for example, XPS, energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.
[0206] The crystal structure of the surface layer 100a, the grain boundaries, and the like can be analyzed by electron diffraction or the like of a cross section of the positive electrode active material particle 100.
[0207] ≪Charging method≫ Charging for determining whether a certain complex oxide is the positive electrode active material particle 100 of one embodiment of the present invention can be performed, for example, by preparing a coin cell (CR2032 type, diameter 20 mm, height 3.2 mm) with a lithium counter electrode and charging it.
[0208] More specifically, for the positive electrode, a slurry in which a positive electrode active material, a conductive material, and a binder are mixed is applied to a positive electrode current collector made of aluminum foil and used.
[0209] Lithium metal can be used for the counter electrode. When a material other than lithium metal is used for the counter electrode, the potential of the secondary battery is different from the potential of the positive electrode. Unless otherwise specified, the voltage and potential in this specification are the potential of the positive electrode.
[0210] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6), and the electrolytic solution can be a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of EC:DEC = 3:7, with 2 wt% vinylene carbonate (VC).
[0211] The separator can be a 25 μm thick porous polypropylene film.
[0212] The positive electrode can and the negative electrode can may be made of stainless steel (SUS).
[0213] The coin cell prepared under the above conditions is charged at an arbitrary voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V, or 4.8V). The charging method is not particularly limited as long as the charging can be performed at an arbitrary voltage for a sufficient time. For example, when charging by CCCV, the current in CC charging can be 20mA / g or more and 100mA / g or less. CV charging can be terminated at 2mA / g or more and 10mA / g or less. In order to observe the phase change of the positive electrode active material, it is desirable to charge at such a small current value. On the other hand, if the current does not become 2mA / g or more and 10mA / g or less even after CV charging for a long time, it is considered that the current is consumed not for charging the positive electrode active material but for decomposing the electrolyte, so CV charging may be terminated when a sufficient time has passed since the start. The sufficient time in this case can be, for example, 1.5 hours or more and 3 hours or less. The temperature is 25°C or 45°C. After charging in this manner, the coin cell is disassembled in a glove box in an argon atmosphere to remove the positive electrode, and a positive electrode active material with a desired charging capacity can be obtained. When various analyses are performed thereafter, it is preferable to seal the cell in an argon atmosphere in order to suppress reactions with external components. For example, XRD can be performed by sealing the cell in a sealed container in an argon atmosphere. In addition, it is preferable to quickly remove the positive electrode and subject it to analysis after charging is completed. Specifically, it is preferable to do so within 1 hour after charging is completed, and more preferably within 30 minutes.
[0214] In addition, when analyzing the crystal structure in the charged state after multiple charge / discharge cycles, the multiple charge / discharge conditions may be different from the above-mentioned charging conditions. For example, charging can be performed by constant current charging at a current value of 20 mA / g to 100 mA / g up to an arbitrary voltage (e.g., 4.6 V, 4.65 V, 4.7 V, 4.75 V, or 4.8 V), followed by constant voltage charging until the current value becomes 2 mA / g to 10 mA / g, and discharging by constant current discharging at 20 mA / g to 100 mA / g until the voltage becomes 2.5 V.
[0215] Furthermore, when analyzing the crystal structure in the discharged state after multiple charge / discharge cycles, constant current discharge can be performed at, for example, 2.5 V and a current value of 20 mA / g or more and 100 mA / g or less.
[0216] <XRD> The XRD measurement apparatus and conditions are not particularly limited. The software for analyzing the crystal structure is also not particularly limited. It is preferable to use a highly accurate apparatus, conditions, and corresponding software to perform more accurate crystal structure analysis. For example, the measurement and analysis can be performed using the following apparatus, conditions, and analysis software. XRD equipment: Bruker AXS, D8 ADVANCE X-ray source:CuKα1 ray Output: 40kV, 40mA Divergence angle: Div.Slit, 0.5° Detector: LynxEye Scan method: 2θ / θ continuous scan Measurement range (2θ): 15° to 90° Step width (2θ): 0.01° setting Counting time: 1 second / step Sample stage rotation: 15 rpm The background and CuKα2 line peaks can be removed from the obtained XRD pattern using analysis software such as DIFFRAC.EVA.
[0217] If the measurement sample is a powder, it can be set by placing it in a glass sample holder, sprinkling the sample on a greased silicone non-reflective plate, etc. If the measurement sample is a positive electrode, the positive electrode can be attached to the substrate with double-sided tape, and the positive electrode active material layer can be set to match the measurement surface required by the device.
[0218] The ideal powder XRD patterns calculated from the O3' type crystal structure, the monoclinic O1(15) type crystal structure, and the H1-3 type crystal structure model are shown in Figures 7, 8, 9(A), and 9(B). xThe ideal XRD patterns calculated from the crystal structure of LiCoO2O3 with x=1 in CoO2 and trigonal O1 with x=0 are also shown. Figures 9(A) and 9(B) show the XRD patterns of the O3' type crystal structure, monoclinic O1(15) type crystal structure, and H1-3 type crystal structure, with Figure 9(A) showing an enlarged view of the region where 2θ is in the range of 18° to 21°, and Figure 9(B) showing an enlarged view of the region where 2θ is in the range of 42° to 46°. The patterns of LiCoO2(O3) and CoO2(O1) were created using Reflex Powder DiffracTion, one of the modules of Materials Studio (BIOVIA), from crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) (see Non-Patent Document 4). The range of 2θ was 15° to 75°, Step size=0.01, and wavelength λ1=1.540562×10 -10 m and λ2 were not set, and monochromator was set to single. The pattern of the H1-3 type crystal structure was similarly created from the crystal structure information described in Non-Patent Document 3. The patterns of the O3' type and monoclinic O1(15) type crystal structures were estimated from the XRD pattern of the positive electrode active material, and fitted using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker), and XRD patterns were created in the same manner as the others.
[0219] As shown in Figures 7, 9(A) and 9(B), in the O3' type crystal structure, diffraction peaks appear in the 2θ range of 19.13° or more and less than 19.37°, and in the 2θ range of 45.37° or more and less than 45.57°.
[0220] In addition, in the monoclinic O1(15) crystal structure, diffraction peaks appear in the 2θ range of 19.37° to 19.57° and in the 2θ range of 45.57° to 45.67°.
[0221] However, as shown in Figures 8, 9(A) and 9(B), no peaks appear at these positions in the H1-3 type crystal structure and trigonal O1. xThe appearance of peaks at 19.13° or more and less than 19.37° and / or 19.37° or more and 19.57° or less, and at least 45.37° or more and less than 45.57° and / or at least 45.57° or more and 45.67° or less when x in CoO2 is small can be said to be a characteristic of the positive electrode active material particle 100 of one embodiment of the present invention.
[0222] This can also be said to be because, in the positive electrode active material particle 100 according to one embodiment of the present invention, the positions at which XRD diffraction peaks appear are close between the crystal structure where x=1 and the crystal structure where x≦0.24. More specifically, for the main diffraction peaks of the crystal structure where x=1 and the crystal structure where x≦0.24 appear at 2θ of 42° or more and 46° or less, the difference in 2θ is 0.7° or less, more preferably 0.5° or less.
[0223] The positive electrode active material particles 100 according to one embodiment of the present invention are Li x When x in CoO2 is small, it may have O3' and / or monoclinic O1(15) type crystal structure, but not all of the particles may have O3' and / or monoclinic O1(15) type crystal structure. It may contain other crystal structures, or may be partially amorphous. However, when Rietveld analysis is performed on the XRD pattern, it is preferable that the O3' and / or monoclinic O1(15) type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more. If the O3' and / or monoclinic O1(15) type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more, it can be a positive electrode active material with sufficiently excellent cycle characteristics.
[0224] Similarly, when Rietveld analysis is performed, the H1-3 type and O1 type crystal structures are preferably 50% or less, more preferably 34% or less, and even more preferably substantially not observed.
[0225] Furthermore, even after 100 or more charge / discharge cycles from the start of measurement, when Rietveld analysis is performed, the O3' type and / or monoclinic O1(15) type crystal structure is preferably 35% or more, more preferably 40% or more, and even more preferably 43% or more.
[0226] Also, the sharpness of the diffraction peaks in the XRD pattern indicates the high crystallinity. Therefore, it is preferable that each diffraction peak after charging is sharp, that is, the full width at half maximum is narrow. For example, it is preferable that the full width at half maximum is narrow. The full width at half maximum varies depending on the XRD measurement conditions and the value of 2θ, even for peaks generated from the same crystal phase. In the case of the above-mentioned measurement conditions, the full width at half maximum is preferably 0.2° or less, more preferably 0.15° or less, and even more preferably 0.12° or less, for example, in peaks observed at 2θ=43° or more and 46° or less. It is not necessary that all peaks meet this requirement. If some peaks meet this requirement, it can be said that the crystallinity of the crystal phase is high. Such high crystallinity contributes to the stabilization of the crystal structure after charging sufficiently.
[0227] In addition, the crystallite size of the O3' type and monoclinic O1(15) crystal structures of the positive electrode active material particles 100 is reduced to only about 1 / 20 of that of LiCoO2(O3) in the discharged state. Therefore, even if the XRD measurement conditions are the same as those of the positive electrode before and after charging and discharging, the Li x When x in CoO2 is small, clear peaks of O3' and / or monoclinic O1(15) crystal structure can be confirmed. On the other hand, in conventional LiCoO2, even if some parts have a structure similar to O3' and / or monoclinic O1(15) crystal structure, the crystallite size becomes small and the peak becomes broad and small. The crystallite size can be calculated from the full width at half maximum of the XRD peak.
[0228] In the positive electrode active material particle 100 according to one embodiment of the present invention, as described above, it is preferable that the influence of the Jahn-Teller effect is small. As long as the influence of the Jahn-Teller effect is small, a transition metal such as nickel or manganese may be contained as an additive element in addition to cobalt.
[0229] For example, when the nickel concentration is 5% and 7.5%, the a-axis / c-axis tends to change significantly, and when the nickel concentration is 7.5%, the distortion of the a-axis becomes large. The distortion may be caused by the Jahn-Teller distortion of trivalent nickel. Therefore, it is preferable that nickel is less than 7.5 atomic % of the transition metal M contained in the positive electrode active material particle 100.
[0230] Furthermore, when the manganese concentration is 5% or more, the behavior of the change in lattice constant is different, suggesting that it does not follow Vegard's law. Therefore, among the transition metals M contained in the positive electrode active material particles 100, manganese is preferably 4 atomic % or less.
[0231] The above ranges of nickel concentration and manganese concentration do not necessarily apply to the surface layer portion 100a, that is, the concentrations in the surface layer portion 100a may be higher than the above ranges.
[0232] As a result of considering the above-mentioned preferable range of the lattice constant, it was found that in the positive electrode active material of one embodiment of the present invention, the layered rock-salt crystal structure of the positive electrode active material particle 100 in a state in which no charge / discharge is performed or in a discharged state, which can be estimated from the XRD pattern, has an a-axis lattice constant of 2.814 × 10 -10 m or larger, 2.817×10 -10 m and the c-axis lattice constant is 14.05×10 -10 m or larger, 14.07×10 -10 It has been found that the value is preferably smaller than m. The state in which charging and discharging are not performed may be, for example, the powder state prior to fabrication of the positive electrode of a secondary battery.
[0233] Alternatively, in the layered rock-salt crystal structure of the positive electrode active material particles 100 in a state where no charge or discharge is being performed or in a discharged state, it is preferable that the value obtained by dividing the lattice constant of the a-axis by the lattice constant of the c-axis (a-axis / c-axis) is greater than 0.20000 and smaller than 0.20049.
[0234] Alternatively, when XRD analysis is performed on the layered rock salt type crystal structure of the positive electrode active material particle 100 in a state where no charging or discharging is performed or in a discharged state, a first peak may be observed at 2θ of 18.50° or more and 19.30° or less, and a second peak may be observed at 2θ of 38.00° or more and 38.80° or less.
[0235] <XPS> In X-ray photoelectron spectroscopy (XPS), in the case of inorganic oxides, when monochromatic aluminum Kα rays are used as the X-ray source, it is possible to analyze a region from the surface to a depth of about 2 to 8 nm (usually 5 nm or less), so the concentration of each element can be quantitatively analyzed in a region about half the depth of the surface layer 100a. In addition, narrow scan analysis can be used to analyze the bonding state of elements. The quantitative accuracy of XPS is often about ±1 atomic %, with a lower limit of about 1 atomic %, depending on the element.
[0236] In the positive electrode active material particle 100 according to one embodiment of the present invention, the concentration of one or more selected from the additive elements is preferably higher in the surface layer portion 100a than in the interior portion 100b. This is synonymous with the fact that the concentration of one or more selected from the additive elements in the surface layer portion 100a is preferably higher than the average concentration of the entire positive electrode active material particle 100. Therefore, for example, it can be said that the concentration of one or more additive elements selected from the surface layer portion 100a measured by XPS or the like is preferably higher than the average concentration of the additive elements in the entire positive electrode active material particle 100 measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry). For example, it is preferable that the magnesium concentration of at least a part of the surface layer portion 100a measured by XPS or the like is higher than the magnesium concentration of the entire positive electrode active material particle 100. It is also preferable that the titanium concentration of at least a part of the surface layer portion 100a is higher than the titanium concentration of the entire positive electrode active material particle 100. It is also preferable that the nickel concentration in at least a part of the surface layer portion 100a is higher than the nickel concentration in the entire positive electrode active material particle 100. It is also preferable that the aluminum concentration in at least a part of the surface layer portion 100a is higher than the aluminum concentration in the entire positive electrode active material particle 100. It is also preferable that the fluorine concentration in at least a part of the surface layer portion 100a is higher than the fluorine concentration in the entire positive electrode active material particle 100.
[0237] The surface and surface layer 100a of the positive electrode active material particle 100 according to one embodiment of the present invention do not include carbonates, hydroxyl groups, etc. that are chemically adsorbed after the preparation of the positive electrode active material particle 100. Also, the electrolyte, binder, conductive material, or compounds derived from these that are attached to the surface of the positive electrode active material particle 100 are not included. Therefore, when quantifying the elements contained in the positive electrode active material, correction may be made to exclude carbon, hydrogen, excess oxygen, excess fluorine, etc. that can be detected by surface analysis such as XPS. For example, XPS allows the type of bond to be separated by analysis, and correction may be made to exclude C-F bonds derived from the binder.
[0238] Furthermore, before being subjected to various analyses, the sample such as the positive electrode active material and the positive electrode active material layer may be washed in order to remove the electrolyte, binder, conductive material, or compounds derived therefrom that are attached to the surface of the positive electrode active material. At this time, lithium may dissolve in the solvent used for washing, but even in this case, the added element is unlikely to dissolve, and therefore the atomic ratio of the added element is not affected.
[0239] The concentration of the added element may be compared in terms of the ratio to cobalt. By using the ratio to cobalt, the influence of carbonates and the like chemically adsorbed after the preparation of the positive electrode active material can be reduced and comparison is preferably made. For example, the ratio of the number of magnesium atoms to the number of cobalt atoms, Mg / Co, as determined by XPS analysis, is preferably 0.4 to 1.5. On the other hand, the ratio of Mg / Co as determined by ICP-MS analysis is preferably 0.001 to 0.06.
[0240] Similarly, in order to sufficiently secure a path for lithium insertion and desorption, the positive electrode active material particle 100 preferably has a higher concentration of lithium and cobalt than each of the additive elements in the surface layer portion 100a. This means that the concentration of lithium and cobalt in the surface layer portion 100a is preferably higher than the concentration of one or more additive elements selected from the additive elements contained in the surface layer portion 100a measured by XPS or the like. For example, it is preferable that the concentration of at least a part of cobalt in the surface layer portion 100a measured by XPS or the like is higher than the concentration of magnesium in at least a part of the surface layer portion 100a measured by XPS or the like. Similarly, it is preferable that the concentration of lithium is higher than the concentration of magnesium. It is also preferable that the concentration of cobalt is higher than the concentration of nickel. Similarly, it is preferable that the concentration of lithium is higher than the concentration of nickel. It is also preferable that the concentration of cobalt is higher than aluminum. Similarly, it is preferable that the concentration of lithium is higher than the concentration of aluminum. It is also preferable that the concentration of cobalt is higher than fluorine. Similarly, it is preferable that the concentration of lithium is higher than fluorine.
[0241] Furthermore, it is more preferable that aluminum is widely distributed in a deep region, for example, on the surface or in a region having a depth of 5 nm to 50 nm from the reference point. Therefore, although aluminum is detected in an analysis of the entire positive electrode active material particle 100 using ICP-MS, GD-MS, etc., it is more preferable that the concentration of aluminum is not detected by XPS, etc., or is 1 atomic % or less.
[0242] Furthermore, when the positive electrode active material particle 100 according to one embodiment of the present invention is subjected to XPS analysis, the number of magnesium atoms is preferably 0.4 times or more and 1.2 times or less, more preferably 0.65 times or more and 1.0 times or less, relative to the number of cobalt atoms. The number of nickel atoms is preferably 0.15 times or less, more preferably 0.03 times or more and 0.13 times or less, relative to the number of cobalt atoms. The number of aluminum atoms is preferably 0.12 times or less, more preferably 0.09 times or less, relative to the number of cobalt atoms. The number of fluorine atoms is preferably 0.3 times or more and 0.9 times or less, more preferably 0.1 times or more and 1.1 times or less, relative to the number of cobalt atoms. The above ranges indicate that these additive elements are not attached to a narrow range on the surface of the positive electrode active material particle 100, but are widely distributed in a preferred concentration in the surface layer portion 100a of the positive electrode active material particle 100.
[0243] When performing XPS analysis, for example, monochromated aluminum Kα rays can be used as the X-ray source. The take-off angle can be set to, for example, 45°. For example, the measurement can be performed using the following equipment and conditions. Measurement equipment: PHI Quantera II X-ray source: Monochromatic Al Kα (1486.6eV) Detection area: 100μmφ Detection depth: Approx. 4 to 5 nm (take-off angle 45°) Measurement spectrum: Wide scan, narrow scan of each detected element
[0244] Furthermore, when the positive electrode active material particle 100 according to one embodiment of the present invention is subjected to XPS analysis, the peak showing the bond energy between fluorine and other elements is preferably equal to or greater than 682 eV and less than 685 eV, and more preferably about 684.3 eV, which is a different value from both the bond energy of lithium fluoride (685 eV) and the bond energy of magnesium fluoride (686 eV).
[0245] Furthermore, when the positive electrode active material particle 100 according to one embodiment of the present invention is subjected to XPS analysis, the peak showing the bond energy between magnesium and other elements is preferably equal to or greater than 1302 eV and less than 1304 eV, and more preferably about 1303 eV, which is a different value from the bond energy of magnesium fluoride, 1305 eV, and is close to the bond energy of magnesium oxide.
[0246] <EDX> It is preferable that one or more selected from the additive elements contained in the positive electrode active material particles 100 have a concentration gradient. It is more preferable that the depth from the surface of the concentration peak differs depending on the additive element in the positive electrode active material particles 100. The concentration gradient of the additive element can be evaluated, for example, by exposing a cross section of the positive electrode active material particle 100 using a focused ion beam (FIB) or the like and analyzing the cross section using energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.
[0247] Among EDX measurements, EDX area analysis is performed by scanning an area and evaluating the area in two dimensions. EDX line analysis is performed by scanning a line and evaluating the distribution of atomic concentration within the positive electrode active material. Line analysis may also be used to extract data from a linear area of EDX area analysis. Point analysis is used to measure an area without scanning it.
[0248] By EDX surface analysis (e.g., element mapping), the concentration of the added element can be quantitatively analyzed in the surface layer 100a, the inside 100b, and the vicinity of the grain boundary of the positive electrode active material particle 100. In addition, by EDX line analysis, the concentration distribution and maximum value of the added element can be analyzed. In addition, analysis of thinning the sample such as STEM-EDX is more suitable because it can analyze the concentration distribution in the depth direction from the surface to the center of the positive electrode active material in a specific region without being affected by the distribution in the depth direction.
[0249] Since the positive electrode active material particle 100 is a compound containing oxygen and a transition metal capable of inserting and extracting lithium, the interface between a region where the transition metal M (e.g., Co, Ni, Mn, Fe, etc.) that is oxidized and reduced with the insertion and extraction of lithium and oxygen is present and a region where they are not present is defined as the surface of the positive electrode active material. When the positive electrode active material is subjected to analysis, a protective film may be attached to the surface, but the protective film is not included in the positive electrode active material. As the protective film, a single layer film or a multilayer film of carbon, metal, oxide, resin, etc. may be used.
[0250] In STEM-EDX analysis, the graph of the amount of characteristic X-rays of the element detected does not change sharply in principle or due to measurement errors, and it may be difficult to precisely determine the surface. Therefore, when referring to the depth direction in STEM-EDX analysis, the transition metal M is the average amount of the internal detection M AVE and the background mean value M BG The point where oxygen is 50% of the sum of the two, and the average amount of oxygen detected inside is O AVE and the average background O BG The reference point on the surface is the point where the sum of the interior and the background is 50%. If the points where the sum of the interior and the background is 50% are different for the transition metal M and oxygen, this is considered to be due to the influence of metal oxides and carbonates containing oxygen attached to the surface. Therefore, the average value M AVE and the background mean value M BG In the case of a positive electrode active material having a plurality of transition metals M, the M of the element with the largest count number in the inner portion 100b can be used. AVE and M.BG The reference point can be obtained using the following formula:
[0251] The average background value of the transition metal M BG can be obtained by averaging, for example, a range of 2 nm or more, preferably 3 nm or more, from the outside of the positive electrode active material, avoiding the vicinity where the amount of detected transition metal M starts to increase. AVE can be obtained by averaging a range of 2 nm or more, preferably 3 nm or more, at a depth of 30 nm or more, preferably 50 nm or more, from the region where the counts of the transition metal M and oxygen are saturated and stable, for example, the region where the detected amount of the transition metal M starts to increase. BG and the average internal detection amount of oxygen, O AVE can also be found in the same way.
[0252] The surface of the positive electrode active material particle 100 in a cross-sectional STEM (scanning transmission electron microscope) image or the like is the boundary between an area where an image originating from the crystal structure of the positive electrode active material is observed and an area where it is not observed, and is the outermost area where atomic columns originating from the atomic nuclei of metal elements having atomic numbers larger than that of lithium among the metal elements constituting the positive electrode active material are confirmed. The surface in a STEM image or the like may be determined in conjunction with an analysis with higher spatial resolution.
[0253] In addition, a peak in STEM-EDX ray analysis is the maximum value (the apex of a convex shape) of characteristic X-rays that appears in a graph of the characteristic X-ray intensity for each element, and when multiple peaks are confirmed, it refers to the maximum value of the characteristic X-rays. Note that noise in STEM-EDX ray analysis can be considered to be measured values with a full width at half maximum that is less than the spatial resolution (R), for example, R / 2 or less.
[0254] The effect of noise can be reduced by scanning the same location multiple times under the same conditions. For example, the integrated value of six scans can be used as the amount of each element detected. The number of scans is not limited to six, and more scans can be performed and the average can be used as the amount of each element detected.
[0255] The STEM-EDX line analysis can be carried out, for example, as follows: First, a protective film is deposited on the surface of the positive electrode active material. For example, carbon can be deposited using a carbon coating unit of an ion sputtering device (MC1000 manufactured by Hitachi High-Technologies).
[0256] Next, the positive electrode active material is sliced to prepare a STEM cross-section sample. For example, the slice processing can be performed using a FIB-SEM (Hitachi High-Tech XVision200TBS). In this case, the pickup is performed using an MPS (micro-probing system), and the finishing processing conditions can be, for example, an acceleration voltage of 10 kV.
[0257] For STEM-EDX analysis, for example, a STEM device (Hitachi High-Tech HD-2700) can be used, and an EDAX Octane T Ultra W (Dual EDS) can be used as the EDX detector. During EDX analysis, the acceleration voltage of the STEM device is set to 200 kV, and the emission current is set to 6 μA to 10 μA, and a portion of the sliced sample with minimal depth and unevenness is measured. The magnification is, for example, about 150,000 times. The conditions for EDX analysis can be drift correction, line width 42 nm, pitch 0.2 nm, and frame number 6 or more.
[0258] When EDX areal analysis or EDX point analysis is performed on positive electrode active material particle 100 according to one embodiment of the present invention, it is preferable that the concentration of each additional element, particularly additional element X, in surface layer portion 100a is higher than that in interior portion 100b.
[0259] For example, when EDX area analysis or EDX point analysis is performed on a positive electrode active material particle 100 having magnesium as an additive element, the magnesium concentration in the surface layer 100a is preferably higher than the magnesium concentration in the interior 100b. Furthermore, when EDX line analysis is performed, the peak of the magnesium concentration in the surface layer 100a is preferably present on the surface of the positive electrode active material particle 100 or within a depth of 3 nm from a reference point toward the center, more preferably within a depth of 1 nm, and even more preferably within a depth of 0.5 nm.
[0260] Furthermore, when EDX line analysis is performed, the maximum value of the magnesium concentration in the surface layer 100a (detected amount of magnesium / (sum of detected amounts of magnesium, oxygen, cobalt, fluorine, aluminum, titanium, and nickel) is preferably 0.5 atomic% or more and 10 atomic% or less, and more preferably 1 atomic% or more and 10 atomic% or less.
[0261] Furthermore, when EDX line analysis is performed, the maximum value of the titanium concentration (detected amount of titanium / (sum of detected amounts of magnesium, oxygen, cobalt, fluorine, aluminum, titanium, and nickel) in the surface layer portion 100a is preferably 0.2 atomic % or more and 5 atomic % or less, and more preferably 0.5 atomic % or more and 2 atomic % or less.
[0262] Furthermore, when EDX line analysis is performed, the maximum value of the nickel concentration in the surface layer portion 100a (detected amount of nickel / (sum of detected amounts of magnesium, oxygen, cobalt, fluorine, aluminum, titanium, and nickel) is preferably 0.2 atomic % or more and 5 atomic % or less, and more preferably 0.5 atomic % or more and 3 atomic % or less.
[0263] In the positive electrode active material particles 100 having magnesium and fluorine as additive elements, the fluorine distribution preferably has an overlapping region with the magnesium distribution. For example, the difference in the depth direction between the peak of the fluorine concentration and the peak of the magnesium concentration is preferably within 10 nm, more preferably within 3 nm, and even more preferably within 1 nm.
[0264] In addition, when EDX analysis is performed, the fluorine concentration peak of the surface layer 100a is preferably present on the surface of the positive electrode active material particle 100 or at a depth of 3 nm from the reference point toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. Furthermore, if the fluorine concentration peak is slightly closer to the surface than the magnesium concentration peak, it is more preferable because it increases resistance to hydrofluoric acid. For example, it is more preferable that the fluorine concentration peak is 0.5 nm or more closer to the surface than the magnesium concentration peak, and even more preferable that it is 1.5 nm or more closer to the surface.
[0265] In the positive electrode active material particle 100 having nickel as an additive element, the nickel concentration peak of the surface layer 100a is preferably present at a depth of 3 nm from the surface or reference point toward the center of the positive electrode active material particle 100, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. In the positive electrode active material particle 100 having magnesium and nickel, the nickel distribution preferably has an overlapping region with the magnesium distribution. For example, the difference in depth between the nickel concentration peak and the magnesium concentration peak is preferably within 3 nm, more preferably within 1 nm.
[0266] In the positive electrode active material particle 100 having titanium as an additive element, the peak of the titanium concentration in the surface layer 100a is preferably present at a depth of 3 nm from the surface or reference point toward the center of the positive electrode active material particle 100, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. In the positive electrode active material particle 100 having magnesium and titanium, the distribution of titanium preferably has an overlapping region with the distribution of magnesium. For example, the difference in the depth direction between the peak of titanium concentration and the peak of magnesium concentration is preferably within 3 nm, more preferably within 1 nm.
[0267] Furthermore, when the positive electrode active material particle 100 contains aluminum as an added element, it is preferable that the peak of the magnesium, nickel, or fluorine concentration is closer to the surface than the peak of the aluminum concentration in the surface layer portion 100a when EDX line analysis is performed. For example, the aluminum concentration peak is preferably present on the surface of the positive electrode active material particle 100, or at a depth of 0.5 nm to 50 nm from the reference point toward the center, and more preferably at a depth of 5 nm to 50 nm.
[0268] When the positive electrode active material particles 100 contain magnesium, titanium, nickel, and aluminum as described above, a battery using the positive electrode active material particles 100 can achieve both "high cycle characteristics" that can suppress deterioration of discharge capacity during repeated high-voltage charging (e.g., charging up to an upper limit of 4.6 V) and discharging, and "high low-temperature characteristics" that can provide a large discharge capacity at low temperatures (e.g., 0°C, -20°C, -40°C).
[0269] In addition, when EDX line analysis, surface analysis, or point analysis is performed on the positive electrode active material particle 100, the ratio of the number of atoms of magnesium Mg and cobalt Co (Mg / Co) at the peak of magnesium concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.4. The ratio of the number of atoms of aluminum Al and cobalt Co (Al / Co) at the peak of aluminum concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.45. The ratio of the number of atoms of nickel Ni and cobalt Co (Ni / Co) at the peak of nickel concentration is preferably 0 to 0.2, more preferably 0.01 to 0.1. The ratio of the number of atoms of fluorine F and cobalt Co (F / Co) at the peak of fluorine concentration is preferably 0 to 1.6, more preferably 0.1 to 1.4.
[0270] For example, when the added element is magnesium, when the positive electrode active material particles 100 are subjected to a line analysis or area analysis, the ratio of the number of magnesium atoms to the number of cobalt atoms (Mg / Co) in the vicinity of the grain boundaries is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. Even more preferably, it is 0.030 or more and 0.20 or less. Or it is preferably 0.020 or more and 0.30 or less. Or it is preferably 0.020 or more and 0.20 or less. Or it is preferably 0.025 or more and 0.50 or less. Or it is preferably 0.025 or more and 0.20 or less. Or it is preferably 0.030 or more and 0.50 or less. Or it is preferably 0.030 or more and 0.30 or less. Furthermore, when the above-mentioned range is present in multiple locations, for example, three or more locations, of the positive electrode active material particle 100, this indicates that the added element is not attached to a narrow area on the surface of the positive electrode active material particle 100, but is widely distributed in a preferred concentration in the surface portion 100a of the positive electrode active material particle 100.
[0271] EPMA EPMA (Electron Probe Microanalysis) can also quantify elements. Area analysis can analyze the distribution of each element.
[0272] When the cross section of the positive electrode active material particle 100 according to one embodiment of the present invention is subjected to EPMA surface analysis, it is preferable that one or more selected from the additive elements have a concentration gradient, as in the EDX analysis results. It is more preferable that the depth of the concentration peak from the surface differs depending on the additive element. The preferable range of the concentration peak of each additive element is also the same as in the case of EDX.
[0273] However, EPMA analyzes a region from the surface to a depth of about 1 μm. Therefore, the quantitative values of each element may differ from the measurement results obtained by other analytical methods. For example, when the surface analysis of the positive electrode active material particle 100 is performed by EPMA, the concentration of each added element present in the surface layer 100a may be lower than the result of XPS.
[0274] <Raman spectroscopy> As described above, at least a part of the surface layer portion 100a of the positive electrode active material particles 100 of one aspect of the present invention preferably has a rock salt-type crystal structure. Therefore, when the positive electrode active material particles 100 and the positive electrode having the same are analyzed by Raman spectroscopy, it is preferable that a cubic crystal structure including a rock salt type as well as a layered rock salt crystal structure is observed. In the STEM image and the selected area electron diffraction pattern described later, cobalt substituted at the lithium position with a certain frequency in the depth direction during observation, and cobalt present at the oxygen four-coordination position, etc., cannot be detected as bright spots in the STEM image and the selected area electron diffraction pattern. On the other hand, since Raman spectroscopy is an analysis that captures the vibration mode of bonds such as Co-O, even if the abundance of the corresponding Co-O bond is small, peaks at the wave numbers of the corresponding vibration modes may be observed. Furthermore, Raman spectroscopy can measure a range with an area of several μm on the surface layer portion and a depth of about 1 μm, so that a state existing only on the particle surface can be captured with high sensitivity. 2 Since it can measure a range with a depth of about 1 μm, it can sensitively capture the state existing only on the particle surface.
[0275] For example, when the laser wavelength is 532 nm, in layered rock salt-type LiCoO2, peaks (vibration modes: E -1 to 490 cm -1 , 580 cm -1 to 600 cm -1 ) are observed at g , A 1g ). On the other hand, in cubic CoO x (0 < x < 1) (rock salt-type Co 1-y O(0 < y < 1) or spinel-type Co3O4), a peak (vibration mode: A -1 to 685 cm -1 ) is observed at 665 cm 1g .
[0276] Therefore, let the integrated intensity at 470 cm -1 to 490 cm -1 be I1, the integrated intensity at 580 cm -1 to 600 cm -1 be I2, and the integrated intensity at 665 cm -1 to 685 cm -1When the integrated intensity at is I3, the value of I3 / I2 is preferably 1% or more and 10% or less, and more preferably 3% or more and 9% or less.
[0277] When a cubic crystal structure such as a rock-salt type is observed in the above range, it can be said that surface layer portion 100a of positive electrode active material particle 100 has a rock-salt type crystal structure in a preferred range.
[0278] <Microelectron diffraction pattern> It is preferable that the characteristics of the rock salt type crystal structure are observed together with the layered rock salt crystal structure in the ultrafine electron diffraction pattern using an ultrafine electron beam with an electron beam diameter of 3 nm or less, for example 2 nm or less. However, in the STEM image and the ultrafine electron diffraction pattern, taking into consideration the above-mentioned difference in sensitivity, it is preferable that the characteristics of the rock salt type crystal structure are not too strong in the surface layer portion 100a, especially in the outermost surface (for example, 1 nm deep from the surface). This is because the lithium layer can secure a diffusion path for lithium and have a stronger function of stabilizing the crystal structure if an additive element such as magnesium is present in the lithium layer while maintaining the layered rock salt type crystal structure, rather than the outermost surface being covered with the rock salt type crystal structure.
[0279] Therefore, for example, when a micro-electron diffraction pattern of a region having a depth of 1 nm or less from the surface and a micro-electron diffraction pattern of a region having a depth of 3 nm to 10 nm are obtained, it is preferable that the difference in lattice constant calculated from these patterns be small.
[0280] For example, the difference in lattice constant calculated from a measurement point at a depth of 1 nm or less from the surface and a measurement point at a depth of 3 nm to 10 nm is preferably 0.1 Å or less for the a-axis and 1.0 Å or less for the c-axis, more preferably 0.05 Å or less for the a-axis and more preferably 0.6 Å or less for the c-axis, even more preferably 0.04 Å or less for the a-axis and even more preferably 0.3 Å or less for the c-axis.
[0281] <Surface roughness and specific surface area> The positive electrode active material particle 100 according to one embodiment of the present invention preferably has a smooth surface with few irregularities. A smooth surface with few irregularities indicates that the effect of the flux described below is fully exerted and the surfaces of the additive element source and lithium cobalt oxide are melted. Therefore, this is one factor indicating that the distribution of the additive element in the surface layer portion 100a is good.
[0282] Whether the surface is smooth and has few projections and recesses can be determined from, for example, a cross-sectional SEM image or cross-sectional TEM image of the positive electrode active material particle 100, the specific surface area of the positive electrode active material particle 100, or the like.
[0283] For example, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material particle 100 as follows.
[0284] First, the positive electrode active material particle 100 is processed by FIB or the like to expose the cross section. At this time, it is preferable to cover the positive electrode active material particle 100 with a protective film, a protective agent, or the like. Next, an SEM image of the interface between the protective film or the like and the positive electrode active material particle 100 is taken. The SEM image is subjected to noise processing using image processing software. For example, Gaussian blurring (σ=2) is performed, and then binarization is performed. Furthermore, interface extraction is performed using image processing software. Furthermore, the interface line between the protective film or the like and the positive electrode active material particle 100 is selected using an automatic selection tool or the like, and data is extracted to a spreadsheet software or the like. Using the functions of the spreadsheet software or the like, correction is performed from a regression curve (quadratic regression), and a parameter for calculating roughness is obtained from the data after the slope correction, and the root mean square surface roughness (RMS) is obtained by calculating the standard deviation. In addition, this surface roughness is the surface roughness at least in the outer periphery of the particle of the positive electrode active material at 400 nm.
[0285] The particle surface of the positive electrode active material particle 100 of this embodiment preferably has a root mean square (RMS) surface roughness, which is an index of roughness, of less than 3 nm, preferably less than 1 nm, and more preferably less than 0.5 nm.
[0286] The image processing software for noise processing, interface extraction, etc. is not particularly limited, but for example, "ImageJ" described in Non-Patent Documents 8 to 10 can be used. The spreadsheet software is also not particularly limited, but for example, Microsoft Office Excel can be used.
[0287] For example, the actual specific surface area S measured by the constant volume gas adsorption method R and the ideal specific surface area S i The smoothness of the surface of the positive electrode active material particle 100 can also be expressed as a numerical value based on the ratio of the surface smoothness to the surface smoothness.
[0288] Ideal specific surface area S i is calculated assuming that all particles have the same diameter, the same weight, and an ideal spherical shape.
[0289] The median diameter D50 can be measured by a particle size distribution meter using a laser diffraction / scattering method, etc. The specific surface area can be measured by a specific surface area measuring device using a gas adsorption method by a constant volume method, for example.
[0290] The positive electrode active material particles 100 according to one embodiment of the present invention have an ideal specific surface area S calculated from the median diameter D50. i and the actual specific surface area S R Ratio of S R / S i It is preferable that the ratio is 2.1 or less.
[0291] Alternatively, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material particle 100 by the following method.
[0292] First, a surface SEM image of the positive electrode active material particle 100 is obtained. At this time, a conductive coating may be applied as a pretreatment for observation. The observation surface is preferably perpendicular to the electron beam. When comparing multiple samples, the measurement conditions and observation area are the same.
[0293] Next, using image processing software (such as "ImageJ"), the above SEM image is converted to, for example, an 8-bit image (called a grayscale image). A grayscale image contains luminance (brightness information). For example, in an 8-bit grayscale image, luminance can be expressed as 2 to the power of 8 = 256 gradations. Dark areas have lower gradations, and bright areas have higher gradations. The change in luminance can be quantified in relation to the number of gradations. This number is called the grayscale value. Obtaining the grayscale value makes it possible to numerically evaluate the unevenness of the positive electrode active material.
[0294] Furthermore, it is possible to visually express the luminance change in the target area. For example, the gradation distribution in the target area can be shown as a histogram, and a histogram with three-dimensional information added is called a luminance histogram. By obtaining a luminance histogram, it becomes possible to visually understand and evaluate the unevenness of the positive electrode active material.
[0295] When evaluating the positive electrode active material particle 100 of one embodiment of the present invention, the difference between the maximum and minimum values of the grayscale value is preferably 120 or less, more preferably 115 or less, and even more preferably 70 or more and 115 or less. The standard deviation of the grayscale value is preferably 11 or less, more preferably 8 or less, and even more preferably 4 or more and 8 or less.
[0296] <Particle size distribution analysis using cross-sectional SEM images of positive electrodes> The particle size distribution of the positive electrode active material particles 100 can also be calculated from a cross-sectional SEM image of the positive electrode active material particles 100 by the method described below.
[0297] First, an analysis region is cut out from the obtained cross-sectional SEM image. For example, a range of 50 μm or more × 100 μm or more can be cut out as a range having a sufficient area for image analysis, but this is not limited to this. Depending on factors such as the size of the positive electrode active material, a smaller area or a larger area may be cut out.
[0298] Note that the cross-sectional SEM image may be cut out using the functions of image processing software. For example, ImageJ may be used as the image processing software, and the image may be cut out using its crop function.
[0299] Next, the cut-out first image is binarized using image processing software, and particle analysis is performed.
[0300] ImageJ, for example, can be used as the image processing software. The binarization process is explained below. The first image shown in 256 grayscale levels is used as a frequency graph excluding black (value 0) and white (value 255), and the low value side (HWHM_L) and high value side (HWHM_H) are obtained as the half width at half maximum (HWHM) of the maximum peak in the frequency graph. Next, the minimum value a of the range twice the width of HWHM_L on the low value side from the value that is the peak top (maximum frequency) of the maximum peak, and the maximum value b of the range twice the width of HWHM_H on the high value side are determined.
[0301] Next, binarization is performed so that the range of values less than a is white, the range of values between a and b is black, and the range of values greater than b is white. Specifically, binarization is performed as Threshold(a,b) using the Threshold function of ImageJ. After that, random bright spots thought to be caused by conductive materials are removed using the Gray Morphology (radius=3, operator=open, type=circle) and Gray Morphology (radius=1, operator=close, type=circle) conditions, and a second image can be obtained.
[0302] Next, using the second image, the particle size (projected area) was determined to be 0.5 μm using the Analyze Particles function of ImageJ. 2 More than 700μm 2 The following particles are detected and the area S of each particle is obtained. Next, the diameter r of each particle is calculated based on the area S of each particle (Equation 1).
[0303]
number
[0304] In this way, the particle size distribution of each particle can be calculated from the cross-sectional SEM image. Performing the above analysis is called performing particle size distribution analysis using a cross-sectional SEM image of the positive electrode.
[0305] A coating portion may be attached to at least a portion of the surface of the positive electrode active material particle 100. Fig. 10 shows an example of a positive electrode active material particle 100 having a coating portion 104 attached thereto.
[0306] The coating portion 104 is preferably formed by the accumulation of decomposition products of the electrolyte and the organic electrolyte solution during charging and discharging. x When charging is repeated such that x in CoO2 is 0.24 or less, it is expected that the charge-discharge cycle characteristics will be improved by having a coating portion derived from the electrolyte on the surface of the positive electrode active material particle 100. This is for reasons such as suppressing an increase in impedance on the surface of the positive electrode active material or suppressing the elution of cobalt. For example, the coating portion 104 preferably contains carbon, oxygen, and fluorine. Furthermore, when LiBOB and / or SUN (suberonitrile) are used as the electrolyte, a good quality coating portion is easily obtained. Therefore, the coating portion 104 having one or more selected from boron, nitrogen, sulfur, and fluorine may be a good quality coating portion and is preferable. In addition, the coating portion 104 does not have to cover the entire positive electrode active material particle 100. For example, it is sufficient that 50% or more of the surface of the positive electrode active material particle 100 is covered, more preferably 70% or more, and even more preferably 90% or more.
[0307] <Powder Resistance Measurement> The positive electrode active material particle 100 according to one embodiment of the present invention has a stable crystal structure even at high voltages. Since the crystal structure of the positive electrode active material is stable in a charged state, it is possible to suppress the decrease in charge / discharge capacity that accompanies repeated charging and discharging. The positive electrode active material particle 100 having the above-mentioned excellent properties is characterized by the above-mentioned < <xrd>> In Li x It was explained that when x in CoO2 is small, it has the O3' type and / or monoclinic O1(15) type crystal structure. <edx>> described a preferable distribution of the additive elements when STEM-EDX analysis was performed on the positive electrode active material particles 100. Furthermore, the positive electrode active material particles 100 of one embodiment of the present invention are also characterized by the volume resistivity of the powder.
[0308] As a feature of the positive electrode active material particle 100 according to one embodiment of the present invention, the volume resistivity of the powder of the positive electrode active material particle 100 is 1.0×10 8 Ω cm or more 1.0×10 10 It is preferable that the resistance is 5.0×10 8 Ω cm or more 1.5×10 9 It is more preferable that the resistivity is Ω·cm or less.
[0309] The positive electrode active material particles 100 having the above volume resistivity have a stable crystal structure even at high voltages, and can be used as an indicator that the surface layer portion 100a, which is important for the stability of the crystal structure of the positive electrode active material in a charged state, has been well formed.
[0310] A method for measuring the volume resistivity of the powder of the positive electrode active material particles 100 according to one embodiment of the present invention will be described.
[0311] The volume resistivity of a powder is preferably measured by an instrument having a terminal for resistance measurement and a mechanism for applying pressure to the powder to be measured. The terminal for resistance measurement is preferably four terminals (also called four probes). As a measuring device having a terminal for resistance measurement and a mechanism for applying pressure to the powder (sample) to be measured, for example, MCP-PD51 manufactured by Mitsubishi Chemical Analytech Co., Ltd. can be used. As a resistance measuring instrument, a low resistance measuring instrument Loresta-GP or a high resistance measuring instrument Hiresta-GP can be used. Loresta-GP can be used to measure low resistance samples, and Hiresta-GP can be used to measure high resistance samples. In addition, a stable environment such as a dry room is preferable as the measurement environment. As the dry room environment, for example, a temperature environment of 25°C and a dew point environment of minus 40°C or less are preferable. When performing measurements in a high humidity environment, the electrical resistance decreases due to the influence of moisture in the air, and the original physical property value may not be obtained.
[0312] The measurement of the volume resistivity of a powder using the measuring device shown above will be described. First, a powder sample is set in the measuring section. In the measuring section, the powder sample and a terminal for resistance measurement are in contact with each other, and pressure can be applied to the powder sample. The measuring section also has a structure for measuring the volume of the powder sample in the measuring section. Specifically, the measuring section has a cylindrical space, and the powder sample is set in the space. The structure for measuring the volume of the powder sample described above can measure the height of the powder set in the space, thereby measuring the volume occupied by the powder at that time.
[0313] In measuring the volume resistivity of a powder, the electrical resistance of the powder and the volume of the powder are measured while pressure is applied to the powder. The pressure applied to the powder can be measured under a variety of conditions. For example, the electrical resistance and the volume of the powder can be measured under each of the pressure conditions of 16 MPa, 25 MPa, 38 MPa, 51 MPa, and 64 MPa. The volume resistivity of the powder can be calculated from the measured electrical resistance and volume of the powder.
[0314] When the above-described measurement is performed, the volume resistivity of the powder of the positive electrode active material particles 100 according to one embodiment of the present invention is 1.0×10 8 Ω cm or more 1.0×10 10 When the dielectric constant is less than 5.0×10 Ω·cm, favorable cycle characteristics are observed in charge-discharge cycle tests under high charging voltage conditions. 8 Ω cm or more 1.5×10 9 When the electrical resistance is Ω·cm or less, more favorable cycle characteristics are exhibited in a charge-discharge cycle test under high voltage conditions.
[0315] Unless otherwise specified in the present specification, the volume resistivity measured as described above is the volume resistivity of the powder.
[0316] <Ion Chromatography> A method for measuring the powder of the positive electrode active material particles 100 according to one embodiment of the present invention by ion chromatography will be described below. The measurement by ion chromatography involves a pretreatment step of dissolving the powder of the positive electrode active material particles 100 in acid to obtain a solution for measurement, and a measurement step of measuring the solution.
[0317] The ion chromatography apparatus and conditions are not particularly limited. For example, the measurement can be performed using the following apparatus and conditions. As the ion chromatography apparatus, for example, the ion chromatography system Dionex ICS-2100 manufactured by Thermo Fisher Scientific can be used.
[0318] An example of the pretreatment of ion chromatography will be described. 250 mg of powder of the positive electrode active material particles 100 and 2 ml of 0.05 M H2SO4 aqueous solution are prepared, put into a glass container with a lid, and mixed to obtain a first mixed solution. For mixing, ultrasonic waves may be applied for about 1 hour. Then, the container is left to stand in a room temperature environment for 12 hours or more. Then, 1 ml of the filtrate obtained by filtering the first mixed solution is mixed with 9 ml of pure water to obtain a second mixed solution. In this way, the powder of the positive electrode active material particles 100 can be pretreated.
[0319] Next, the second mixed solution obtained by the above pretreatment is used to perform ion chromatography, which may include anion analysis and cation analysis.
[0320] An example of the conditions for anion analysis is shown below. Anion analysis can be performed at 35°C using a Dionex IonPac AG20 (2 x 50 mm) or Dionex IonPac AS20 (2 x 250 mm) column. A KOH aqueous solution is used as the eluent, and the flow rate is preferably set to 0.44 ml / min. It is preferable to perform gradient measurement so that the concentration of the KOH aqueous solution gradually increases. An electric conductivity detector is used as the detector, and a mixed anion standard solution manufactured by Kanto Chemical Co., Ltd. can be used to create a calibration curve.
[0321] An example of the conditions for cation analysis is shown below. Cation analysis can be performed at 30°C using a Dionex IonPac CG16 (3 x 50 mm) or Dionex IonPac CS16 (3 x 250 mm) column. The eluent should be an aqueous solution of methanesulfonic acid (MSA), and the flow rate should be 0.36 ml / min. It is recommended that the concentration of the MSA aqueous solution be kept constant and that isocratic measurements be performed. An electric conductivity detector is used as the detector, and a mixed cation standard solution manufactured by Kanto Chemical Co., Ltd. can be used to create a calibration curve.
[0322] The above-described ion chromatography measurement allows quantitative measurement of anions such as fluorine (F) and chlorine (Cl), and allows quantitative measurement of cations such as lithium (Li), magnesium (Mg), cobalt (Co), and nickel (Ni).
[0323] In ion chromatography measurement of the powder of the positive electrode active material particles 100 according to one embodiment of the present invention, the weight of fluorine relative to the weight of the powder is preferably 100 ppm or more and 1000 ppm or less, and more preferably 100 ppm or more and 200 ppm or less.
[0324] This embodiment can be used in combination with other embodiment modes.
[0325] (Embodiment 2) In this embodiment, an example of a manufacturing method of a positive electrode active material particle 100 according to one embodiment of the present invention will be described with reference to FIGS.
[0326] In order to prepare the positive electrode active material particle 100 having the distribution, composition, and / or crystal structure of the additive element as described in the previous embodiment, the method of adding the additive element is important. At the same time, it is also important that the crystallinity of the inner portion 100b is good.
[0327] Therefore, in the process of producing the positive electrode active material particles 100, it is preferable to first synthesize lithium cobalt oxide, and then mix in the additive element source and perform a heat treatment.
[0328] In the method of synthesizing lithium cobalt oxide having an additive element by mixing an additive element source with a cobalt source and a lithium source, it is difficult to increase the additive element concentration in the surface layer portion 100a. Furthermore, if the additive element source is only mixed after the lithium cobalt oxide is synthesized and heating is not performed, the additive element will only adhere to the lithium cobalt oxide without being dissolved in the lithium cobalt oxide. If sufficient heating is not performed, it is also difficult to distribute the additive element well. Therefore, it is preferable to synthesize lithium cobalt oxide, mix the additive element source, and perform a heat treatment. This heat treatment after mixing the additive element source is sometimes called annealing.
[0329] However, if the annealing temperature is too high, cation mixing occurs, increasing the possibility that an added element, such as magnesium, will enter the cobalt site. Magnesium present in the cobalt site will be mixed with Li x When x in CoO2 is small, there is no effect of maintaining the layered rock-salt crystal structure of R-3m. Furthermore, if the heat treatment temperature is too high, there are concerns that adverse effects such as cobalt being reduced to divalent and lithium being evaporated may occur.
[0330] Therefore, it is preferable to mix a material that functions as a flux with the additive element source. If the melting point is lower than that of lithium cobalt oxide, the material can function as a flux. For example, fluorine compounds such as lithium fluoride are suitable. Adding a flux lowers the melting point of the additive element source and lithium cobalt oxide. Lowering the melting point makes it easier to distribute the additive element well at a temperature where cation mixing is unlikely to occur.
[0331] <<Production method 1 of positive electrode active material>> The manufacturing method 1 for the positive electrode active material particles 100 will be described with reference to FIGS. 11 to 12(C).
[0332] <Step S11> In step S11 shown in FIG. 11(A), a lithium source (Li source) and a cobalt source (Co source) are prepared as starting materials, that is, lithium and transition metal materials, respectively.
[0333] As the lithium source, it is preferable to use a compound containing lithium, such as lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. It is preferable that the lithium source has high purity, and for example, it is preferable to use a material with a purity of 99.99% or more.
[0334] As the cobalt source, it is preferable to use a compound containing cobalt, for example, cobalt oxide such as tricobalt tetroxide, cobalt hydroxide, or the like.
[0335] The cobalt source is preferably of high purity, for example, a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and even more preferably 5N (99.999%) or more may be used. By using a material of high purity, impurities in the positive electrode active material can be controlled. As a result, the capacity of the secondary battery is increased and / or the reliability of the secondary battery is improved.
[0336] <Step S12> Next, in step S12 shown in FIG. 11(A), the lithium source and the cobalt source are pulverized and mixed to prepare a mixed material. The pulverization and mixing can be performed in a dry or wet manner. The wet method is preferable because it can be crushed into smaller pieces. When performing the wet method, a solvent is prepared. As the solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent that does not easily react with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. It is preferable to mix the lithium source and the cobalt source with dehydrated acetone with a purity of 99.5% or more, in which the moisture content is suppressed to 10 ppm or less, and then pulverize and mix them. By using dehydrated acetone with the above purity, it is possible to reduce impurities that may be mixed in.
[0337] A ball mill, a bead mill, or the like can be used as a means for pulverization and mixing. When using a ball mill, it is preferable to use aluminum oxide balls or zirconium oxide balls as media. Zirconium oxide balls are preferable because they emit less impurities. Furthermore, when using a ball mill, a bead mill, or the like, it is preferable to set the peripheral speed to 100 mm / s or more and 2000 mm / s or less in order to suppress contamination from the media.
[0338] <Step S13> Next, in step S13 shown in FIG. 11(A), the mixed material is heated. The heating is preferably performed at 800° C. to 1100° C., more preferably at 900° C. to 1000° C., and even more preferably at about 950° C. If the temperature is too low, the decomposition and melting of the lithium source and the cobalt source may be insufficient. On the other hand, if the temperature is too high, defects may occur due to lithium transpiration from the lithium source and / or cobalt being excessively reduced. For example, cobalt may change from trivalent to divalent, inducing oxygen defects.
[0339] If the heating time is too short, lithium cobalt oxide will not be synthesized, but if it is too long, productivity will decrease. For example, the heating time is preferably 1 hour or more and 100 hours or less, and more preferably 2 hours or more and 20 hours or less.
[0340] The rate of temperature rise depends on the heating temperature reached, but it is recommended to set it to between 80°C / h and 250°C / h. For example, if heating at 1000°C for 10 hours, the rate of temperature rise should be 200°C / h.
[0341] Heating is preferably performed in an atmosphere with little moisture, such as dry air, for example, an atmosphere with a dew point of -50° C. or less, more preferably an atmosphere with a dew point of -80° C. or less. In order to suppress impurities that may be mixed into the material, the impurity concentrations of CH4, CO, CO2, H2, etc. in the heating atmosphere should each be 5 ppb (parts per billion) or less.
[0342] The heating atmosphere is preferably an atmosphere containing oxygen, and dry air can be used. For example, there is a method of continuously introducing dry air into the furnace. In this case, the flow rate of the dry air is preferably 10 L / min. The method of continuously introducing oxygen into the furnace and having oxygen flow through the furnace is called flow.
[0343] When the heating atmosphere is an atmosphere containing oxygen, a method that does not allow oxygen to flow may be used. For example, the inside of the furnace may be depressurized and then filled with oxygen (or purged) to prevent the oxygen from entering or leaving the furnace. For example, the furnace may be depressurized until the differential pressure gauge indicates -970 hPa, and then oxygen may be filled to 50 hPa.
[0344] After heating, the material may be naturally cooled, but it is preferable that the time required for the material to cool from the specified temperature to room temperature is within a range of 10 to 50 hours. However, cooling to room temperature is not always necessary, and it is sufficient to cool the material to a temperature acceptable for the next step.
[0345] The heating in this step may be performed using a rotary kiln or a roller hearth kiln. Heating using a rotary kiln can be performed while stirring in either a continuous or batch type.
[0346] A crucible, setter or sheath can be used as a container used during heating. The container preferably has aluminum oxide. Aluminum oxide has the property of being less likely to release impurities. In this embodiment, a sheath made of aluminum oxide with a purity of 99.5% or more, preferably 99.9% or more, is used. In the case of mass production, a setter or sheath made of mullite-cordierite (Al2O3, SiO2, MgO) is used. It is preferable to place a lid on the container before heating. This can prevent the material from volatilizing.
[0347] In addition, it is preferable to use a container that has been used multiple times rather than a new one when heating. In this specification, a new container refers to one that has undergone the process of putting in and heating materials containing lithium, transition metal M, and / or additive elements two or less times. In addition, a container that has been used multiple times refers to one that has undergone the process of putting in and heating materials containing lithium, transition metal M, and / or additive elements three or more times. This is because when a new container is used, there is a risk that some of the materials, including lithium fluoride, may be absorbed, diffused, moved, and / or attached to the container during heating. If some of the materials are lost due to these reasons, there is a growing concern that the distribution of the additive elements, especially in the surface layer of the positive electrode active material, will not be in a preferred range. On the other hand, this risk is less likely with a container that has been used multiple times.
[0348] After the heating is completed, the recovered material may be crushed as necessary and sieved. When recovering the heated material, it may be transferred from the container to a mortar and then recovered. The mortar is preferably made of aluminum oxide or zirconium oxide. Aluminum oxide is a material that does not easily release impurities. Specifically, it is preferable to use a mortar made of aluminum oxide with a purity of 90% or more, preferably 99% or more. Note that the same heating conditions as those in step S13 can be applied to the heating steps described below other than step S13.
[0349] <Step S14> By the above process, lithium cobalt oxide (LiCoO2) can be synthesized as shown in step S14 of FIG. 11(A).
[0350] Although an example of producing lithium cobalt oxide by a solid phase method as in steps S11 to S14 has been shown, lithium cobalt oxide may be produced by a coprecipitation method, a hydrothermal method, or a composite oxide other than lithium cobalt oxide may be produced.
[0351] Note that lithium cobalt oxide that has been synthesized in advance may be used in step S14, in which case steps S11 to S13 can be omitted.
[0352] The lithium cobalt oxide synthesized in advance will be described. Tables 1 to 3 show the concentration of each element obtained by glow discharge mass spectrometry (GD-MS) for four types of lithium cobalt oxide (material Sm-1, material Sm-2, material Sm-3, and material Sm-4). The unit of concentration is weight ppm (wt ppm). For ease of viewing, the tables are divided into three tables, Tables 1 to 3. In the tables, "Matrix" means that it is the main component, "Binder" means that it is the auxiliary electrode, "Source" means that there is an influence from the material of the measuring device, "<" means that it was below the detection limit, "≦" means that the interfering element overlaps but is below the numerical value, and "~" means that there is variation or that the interfering element partially overlaps but is a semi-quantitative value.
[0353] [Table 2]
[0354] [Table 3]
[0355] [Table 4]
[0356] From the above table, the concentration range of each element contained in the lithium cobalt oxide (material Sm-1, material Sm-2, material Sm-3, material Sm-4) can be read. For example, when material Sm-1 is used as the lithium cobalt oxide used in step S14, it can be read from the above table that the lithium cobalt oxide preferably has a magnesium concentration of 50 wt ppm or less, a fluorine concentration of 50 wt ppm or less, a titanium concentration of 50 wt ppm or less, and more preferably a combined magnesium and fluorine concentration of 100 wt ppm or less.
[0357] <Step S15> Next, in step S15 shown in FIG. 11(A), the lithium cobalt oxide is heated. Since this is the first heating of the lithium cobalt oxide, the heating in step S15 may be called initial heating. Alternatively, since the heating is performed before step S20 described below, it may be called preheating or pretreatment. The container and / or lid used in this step are the same as those used in step S13. Although the following effects are expected from the initial heating, the initial heating is not essential in order to obtain the positive electrode active material which is one embodiment of the present invention.
[0358] As described above, the initial heating causes lithium to be desorbed from a part of the surface layer 100a of the lithium cobalt oxide. In addition, the effect of increasing the crystallinity of the interior 100b can be expected. In addition, impurities may be mixed into the lithium source and / or cobalt source prepared in step S11, etc. The initial heating can reduce the impurities in the lithium cobalt oxide completed in step S14.
[0359] Furthermore, the initial heating has the effect of smoothing the surface of the lithium cobalt oxide. A smooth surface means that there are few irregularities, the composite oxide is generally rounded, and the corners are rounded. Furthermore, a state in which there is little foreign matter adhering to the surface is called smooth. Foreign matter is thought to be the cause of irregularities, so it is preferable that it does not adhere to the surface.
[0360] For this initial heating, it is not necessary to prepare a lithium source, a source of an additive element, or a material that functions as a flux.
[0361] If the heating time of this step is too short, sufficient effect is not obtained, but if it is too long, productivity decreases. For example, the heating conditions can be selected from those described in step S13. In addition to the heating conditions, the heating temperature of this step is preferably lower than the temperature of step S13 in order to maintain the crystal structure of lithium cobalt oxide. Furthermore, the heating time of this step is preferably shorter than the time of step S13 in order to maintain the crystal structure of lithium cobalt oxide. For example, heating is preferably performed at a temperature of 700°C or higher and 1000°C or lower for 2 hours or longer and 20 hours or shorter.
[0362] The effect of enhancing the crystallinity of the inner portion 100b is, for example, the effect of mitigating distortion, displacement, and the like resulting from a shrinkage difference or the like possessed by the lithium cobalt oxide produced in step S13.
[0363] The heating in step S13 may cause a temperature difference between the surface and the inside of the lithium cobalt oxide. The temperature difference may induce a shrinkage difference. It is also considered that the temperature difference causes the difference in fluidity between the surface and the inside, which causes the shrinkage difference. The energy related to the shrinkage difference gives the lithium cobalt oxide a difference in internal stress. The internal stress difference is also called strain, and this energy is sometimes called strain energy. The internal stress is removed by the initial heating in step S15, or in other words, the strain energy is considered to be homogenized by the initial heating in step S15. When the strain energy is homogenized, the strain of the lithium cobalt oxide is relaxed. As a result, the surface of the lithium cobalt oxide may become smooth. This is also called the surface being improved. In other words, it is considered that the shrinkage difference caused in the lithium cobalt oxide is relaxed and the surface of the lithium cobalt oxide becomes smooth after step S15.
[0364] Furthermore, the shrinkage difference may cause microscopic deviations, such as deviations of crystals, in the lithium cobalt oxide. In order to reduce such deviations, it is advisable to carry out this step. Through this step, it is possible to equalize the deviations of the composite oxide. When the deviations are equalized, the surface of the lithium cobalt oxide may become smooth. This is also referred to as the alignment of crystal grains. In other words, it is believed that through step S15, deviations of crystals and the like that have occurred in the lithium cobalt oxide are alleviated, and the surface of the lithium cobalt oxide becomes smooth.
[0365] When lithium cobalt oxide, which has a smooth surface, is used as the positive electrode active material, deterioration during charging and discharging as a secondary battery is reduced and cracks in the positive electrode active material can be prevented.
[0366] In addition, in step S14, lithium cobalt oxide synthesized in advance may be used. In this case, steps S11 to S13 can be omitted. By carrying out step S15 on lithium cobalt oxide synthesized in advance, lithium cobalt oxide with a smooth surface can be obtained.
[0367] <Step S20> Next, as shown in step S20, it is preferable to add an additive element to the lithium cobalt oxide. In the manufacturing method of the positive electrode active material described in this embodiment, the additive element is added in a plurality of steps, so that the additive element added first in the flow shown in Fig. 11 is described as A1, the additive element added second time is A2, and the additive element added third time is A3. The step of adding the additive element A1 will be described with reference to Fig. 12(A).
[0368] <Step S21> 12(A), a source of an additive element (A1 source) to be added to lithium cobalt oxide is prepared. In step S21, a lithium source may be prepared together with the A1 source.
[0369] The additive element A1 may be any of the additive elements described in the previous embodiment, specifically, one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, tungsten, chromium, molybdenum, rhenium, tantalum, phosphorus, and boron.
[0370] When magnesium is selected as the additive element, the source of the additive element can be called a magnesium source. As the magnesium source, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. can be used. In addition, a plurality of the above-mentioned magnesium sources may be used.
[0371] When fluorine is selected as the additive element, the additive element source can be called a fluorine source. As the fluorine source, for example, lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF3, CeF4), lanthanum fluoride (LaF3), or sodium aluminum hexafluoride (Na3AlF6) can be used. Among these, lithium fluoride is preferred because it has a relatively low melting point of 848° C. and is easily melted in the heating step described below.
[0372] Magnesium fluoride can be used as both the fluorine source and the magnesium source, and lithium fluoride can be used as the lithium source. Another lithium source that can be used in step S21 is lithium carbonate.
[0373] The fluorine source may be a gas, such as fluorine (F2), carbon fluoride, sulfur fluoride, oxygen fluoride (OF2, O2F2, O3F2, O4F2, O5F2, O6F2, O2F), or nitrogen trifluoride (NF3), which may be mixed into the atmosphere in the heating step described below. A plurality of the above-mentioned fluorine sources may be used.
[0374] In FIG. 11 and FIG. 12(A), a case where magnesium and fluorine are used as the additive element A1 will be described. Lithium fluoride (LiF) is prepared as the fluorine source, and magnesium fluoride (MgF2) is prepared as the fluorine source and magnesium source. When lithium fluoride and magnesium fluoride are mixed at about LiF:MgF2=65:35 (molar ratio), the effect of lowering the melting point is maximized. On the other hand, if the amount of lithium fluoride is large, there is a concern that the lithium becomes excessive and the cycle characteristics deteriorate. Therefore, the molar ratio of lithium fluoride and magnesium fluoride is preferably LiF:MgF2=x:1 (0≦x≦1.9), more preferably LiF:MgF2=x:1 (0.1≦x≦0.5), and even more preferably LiF:MgF2=x:1 (x=0.33 or nearby). In this specification, etc., "nearby" refers to a value that is greater than 0.9 times and less than 1.1 times the value.
[0375] <Step S22> 12(A), the magnesium source and the fluorine source are pulverized and mixed. This step can be performed under the pulverization and mixing conditions selected from those described in step S12.
[0376] <Step S23> Next, in step S23 shown in Fig. 12(A), the above-mentioned crushed and mixed materials are collected to obtain the A1 source. Note that the A1 source shown in step S23 has multiple starting materials and can be called a mixture.
[0377] The particle size of the mixture is preferably D50 (median diameter) 600 nm to 10 μm, more preferably 1 μm to 5 μm. Even when a single material is used as the additive element source, the D50 (median diameter) is preferably 600 nm to 10 μm, more preferably 1 μm to 5 μm.
[0378] When such a finely powdered mixture (including the case where only one kind of additive element is included) is mixed with lithium cobalt oxide in a later step, the mixture can be easily attached uniformly to the surface of the lithium cobalt oxide particles. If the mixture is attached uniformly to the surface of the lithium cobalt oxide particles, it is preferable because the additive element can be easily distributed or diffused uniformly in the surface layer portion 100a of the composite oxide after heating.
[0379] <Step S31> 11, lithium cobalt oxide and the Al source are mixed together. The ratio of the number of cobalt atoms Co in the lithium cobalt oxide to the number of magnesium atoms Mg in the Al source is preferably Co:Mg=100:y (0.1≦y≦6), and more preferably Co:Mg=100:y (0.3≦y≦3).
[0380] The mixing in step S31 is preferably performed under milder conditions than the mixing in step S12 in order not to destroy the particulate lithium cobalt oxide. For example, the mixing is preferably performed under conditions of a lower rotation speed or shorter time than in step S12. It can also be said that the dry method is a milder condition than the wet method. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconium oxide balls as the media.
[0381] In this embodiment, the materials are mixed in a ball mill using zirconium oxide balls with a diameter of 1 mm at 150 rpm for 1 hour in a dry room with a dew point of -100°C or higher and -10°C or lower.
[0382] <Step S32> 11, the mixed material is collected to obtain a mixture 901. When collecting the material, it may be crushed and then sieved, if necessary.
[0383] <Step S33> Next, in step S33 shown in FIG. 11, the mixture 901 is heated. The heating conditions can be selected from those described in step S13. The heating time is preferably 2 hours or more. At this time, the pressure inside the furnace may be higher than atmospheric pressure in order to increase the oxygen partial pressure of the heating atmosphere. This is because if the oxygen partial pressure of the heating atmosphere is insufficient, cobalt, etc. will be reduced, and lithium cobalt oxide, etc. may not be able to maintain the layered rock salt type crystal structure.
[0384] Here, a supplementary note on the heating temperature will be provided. The lower limit of the heating temperature in step S33 must be equal to or higher than the temperature at which the reaction between the lithium cobalt oxide and the additive element source proceeds. The temperature at which the reaction proceeds may be any temperature at which interdiffusion between the lithium cobalt oxide and the elements contained in the additive element source occurs, and may be lower than the melting temperatures of these materials. An oxide will be used as an example to explain the melting temperature T m 0.757 times (Tammann temperature T d ) solid-phase diffusion occurs. Therefore, the heating temperature in step S33 should be 650° C. or higher.
[0385] Of course, the reaction proceeds more easily if the temperature is equal to or higher than the melting point of one or more of the materials contained in the mixture 901. For example, when LiF and MgF2 are contained as the additive element source, the eutectic point of LiF and MgF2 is around 742°C, so that the lower limit of the heating temperature in step S33 is preferably set to 742°C.
[0386] In addition, the mixture 903 obtained by mixing so that LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio) shows an endothermic peak at about 830° C. in differential scanning calorimetry (DSC measurement). Therefore, the lower limit of the heating temperature is more preferably 830° C.
[0387] A higher heating temperature is preferable because the reaction proceeds more easily, the heating time is shorter, and the productivity is high.
[0388] The upper limit of the heating temperature is below the melting point (1130°C) of lithium cobalt oxide. At temperatures near the melting point, there is a concern that lithium cobalt oxide may decompose, albeit in a small amount. Furthermore, when heating the mixture 903, it is preferable to control the partial pressure of fluorine or fluoride resulting from the fluorine source, etc., within an appropriate range. If the temperature is too high, the fluoride decreases due to evaporation. For example, the vapor pressure of lithium fluoride rises sharply from 900°C. Therefore, 1000°C is more preferable, 950°C is even more preferable, 900°C is even more preferable, and 850°C or less is even more preferable. If the evaporation of lithium fluoride is suppressed, the surface layer 100a can have fluorine and lithium at a high concentration. If the surface layer 100a has a sufficient amount of lithium, there is also the advantage that a different phase (MgTiO3, etc.) is less likely to be generated when titanium is added in a later process.
[0389] Considering these, the heating temperature in step S33 is preferably 650°C to 1130°C, more preferably 650°C to 1000°C, even more preferably 650°C to 950°C, and even more preferably 650°C to 900°C. Also, it is preferably 742°C to 1130°C, more preferably 742°C to 1000°C, even more preferably 742°C to 950°C, and even more preferably 742°C to 900°C. Also, it is preferably 800°C to 1100°C, 830°C to 1130°C, more preferably 830°C to 1000°C, even more preferably 830°C to 950°C, and even more preferably 830°C to 900°C. The heating temperature in step S33 is preferably higher than that in step S13.
[0390] Furthermore, when the mixture 901 is heated, it is preferable to control the partial pressure of fluorine or fluoride resulting from the fluorine source or the like within an appropriate range.
[0391] In the manufacturing method described in this embodiment, some materials, for example, LiF, which is a fluorine source, may function as a flux. This function allows the heating temperature to be lowered below the melting point of lithium cobalt oxide, for example, to 742°C to 950°C, and allows additive elements such as magnesium to be distributed in the surface layer, making it possible to produce a positive electrode active material with good characteristics.
[0392] However, since LiF has a lower specific gravity in a gaseous state than oxygen, LiF may volatilize or sublime when heated, and if it volatilizes, the amount of LiF in the mixture 903 will decrease. This weakens its function as a flux. Therefore, it is necessary to heat while suppressing the volatilization of LiF. Even if LiF is not used as a fluorine source, etc., Li on the LiCoO2 surface may react with F of the fluorine source to produce LiF, which may then volatilize. Therefore, even if a fluoride with a higher melting point than LiF is used, it is necessary to suppress the volatilization in the same way.
[0393] Therefore, it is preferable to heat the mixture 901 in an atmosphere containing LiF, that is, to heat the mixture 901 in a state where the partial pressure of LiF in the furnace is high. By heating in this manner, it is possible to suppress the volatilization of LiF in the mixture 901. The mixture 901 may be heated with a lid placed on the container containing the mixture 901.
[0394] The heating in this step is preferably performed so as not to cause adhesion between particles of the mixture 901. If the particles of the mixture 901 adhere to each other during heating, the contact area with oxygen in the atmosphere decreases, and the route along which the additive element (e.g., fluorine) diffuses is blocked, which may result in poor distribution of the additive element (e.g., magnesium and fluorine) in the surface layer.
[0395] It is also believed that if an additive element (e.g., fluorine) is uniformly distributed in the surface layer, a smooth positive electrode active material with few irregularities can be obtained. Therefore, in order to maintain the smooth surface or to make it even smoother after the heating in step S15 in this process, it is better for the particles of mixture 901 not to stick together.
[0396] In addition, when heating is performed using a rotary kiln, it is preferable to control the flow rate of the oxygen-containing atmosphere in the kiln. For example, it is preferable to reduce the flow rate of the oxygen-containing atmosphere, or to first purge the atmosphere and not flow the atmosphere after introducing the oxygen atmosphere into the kiln. If oxygen is flowed, the fluorine source may evaporate, which is not preferable in terms of maintaining the smoothness of the surface.
[0397] When heating is performed using a roller hearth kiln, the mixture 901 can be heated in an atmosphere containing LiF, for example, by placing a lid on a container containing the mixture 901.
[0398] Regarding the heating time, the heating time varies depending on conditions such as the heating temperature, the particle size and composition of the lithium cobalt oxide in step S14, etc. When the particle size (e.g., median size) of the lithium cobalt oxide is small, a lower temperature or a shorter heating time may be more preferable than when the particle size is large.
[0399] When the median diameter (D50) of the lithium cobalt oxide in step S14 of Fig. 11 is about 12 µm, the heating temperature is preferably, for example, 650°C or more and 950°C or less. The heating time is preferably, for example, 3 hours or more and 60 hours or less, more preferably 10 hours or more and 30 hours or less, and further preferably about 20 hours. The temperature reduction time after heating is preferably, for example, 10 hours or more and 50 hours or less.
[0400] On the other hand, when the median diameter (D50) of the lithium cobalt oxide in step S14 is about 7 μm, the heating temperature is preferably, for example, 650° C. to 950° C. The heating time is preferably, for example, 1 hour to 10 hours, more preferably about 5 hours. The cooling time after heating is preferably, for example, 10 hours to 50 hours.
[0401] <Step S34> Next, in step S34 shown in FIG. 11, the heated material is recovered and crushed as necessary to obtain composite oxide 902.
[0402] <Step S40> Next, in step S40 shown in FIG. 11, an additive element source (A2 source) is prepared. The additive element A2 can be the additive element described in step S21, and is preferably different from the additive element A1. In the manufacturing method 1 of the positive electrode active material described in FIG. 11 and FIG. 12(B), nickel and aluminum are used as the additive element A2. Nickel oxide, nickel hydroxide, etc. can be used as the nickel source. Aluminum oxide, aluminum hydroxide, etc. can be used as the aluminum source. As shown in steps S41 to S43 of FIG. 12(B), the nickel source and the aluminum source can be crushed to obtain the A2 source. The conditions of step S22 can be referred to for the crushing conditions.
[0403] <Step S51> 11, the composite oxide 902 and the A2 source are mixed. For the mixing conditions, see the description of step S31. When the composite oxide 902 contains lithium cobalt oxide and the A2 source contains an aluminum compound, the aluminum compound is weighed out to be 0.1 mol% or more and 1 mol% or less, preferably 0.1 mol% or more and 0.5 mol% or less, relative to the lithium cobalt oxide.
[0404] <Step S52> 11, the mixed materials are collected to obtain a mixture 903. When collecting the materials, they may be crushed and then sieved, if necessary.
[0405] <Step S53> 11, the mixture 903 is heated. For the heating conditions, see the description of step S33.
[0406] The lower limit of the heating temperature in step S53 must be equal to or higher than the temperature at which the reaction between the lithium cobalt oxide and the additive element source proceeds. The temperature at which the reaction proceeds may be any temperature at which mutual diffusion between the lithium cobalt oxide and the element contained in the additive element source occurs, and may be equal to or higher than 650°C. However, the lower limit of the heating temperature in step S53 does not need to be taken into consideration that the endothermic peak of the mixture 903 obtained by mixing so that LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio) is near 830°C. In addition, a higher heating temperature is preferable because the reaction proceeds more easily, the heating time is shorter, and the productivity is high. Therefore, the lower limit of the heating temperature in step S53 is 750°C, preferably 800°C, and more preferably 850°C.
[0407] The upper limit of the heating temperature in step S53 is set to be lower than the melting point (1130°C) of lithium cobalt oxide. At temperatures close to the melting point, there is a concern that lithium cobalt oxide may decompose, albeit in a small amount. Therefore, 1000°C is more preferable, 950°C is even more preferable, and 900°C is even more preferable.
[0408] The heating temperature in step S53 may preferably be equal to or lower than the heating temperature in step S33, and the heating time in step S53 may preferably be equal to or shorter than the heating time in step S33.
[0409] In step S53, a lid may be placed on the container containing the mixture 903 and the mixture 903 may be heated.
[0410] <Step S54> Next, in step S54 shown in FIG. 11, the heated material is recovered and crushed as necessary to obtain a composite oxide 904.
[0411] <Step S60> Next, in step S60 shown in FIG. 11, an additive element source (A3 source) is prepared. The additive element A3 can be the additive element described in step S21, and is preferably different from the additive element A1 and the additive element A2. In the manufacturing method 1 of the positive electrode active material described in FIG. 11 to FIG. 12(C), titanium is used as the additive element A3, and a titanium compound is used as the titanium source, which is the A3 source. Titanium compounds include titanium oxide and lithium titanate. Titanium oxide includes a compound represented by TiO2, and lithium titanate includes a compound represented by Li2TiO3 and LiTiO2. One or more of the above-mentioned compounds can be used as the titanium source. In particular, when a heating step is performed after mixing the titanium source, it is preferable to use lithium titanate as the titanium source, since there is a possibility that part of the lithium will evaporate during heating. As shown in steps S61 to S63 of FIG. 12(C), the titanium source can be pulverized to obtain the A3 source. The pulverization conditions can refer to the conditions in step S22.
[0412] <Step S71> 11, the composite oxide 904 and the A3 source are mixed. For the mixing conditions, see the description of step S31. When the composite oxide 904 contains lithium cobalt oxide and the A3 source contains a titanium compound, the titanium compound is weighed out to be 0.1 mol% or more and 2 mol% or less, preferably 0.1 mol% or more and 1 mol% or less, relative to the lithium cobalt oxide.
[0413] <Step S72> 11, the mixed materials are collected to obtain a mixture 905. When collecting the materials, they may be crushed and then sieved, if necessary.
[0414] <Step S73> Next, in step S73 shown in FIG. 11, the mixture 905 is heated. The heating conditions can be referred to in the description of step S33. The lower limit of the heating temperature in step S73 must be equal to or higher than the temperature at which the reaction between the lithium cobalt oxide and the additive element source proceeds. The temperature at which the reaction proceeds may be any temperature at which mutual diffusion between the lithium cobalt oxide and the element contained in the additive element source occurs, and may be equal to or higher than 650°C. However, the lower limit of the heating temperature in step S73 does not need to be taken into consideration that the endothermic peak of the mixture 903 obtained by mixing so that LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio) is near 830°C. In addition, a higher heating temperature is preferable because the reaction proceeds more easily, the heating time is shorter, and the productivity is high. Therefore, the lower limit of the heating temperature in step S73 is 750°C, preferably 800°C, and more preferably 850°C.
[0415] The upper limit of the heating temperature in step S73 is set to be lower than the melting point (1130°C) of lithium cobalt oxide. At temperatures close to the melting point, there is a concern that lithium cobalt oxide may decompose, albeit in a small amount. Therefore, 1000°C is more preferable, 950°C is even more preferable, and 900°C is even more preferable.
[0416] The heating temperature in step S73 may preferably be equal to or lower than the heating temperature in step S53. The heating temperature in step S73 is preferably 750° C. or higher and 850° C. or lower. Also, the heating time in step S73 may preferably be equal to or shorter than the heating time in step S53. As will be shown in the examples below, the heating time in step S73 is preferably 2 hours or higher and 10 hours or lower, and the examples below show that 2 hours is more preferable than 10 hours.
[0417] In step S73, a lid may be placed on the container containing the mixture 905 and the mixture 905 may be heated.
[0418] <Step S74> Next, in step S74 shown in Fig. 11, the heated material is collected to obtain positive electrode active material particles 100. At this time, it is preferable to further sieve the collected particles. Through the above steps, the positive electrode active material particles 100 of one embodiment of the present invention can be produced. The positive electrode active material of one embodiment of the present invention has a smooth surface.
[0419] Positive electrode active material particles 100 with a smooth surface may be more resistant to physical destruction due to pressure, etc. than positive electrode active materials that do not have a smooth surface. For example, the positive electrode active material particles 100 are less likely to be destroyed in tests involving pressure, such as a nail penetration test, and as a result, safety may be improved.
[0420] <<Production method 2 of positive electrode active material>> Next, a method for producing a positive electrode active material 2, which is one embodiment of the present invention and is different from method for producing a positive electrode active material 1, will be described with reference to Figures 13(A) and 13(B). Method for producing a positive electrode active material 2 differs from method for producing 1 mainly in the number of times that an additive element is added. For other descriptions, the description of method for producing 1 can be referred to.
[0421] In the manufacturing method 1 of the positive electrode active material, magnesium and fluorine are used as the additive element A1, and nickel and aluminum are used as the additive element A2, and a manufacturing method in which they are added in different steps has been described, but nickel, aluminum, and titanium may be added in the same step. Figures 13(A) and 13(B) show a method of adding these in the same step as step S60. This manufacturing method can also be said to be a simple and highly productive method because it can reduce the mixing and heating steps.
[0422] Also, lithium cobalt oxide having some of the added elements in advance may be used, as described in the manufacturing method 1. For example, if lithium cobalt oxide to which magnesium and fluorine are added is used, steps S11 to S14 and some of the steps in step S20 can be omitted, and nickel, aluminum, and titanium can be added in the same step in step S60. This can be said to be a simple and highly productive method.
[0423] Alternatively, magnesium and fluorine may be added again to lithium cobalt oxide to which magnesium and fluorine have been added in advance in step S20a.
[0424] <<Production method 3 of positive electrode active material>> Next, a method for producing a positive electrode active material 3, which is one embodiment of the present invention and differs from methods for producing a positive electrode active material 1 and 2, will be described with reference to Figures 14(A) and 14(B). Method for producing a positive electrode active material 3 differs from method for producing 1 mainly in the number of times that an additive element is added. For other descriptions, the description of method for producing 1 can be referred to.
[0425] In the manufacturing method 1 of the positive electrode active material, magnesium and fluorine are used as the additive element A1, and nickel and aluminum are used as the additive element A2, and a manufacturing method in which they are added in different steps has been described, but magnesium, fluorine, nickel, and aluminum may be added in the same step. Figures 14(A) and 14(B) show a method of adding these in the same step as step S20a. This manufacturing method can also be said to be a simple and highly productive method because it can reduce the mixing and heating steps.
[0426] Furthermore, in the manufacturing method 1 of the positive electrode active material, the manufacturing method in which the additive element is added after the lithium cobalt oxide is produced has been described, but the present invention is not limited to the above method. The additive element may be added at another timing or may be added multiple times. The timing may be changed depending on the additive element.
[0427] For example, the additive element may be prepared in the same step as the lithium source and the cobalt source at step S11, that is, at the stage of the starting material for the composite oxide. The additive element source added at this time is shown as the A0 source in FIG. 14(A). Then, lithium cobalt oxide containing the additive element can be obtained at step S13. In this case, there is no need to separate the steps S11 to S14 from the steps S21 to S23. This method can be said to be simple and highly productive.
[0428] Also, lithium cobalt oxide having some of the added elements in advance may be used as described in the manufacturing method 1. For example, if lithium cobalt oxide having magnesium and fluorine added thereto is used, steps S11 to S14 and some of the steps in step S20 can be omitted. This is a simple and highly productive method.
[0429] Alternatively, magnesium and fluorine may be added again to lithium cobalt oxide to which magnesium and fluorine have been added in advance in step S20a.
[0430] This embodiment mode can be used in combination with other embodiment modes.
[0431] (Embodiment 3) In this embodiment, an example of a secondary battery of one embodiment of the present invention will be described with reference to FIGS. 15 and 16A to 16C.
[0432] <Example of secondary battery configuration> The following description will be given taking as an example a secondary battery shown in FIG. 15 in which a positive electrode, a negative electrode, and an electrolyte are enclosed in an exterior body.
[0433] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer has a positive electrode active material, and may have a conductive material (synonymous with a conductive additive) and a binder. The positive electrode active material is the positive electrode active material manufactured by the manufacturing method described in the above embodiment.
[0434] The positive electrode active material described in the above embodiment may be mixed with another positive electrode active material.
[0435] Other examples of the positive electrode active material include composite oxides having an olivine type crystal structure, a layered rock salt type crystal structure, or a spinel type crystal structure, such as LiFePO4, LiFeO2, LiNiO2, LiMn2O4, V2O5, Cr2O5, and MnO2.
[0436] In addition, as another positive electrode active material, a lithium-containing material having a spinel-type crystal structure containing manganese such as LiMn2O4 is preferably mixed with lithium nickelate (LiNiO2 or LiNi 1-x M x O2 (0 < x < 1) (M = Co, Al, etc.)). By adopting this configuration, the characteristics of the secondary battery can be improved.
[0437] <Conductive material> The conductive material, also called a conductivity-imparting agent or a conductive auxiliary agent, is a carbon material. By adhering the conductive material between a plurality of active materials, the plurality of active materials are electrically connected to each other, enhancing the conductivity. Note that the term "adhere" does not only refer to the physical close contact between the active material and the conductive material, but also includes cases where a covalent bond is formed, cases where they are bonded by van der Waals forces, cases where the surface of the active material is covered by the conductive material, cases where the conductive material fits into the surface irregularities of the active material, and cases where they are electrically connected even if they are not in contact with each other.
[0438] Active material layers such as the positive electrode active material layer and the negative electrode active material layer preferably have a conductive material.
[0439] As the conductive material, for example, any one or two or more of carbon blacks such as acetylene black and furnace black, graphites such as artificial graphite and natural graphite, carbon fibers such as carbon nanofibers and carbon nanotubes, and graphene compounds can be used.
[0440] As the carbon fiber, for example, carbon fibers such as mesophase pitch-based carbon fibers and isotropic pitch-based carbon fibers can be used. Also, as the carbon fiber, carbon nanofibers or carbon nanotubes can be used. Carbon nanotubes can be produced, for example, by a vapor phase growth method.
[0441] In the present specification and the like, the graphene compound includes graphene, multi-layer graphene, multi-graphene, graphene oxide, multi-layer graphene oxide, multi-graphene oxide, reduced graphene oxide, reduced multi-layer graphene oxide, reduced multi-graphene oxide, graphene quantum dots, and the like. The graphene compound has carbon, has a shape such as a plate shape or a sheet shape, and has a two-dimensional structure formed by six-membered carbon rings. The two-dimensional structure formed by six-membered carbon rings may be called a carbon sheet. The graphene compound may have a functional group. In addition, the graphene compound preferably has a curved shape. In addition, the graphene compound may be rolled up like a carbon nanofiber.
[0442] In this specification and the like, graphene oxide refers to a material that contains carbon and oxygen, has a sheet-like shape, and has a functional group, in particular, an epoxy group, a carboxy group, or a hydroxy group.
[0443] In the present specification and the like, reduced graphene oxide refers to a graphene oxide having a sheet-like shape and a two-dimensional structure formed of six-membered carbon rings, which contains carbon and oxygen. Although reduced graphene oxide functions as a single sheet, multiple sheets may be stacked. Reduced graphene oxide preferably has a portion in which the carbon concentration is greater than 80 atomic % and the oxygen concentration is 2 atomic % to 15 atomic %. By setting such carbon and oxygen concentrations, it can function as a conductive material with high conductivity even in a small amount. In addition, reduced graphene oxide preferably has an intensity ratio G / D of G band to D band in Raman spectrum of 1 or more. Reduced graphene oxide with such an intensity ratio can function as a conductive material with high conductivity even in a small amount.
[0444] The graphene compound may have excellent electrical properties such as high electrical conductivity, and excellent physical properties such as high flexibility and high mechanical strength. The graphene compound may have a sheet-like shape. The graphene compound may have a curved surface, enabling surface contact with low contact resistance. In addition, even if the graphene compound is thin, it may have very high electrical conductivity, and a small amount of the graphene compound may efficiently form a conductive path in the active material layer. Therefore, by using the graphene compound as a conductive material, the contact area between the active material and the conductive material can be increased. The graphene compound may cover 80% or more of the area of the active material. It is preferable that the graphene compound is wrapped around at least a part of the active material particles. It is also preferable that the graphene compound is overlapped on at least a part of the active material particles. It is also preferable that the shape of the graphene compound matches at least a part of the shape of the active material particles. The shape of the active material particles refers to, for example, the unevenness of a single active material particle or the unevenness formed by a plurality of active material particles. It is also preferable that the graphene compound surrounds at least a part of the active material particles. The graphene compound may have holes.
[0445] When using active material particles having a small particle size, for example, active material particles having a size of 1 μm or less, the specific surface area of the active material particles is large, and more conductive paths connecting the active material particles are required. In such a case, it is preferable to use a graphene compound that can efficiently form conductive paths even in a small amount.
[0446] Because of the above-mentioned properties, it is particularly effective to use a graphene compound as a conductive material for secondary batteries that require rapid charging and rapid discharging. For example, secondary batteries for two-wheeled or four-wheeled vehicles and secondary batteries for drones may require rapid charging and rapid discharging characteristics. Rapid charging and discharging may also be required for mobile electronic devices. Rapid charging and discharging refers to charging and discharging at 200 mA / g, 400 mA / g, or 1000 mA / g or more per weight of the positive electrode active material.
[0447] The multiple graphenes or graphene compounds are formed so as to partially cover the multiple granular positive electrode active material particles or to be attached to surfaces of the multiple granular positive electrode active material particles, and therefore are preferably in surface contact with each other.
[0448] Here, a mesh-like graphene compound sheet (hereinafter referred to as a graphene compound net or graphene net) can be formed by bonding multiple graphenes or graphene compounds together. When an active material is covered with a graphene net, the graphene net can also function as a binder that bonds the active materials together. Therefore, the amount of binder can be reduced or no binder can be used, so that the ratio of the active material to the electrode volume and the electrode weight can be improved. That is, the discharge capacity of the secondary battery can be increased.
[0449] In addition, a material used in forming the graphene compound may be mixed with the graphene compound and used in the active material layer. For example, particles used as a catalyst in forming the graphene compound may be mixed with the graphene compound. Examples of catalysts used in forming the graphene compound include silicon oxide (SiO2, SiO x (x<2)), aluminum oxide, iron, nickel, ruthenium, iridium, platinum, copper, germanium, etc. The particles preferably have a median diameter (D50) of 1 μm or less, more preferably 100 nm or less.
[0450] The content of the conductive material relative to the total amount of the active material layer is preferably 1 wt % or more and 10 wt % or less, and more preferably 1 wt % or more and 5 wt % or less.
[0451] Unlike granular conductive materials such as carbon black, which are in point contact with the active material, the graphene compound allows for surface contact with low contact resistance, and therefore can improve the electrical conductivity between the granular active material and the graphene compound with a smaller amount than that of a normal conductive material. This allows the ratio of the active material in the active material layer to be increased, thereby increasing the discharge capacity of the battery.
[0452] Particulate carbon-containing compounds such as carbon black and graphite, or fibrous carbon-containing compounds such as carbon nanotubes, tend to enter into minute spaces. The minute spaces refer to, for example, the regions between a plurality of active materials. By using a combination of a carbon-containing compound that tends to enter into minute spaces and a sheet-like carbon-containing compound such as graphene that can impart conductivity across a plurality of particles, the density of the electrode can be increased and an excellent conductive path can be formed. The battery obtained by the manufacturing method of one embodiment of the present invention has a high capacity density and can be stable, and is effective as an in-vehicle battery.
[0453] [Binder] As the binder, it is preferable to use a rubber material such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Also, as the binder, fluororubber can be used.
[0454] In addition, it is preferable to use, for example, a water-soluble polymer as the binder. For example, polysaccharides can be used as the water-soluble polymer. For the polysaccharides, one or more of cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, regenerated cellulose, and starch can be used. It is even more preferable to use these water-soluble polymers in combination with the above-mentioned rubber material.
[0455] Alternatively, it is preferable to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (polymethyl methacrylate, PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose as the binder.
[0456] The binder may be used in combination of two or more of the above.
[0457] [Current collector] As the current collector, a material having high electrical conductivity, such as metals such as stainless steel, gold, platinum, aluminum, and titanium, and alloys thereof, can be used. In addition, it is preferable that the material used for the positive electrode current collector does not dissolve at the potential of the positive electrode. In addition, an aluminum alloy to which an element that improves heat resistance, such as silicon, titanium, neodymium, scandium, or molybdenum, is added can be used. In addition, it may be formed of a metal element that reacts with silicon to form a silicide. Examples of the metal element that reacts with silicon to form a silicide include zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, and nickel. The current collector can be appropriately used in the form of a foil, plate, sheet, net, punched metal, or expanded metal. It is preferable to use a current collector having a thickness of 5 μm or more and 30 μm or less.
[0458] [Negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may include a conductive material and a binder.
[0459] [Negative electrode active material] As the negative electrode active material, for example, an alloy-based material and / or a carbon-based material can be used.
[0460] As the negative electrode active material, an element capable of carrying out a charge / discharge reaction by alloying / dealloying reaction with lithium can be used. For example, a material containing one or more elements selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. can be used. Such elements have a larger charge / discharge capacity than carbon, and silicon in particular has a high theoretical capacity of 4200mAh / g. For this reason, it is preferable to use silicon as the negative electrode active material. Compounds containing these elements may also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb, SbSn, etc. Here, elements capable of carrying out charge / discharge reactions through alloying / dealloying reactions with lithium, and compounds containing such elements, are sometimes referred to as alloying materials.
[0461] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO x Here, x preferably has a value close to 1. For example, x is preferably 0.2 or more and 1.5 or less, more preferably 0.3 or more and 1.2 or less, or preferably 0.2 or more and 1.2 or less, or preferably 0.3 or more and 1.5 or less.
[0462] As the carbon-based material, graphite, easily graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon nanotubes, graphene, carbon black, and the like may be used.
[0463] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, MCMB may have a spherical shape, which is preferable. In addition, it is relatively easy to reduce the surface area of MCMB, which may be preferable. Examples of natural graphite include flake graphite and spheroidized natural graphite.
[0464] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are formed), graphite exhibits a low potential similar to that of lithium metal (0.05 V to 0.3 V vs. Li / Li + ) This allows lithium-ion secondary batteries to exhibit high operating voltages. Furthermore, graphite is preferred because it has the advantages of relatively high charge / discharge capacity per unit volume, relatively small volume expansion, low cost, and high safety compared to lithium metal.
[0465] In addition, titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten dioxide (WO2), molybdenum dioxide (MoO2), and other oxides can be used.
[0466] In addition, the negative electrode active material is Li3N-type nitride of lithium and transition metals. 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 ) and is preferred.
[0467] When a nitride of lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, and therefore it is preferable to combine it with a material that does not contain lithium ions, such as V2O5 or Cr3O8, as the positive electrode active material. Even when a material that contains lithium ions is used as the positive electrode active material, the nitride of lithium and a transition metal can be used as the negative electrode active material by desorbing the lithium ions contained in the positive electrode active material in advance.
[0468] In addition, materials that undergo a conversion reaction can also be used as the negative electrode active material. For example, transition metal oxides that do not form an alloy with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as the negative electrode active material. Further examples of materials that undergo a conversion reaction include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, and CoS 0.89 Examples of such oxides include sulfides such as NiS and CuS, nitrides such as Zn3N2, Cu3N and Ge3N4, phosphides such as NiP2, FeP2 and CoP3, and fluorides such as FeF3 and BiF3.
[0469] As the conductive material and binder that can be contained in the negative electrode active material layer, materials similar to the conductive material and binder that can be contained in the positive electrode active material layer can be used.
[0470] [Negative electrode current collector] The negative electrode current collector may be made of the same material as the positive electrode current collector, but it is preferable that the negative electrode current collector is made of a material that does not form an alloy with carrier ions such as lithium.
[0471] [Electrolyte] As one form of the electrolyte, an electrolyte solution having a solvent and an electrolyte dissolved in the solvent can be used. The electrolyte solution has a solvent and a lithium salt. As the solvent of the electrolyte solution, an aprotic organic solvent is preferable, and for example, one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc., or two or more of these can be used in any combination and ratio.
[0472] When the electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC), the volume ratio of ethylene carbonate and diethyl carbonate can be x:100-x (where 20≦x≦40) when the total content of ethylene carbonate and diethyl carbonate is 100 vol%. More specifically, a mixed organic solvent containing EC and DEC in a volume ratio of EC:DEC=30:70 can be used.
[0473] When using, as the electrolytic solution, a composition containing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC), when the total content of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate is 100 vol%, a composition having a volume ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate of x:y:100 - x - y (where 5 ≤ x ≤ 35 and 0 < y < 65) can be used. More specifically, a mixed organic solvent containing EC, EMC, and DMC at a volume ratio of EC:EMC:DMC = 30:35:35 can be used.
[0474] Furthermore, as the electrolytic solution, a mixed organic solvent containing a cyclic fluorinated carbonate (which may also be referred to as a fluorinated cyclic carbonate) or a linear fluorinated carbonate (which may also be referred to as a fluorinated linear carbonate) can be used. Furthermore, it is preferable that the above mixed organic solvent contains both a cyclic fluorinated carbonate and a linear fluorinated carbonate. Both the cyclic fluorinated carbonate and the linear fluorinated carbonate have an electron-withdrawing substituent, and it is preferable that the solvation energy of lithium ions is low. Therefore, both the cyclic fluorinated carbonate and the linear fluorinated carbonate are suitable for the electrolytic solution, and these mixed organic solvents are suitable.
[0475] As the cyclic fluorinated carbonate, for example, fluoroethylene carbonate (fluoromethylenecarbonate, FEC, F1EC), difluoroethylene carbonate (DFEC, F2EC), trifluoroethylene carbonate (F3EC), or tetrafluoroethylene carbonate (F4EC) can be used. Note that DFEC has isomers such as cis-4,5 and trans-4,5. Since any of the cyclic fluorinated carbonates has an electron-withdrawing substituent, it is considered that the solvation energy of lithium ions is low. In FEC, the electron-withdrawing substituent is the F group.
[0476] Methyl 3,3,3-trifluoropropionate is an example of a fluorinated chain carbonate. The abbreviation for methyl 3,3,3-trifluoropropionate is "MTFP." In MTFP, the electron-withdrawing substituent is the CF3 group.
[0477] FEC is a cyclic carbonate with a high dielectric constant, and therefore when used in an organic solvent, it has the effect of promoting the dissociation of lithium salts. On the other hand, FEC has a substituent that exhibits electron-withdrawing properties, and therefore desolvation with lithium ions proceeds more easily than ethylene carbonate (EC). Specifically, the solvation energy of lithium ions in FEC is smaller than that of EC that does not have a substituent that exhibits electron-withdrawing properties. Therefore, lithium ions are easily released from the surface of the positive electrode active material and the surface of the negative electrode active material, and the internal resistance of the secondary battery can be reduced. Furthermore, since FEC has a deep highest occupied molecular orbital (HOMO: Highest Occupied Molecular Orbital) level, it is difficult to oxidize and oxidation resistance is improved. On the other hand, there is a concern that FEC has a high viscosity. Therefore, it is recommended to use a mixed organic solvent containing not only FEC but also MTFP in the electrolyte. MTFP is a chain carbonate, and can have the effect of lowering the viscosity of the electrolyte, or maintaining the viscosity at room temperature (typically 25°C) even at low temperatures (typically 0°C). Furthermore, although MTFP has a smaller solvation energy than methyl propionate (abbreviated as "MP"), which does not have an electron-withdrawing substituent, it may form a solvate with lithium ions when used in an electrolyte.
[0478] The organic solvent described above is preferably highly purified with a low content of particulate waste or molecules other than the organic solvent's constituent molecules (hereinafter, also referred to simply as "impurities", including oxygen (O2) or water (H2O)). It is also preferable that the reaction by-products during synthesis are suppressed through appropriate purification. Specifically, the impurities in the electrolyte are 100 ppm or less, preferably 50 ppm or less, and more preferably less than 10 ppm. The concentration of water among the impurities can be detected by Karl Fischer titration.
[0479] Furthermore, it is preferable that the above-mentioned organic solvents have almost no peaks due to impurities that can be confirmed by NMR measurement or the like. "Almost no peaks can be confirmed" includes that the ratio of the integrated area of the peak due to the impurity to the integrated area of the peak due to the main component (simply referred to as integral ratio) is 0.005 or less, preferably 0.002 or less. There are no particular limitations on the device used for NMR measurement, but for example, Bruker's "AVANCE III 400" can be used. Also, 1 Of the five peaks of acetonitrile derived from acetonitrile-d3 used as a solvent in H-NMR measurement, the central peak can be located at 1.94 ppm.
[0480] For example, in the case of MTFP, acetonitrile-d3 solvent was used. 1 It is known that when H-NMR is measured, four peaks appear at δ between 3.29 ppm and 3.43 ppm. However, if other peaks appear in the vicinity, for example, if a peak appears at δ between 3.24 ppm and 3.29 ppm, the peak is considered to be due to impurities. Therefore, if the ratio (integral ratio) of the peak area between 3.24 ppm and 3.29 ppm to the peak area between 3.29 ppm and 3.43 ppm is 0.005 or less, preferably 0.002 or less, it can be said that the peaks due to impurities are almost not confirmed.
[0481] It is preferable to mix FEC having such physical properties and MTFP in a mixed organic solvent so that the volume ratio is x:100-x (where 5≦x≦30, preferably 10≦x≦20), assuming the total content of the mixed organic solvent containing MTFP as 100 vol%. In other words, it is preferable to mix MTFP in a larger amount than FEC in the mixed organic solvent.
[0482] In addition, by using one or more ionic liquids (room-temperature molten salts) that are flame-retardant and non-volatile as a solvent for the electrolyte, even if the internal temperature of the secondary battery rises due to an internal short circuit or overcharging, etc., the secondary battery can be prevented from exploding and / or catching fire. The ionic liquid is composed of a cation and an anion, and includes an organic cation and an anion. Examples of the organic cation used in the electrolyte include aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, and aromatic cations such as imidazolium cations and pyridinium cations. Examples of the anion used in the electrolyte include monovalent amide anions, monovalent methide anions, fluorosulfonate anions, perfluoroalkylsulfonate anions, tetrafluoroborate anions, perfluoroalkylborate anions, hexafluorophosphate anions, and perfluoroalkylphosphate anions.
[0483] [Lithium salt] Examples of the lithium salt (also called electrolyte) dissolved in the above-mentioned solvent include LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 , Li2B 12 Cl 12 Lithium salts such as LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, etc. can be used alone or in any combination and ratio of two or more of these. The lithium salt should be 0.5 mol / L or more and 3.0 mol / L or less relative to the solvent. The use of fluorides such as LiPF6 and LiBF4 improves the safety of lithium-ion secondary batteries.
[0484] The above-mentioned electrolyte is preferably a highly purified electrolyte with a low content of granular waste or elements other than the constituent elements of the electrolyte (hereinafter, simply referred to as "impurities"). Specifically, the weight ratio of impurities to the electrolyte is 1 wt% or less, preferably 0.1 wt% or less, and more preferably 0.01 wt% or less.
[0485] [Additives] The electrolyte may contain an additive. The additive can suppress the reactive decomposition of the electrolyte that may occur on the positive electrode surface or the negative electrode surface when the secondary battery is operated at high voltage and / or high temperature. For example, vinylene carbonate (VC), propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), and lithium bis(oxalate)borate (LiBOB) can be used as the additive. LiBOB is particularly preferred because it is easy to form a good coating. VC or FEC is preferred because it can form a good coating on the negative electrode during charging and discharging, improving the cycle characteristics.
[0486] As the additive, any one or more of dinitrile compounds can be used. Specific examples of the dinitrile compound include succinonitrile, glutaronitrile, adiponitrile (ADN), and ethylene glycol bis(propionitrile) ether (EGBE).
[0487] Further, fluorobenzene may be added to the organic solvent. The concentration of the additive may be, for example, 0.1 wt% or more and 5 wt% or less with respect to the entire electrolyte. PS or EGBE is preferable because it can form a good coating on the positive electrode during charging and discharging, thereby improving cycle characteristics. FB is preferable because it improves the wettability of the organic solvent to the positive electrode and the negative electrode. Dinitrile compounds are preferable because the nitrile groups are oriented to the positive electrode and the negative electrode, inhibiting the oxidative decomposition of the organic solvent, thereby improving the voltage resistance. Furthermore, dinitrile compounds are preferable because they can prevent the dissolution of copper during overdischarge when a current collector having copper is used for the negative electrode. Considering the use of secondary batteries at high voltages, it is preferable to add a nitrile compound.
[0488] [Gel electrolyte] As the gel electrolyte, a polymer gel in which a polymer is swollen with an electrolytic solution may be used. By using a polymer gel electrolyte, a semi-solid electrolyte layer can be provided, and safety against leakage and the like can be improved. In addition, it is possible to make the secondary battery thinner and lighter.
[0489] Examples of the polymer that can be gelled include silicone gel, acrylic gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, and fluorine-based polymer gel.
[0490] Examples of the polymer that can be used include polymers having a polyalkylene oxide structure such as polyethylene oxide (PEO), PVDF, polyacrylonitrile, and copolymers containing these. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. The polymer that is formed may have a porous shape.
[0491] [Solid electrolyte] Instead of the electrolyte, a solid electrolyte containing an inorganic material such as a sulfide or oxide, or a solid electrolyte containing a polymer material such as a PEO (polyethylene oxide) can be used. When a solid electrolyte is used, the installation of a separator and / or spacer becomes unnecessary. In addition, since the entire battery can be solidified, there is no risk of leakage, and safety is dramatically improved.
[0492] [Separator] The secondary battery preferably has a separator. The separator may be made of, for example, paper, nonwoven fabric, glass fiber, ceramics, or synthetic fibers such as nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester, acrylic, polyolefin, or polyurethane. The separator is preferably processed into an envelope shape and disposed so as to encase either the positive electrode or the negative electrode.
[0493] The separator may have a multi-layer structure. For example, an organic material film such as polypropylene or polyethylene may be coated with a ceramic material, a fluorine material, a polyamide material, or a mixture of these. As the ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As the fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As the polyamide material, for example, nylon or aramid (meta-aramid or para-aramid) may be used.
[0494] Coating with ceramic materials improves oxidation resistance, suppressing the deterioration of the separator during high-voltage charging and improving the reliability of the secondary battery. Coating with fluorine-based materials also improves adhesion between the separator and electrodes, improving output characteristics. Coating with polyamide-based materials, especially aramid, improves heat resistance, improving the safety of the secondary battery.
[0495] For example, both sides of a polypropylene film may be coated with a mixture of aluminum oxide and aramid.Alternatively, the surface of the polypropylene film that contacts the positive electrode may be coated with a mixture of aluminum oxide and aramid, and the surface that contacts the negative electrode may be coated with a fluorine-based material.
[0496] By using a separator with a multi-layer structure, the safety of the secondary battery can be maintained even if the overall thickness of the separator is thin, and therefore the discharge capacity per volume of the secondary battery can be increased.
[0497] [Exterior body] The exterior body of the secondary battery can be made of, for example, a metal material such as aluminum and / or a resin material. Also, a film-shaped exterior body can be used. As the film, for example, a three-layer structure film can be used in which a thin metal film having excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is provided on a film made of a material such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as a polyamide-based resin, polyester-based resin, etc. is further provided on the thin metal film as the outer surface of the exterior body.
[0498] <Laminated secondary battery and its manufacturing method> An example of an external view of a laminated secondary battery 500 is shown in FIG. 15. FIG. 15 has a positive electrode 503, a negative electrode 506, a separator 507, an exterior body 509, a positive electrode lead electrode 510, and a negative electrode lead electrode 511. If the laminated secondary battery is mounted in a flexible electronic device, the secondary battery can also be bent in accordance with the deformation of the electronic device. An example of a method for manufacturing the laminated secondary battery will be described with reference to FIGS. 16(A) to 16(C).
[0499] First, as shown in FIG. 16(A), a positive electrode 503 and a negative electrode 506 are prepared. The positive electrode 503 has a positive electrode active material layer 502 and a positive electrode tab 501. The positive electrode tab 501 is a protrusion of a current collector. The negative electrode 506 has a negative electrode active material layer 505 and a negative electrode tab 504. The negative electrode tab 504 is a protrusion of a current collector. Next, as shown in FIG. 16(B), a laminate is formed in which a separator 507 is positioned between the positive electrode 503 and the negative electrode 506. Here, an example is shown in which five pairs of negative electrodes and four pairs of positive electrodes are used. Next, the positive electrode tabs 501 are joined together, and the positive electrode lead electrode 510 is joined to the outermost positive electrode tab 501. For the joining, for example, ultrasonic welding or the like may be used. Similarly, the negative electrode tabs 504 are joined together, and the negative electrode lead electrode 511 is joined to the outermost negative electrode tab 504.
[0500] Next, as shown in FIG. 16C, a laminate having a negative electrode 506 , a separator 507 , and a positive electrode 503 is disposed on an outer casing 509 .
[0501] Thereafter, the exterior body 509 is folded at the portion indicated by the dashed line, and the outer periphery of the exterior body 509 is joined. For the joining, for example, thermocompression bonding or the like may be used. At this time, a region (hereinafter referred to as an inlet) that is not joined is provided in a part (or one side) of the exterior body 509 so that an electrolyte can be introduced later.
[0502] Next, an electrolyte (not shown) is introduced into the inside of the exterior body 509 through an inlet provided in the exterior body 509. The introduction of the electrolyte is preferably performed under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is joined. In this manner, the laminate type secondary battery 500 can be produced.
[0503] By using the positive electrode active material described in the above embodiment for the positive electrode 503, the secondary battery 500 can have a high discharge capacity and excellent cycle characteristics.
[0504] This embodiment mode can be used in appropriate combination with other embodiment modes.
[0505] (Embodiment 4) In this embodiment, an example in which a secondary battery which is one embodiment of the present invention is mounted on an electronic device will be described with reference to FIGS.
[0506] 17A to 17G show examples of electronic devices to which the secondary battery having the positive electrode active material described in the above embodiment is mounted. Examples of electronic devices to which the secondary battery is applied include television devices (also called televisions or television receivers), monitors for computers, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game machines, personal digital assistants, audio playback devices, and large game machines such as pachinko machines.
[0507] Furthermore, a secondary battery having a flexible shape can be incorporated along the curved surfaces of the inner or outer walls of a house or building, or the interior or exterior of an automobile.
[0508] 17A shows an example of a mobile phone. A mobile phone 7400 includes a display portion 7402 built into a housing 7401, operation buttons 7403, an external connection port 7404, a speaker 7405, a microphone 7406, and the like. Note that the mobile phone 7400 includes a secondary battery 7407. By using the secondary battery of one embodiment of the present invention as the secondary battery 7407, a lightweight mobile phone with a long life can be provided.
[0509] FIG. 17B shows a state in which the mobile phone 7400 is bent. When the mobile phone 7400 is deformed by an external force and bent as a whole, the secondary battery 7407 provided inside is also bent. FIG. 17C shows the bent state of the secondary battery 7407 at that time. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is fixed in a bent state. The secondary battery 7407 has a lead electrode electrically connected to a current collector. For example, the current collector is a copper foil, and a part of the current collector is alloyed with gallium to improve adhesion with the active material layer in contact with the current collector, so that the secondary battery 7407 has a high reliability when bent.
[0510] FIG. 17D shows an example of a bangle-type display device. The portable display device 7100 includes a housing 7101, a display unit 7102, an operation button 7103, and a secondary battery 7104. FIG. 17E shows a bent state of the secondary battery 7104. When the secondary battery 7104 is worn on a user's arm in a bent state, the housing is deformed, and the curvature of the secondary battery 7104 changes in part or in whole. Note that the degree of bending at any point of the curve expressed by the value of the radius of the corresponding circle is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. Specifically, the housing or the main surface of the secondary battery 7104 changes in part or in whole when the radius of curvature is in the range of 40 mm to 150 mm. High reliability can be maintained if the radius of curvature of the main surface of the secondary battery 7104 is in the range of 40 mm to 150 mm. By using the secondary battery of one embodiment of the present invention as the secondary battery 7104, a lightweight portable display device with a long life can be provided.
[0511] 17F shows an example of a wristwatch-type portable information terminal. A portable information terminal 7200 includes a housing 7201, a display portion 7202, a band 7203, a buckle 7204, operation buttons 7205, an input / output terminal 7206, and the like.
[0512] The portable information terminal 7200 can execute various applications such as mobile telephone, e-mail, document browsing and creation, music playback, Internet communication, and computer games.
[0513] The display surface of the display portion 7202 is curved, and display can be performed along the curved display surface. The display portion 7202 is also provided with a touch sensor, and can be operated by touching the screen with a finger, a stylus, or the like. For example, an application can be started by touching an icon 7207 displayed on the display portion 7202.
[0514] The operation button 7205 can have various functions, such as time setting, power on / off operation, wireless communication on / off operation, silent mode activation / cancellation, power saving mode activation / cancellation, etc. For example, the function of the operation button 7205 can be freely set by an operating system built into the mobile information terminal 7200.
[0515] The mobile information terminal 7200 can also perform short-distance wireless communication according to a communication standard. For example, the mobile information terminal 7200 can communicate with a wireless headset to enable hands-free calling.
[0516] The portable information terminal 7200 also includes an input / output terminal 7206, and can directly exchange data with another information terminal via a connector. Charging can also be performed via the input / output terminal 7206. Note that charging may be performed by wireless power supply without using the input / output terminal 7206.
[0517] A display portion 7202 of a portable information terminal 7200 includes the secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a portable information terminal that is lightweight and has a long life can be provided. For example, the secondary battery 7104 shown in FIG. 17E can be incorporated in a curved state inside a housing 7201 or in a bendable state inside a band 7203.
[0518] The portable information terminal 7200 preferably has a sensor. For example, it is preferable that a fingerprint sensor, a pulse sensor, a human body sensor such as a body temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, or the like is mounted as the sensor.
[0519] 17G illustrates an example of an armband-type display device. The display device 7300 includes a display portion 7304 and a secondary battery of one embodiment of the present invention. The display device 7300 can also include a touch sensor in the display portion 7304 and can function as a portable information terminal.
[0520] The display surface of the display portion 7304 is curved, and display can be performed along the curved display surface. In addition, the display device 7300 can change the display state by short-range wireless communication according to a communication standard.
[0521] The display device 7300 also includes an input / output terminal, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the input / output terminal. Note that charging may be performed by wireless power supply without using the input / output terminal.
[0522] By using the secondary battery of one embodiment of the present invention as a secondary battery included in the display device 7300, a lightweight display device with a long lifetime can be provided.
[0523] In addition, an example in which the secondary battery having good initial characteristics described in the above embodiment is mounted on an electronic device will be described with reference to FIGS.
[0524] By using the secondary battery of one embodiment of the present invention as a secondary battery in daily electronic devices, products that are lightweight and have a long life can be provided. For example, daily electronic devices include electric toothbrushes, electric shavers, and electric beauty devices. For the secondary battery of these products, a stick-shaped secondary battery that is small, lightweight, and has a large discharge capacity is desired in consideration of ease of holding by users.
[0525] FIG. 17(H) is a perspective view of a device also called a tobacco-receiving smoking device (electronic cigarette). In FIG. 17(H), the electronic cigarette 7500 is composed of an atomizer 7501 including a heating element, a secondary battery 7504 that supplies power to the atomizer, and a cartridge 7502 including a liquid supply bottle, a sensor, and the like. To enhance safety, a protection circuit that prevents overcharging and / or overdischarging of the secondary battery 7504 may be electrically connected to the secondary battery 7504. The secondary battery 7504 shown in FIG. 17(H) has an external terminal so that it can be connected to a charging device. Since the secondary battery 7504 is the tip part when held, it is desirable that the total length is short and the weight is light. Since the secondary battery of one embodiment of the present invention has a high discharge capacity and good cycle characteristics, a small and lightweight electronic cigarette 7500 that can be used for a long period of time can be provided.
[0526] Fig. 18(A) shows an example of a wearable device. The wearable device uses a secondary battery as a power source. In addition, when a user uses the device in daily life or outdoors, in order to improve splash-proof performance, water resistance, or dust resistance, there is a demand for a wearable device that can be charged wirelessly as well as by wire with an exposed connector.
[0527] For example, the secondary battery according to one embodiment of the present invention can be mounted on a glasses-type device 4000 as shown in FIG. 18A. The glasses-type device 4000 includes a frame 4000a and a display unit 4000b. By mounting a secondary battery on temples of the curved frame 4000a, the glasses-type device 4000 can be lightweight, well-balanced in weight, and has a long continuous use time. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a smaller housing can be realized.
[0528] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the headset type device 4001. The headset type device 4001 has at least a microphone unit 4001a, a flexible pipe 4001b, and an earphone unit 4001c. The secondary battery can be provided in the flexible pipe 4001b and / or the earphone unit 4001c. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a miniaturized housing can be realized.
[0529] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4002 that can be directly attached to the body. A secondary battery 4002b can be provided in a thin housing 4002a of the device 4002. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.
[0530] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4003 that can be attached to clothing. A secondary battery 4003b can be provided in a thin housing 4003a of the device 4003. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.
[0531] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the belt type device 4006. The belt type device 4006 has a belt portion 4006a and a wireless power receiving portion 4006b, and a secondary battery can be mounted inside the belt portion 4006a. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with miniaturization of the housing can be realized.
[0532] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the wristwatch device 4005. The wristwatch device 4005 has a display portion 4005a and a belt portion 4005b, and the secondary battery can be provided on the display portion 4005a or the belt portion 4005b. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.
[0533] The display unit 4005a can display not only the time, but also various other information such as incoming e-mails and phone calls.
[0534] In addition, since the wristwatch type device 4005 is a wearable device that is directly wrapped around the arm, it may be equipped with sensors that measure the user's pulse, blood pressure, etc. Data on the user's amount of exercise and health can be accumulated to manage the user's health.
[0535] FIG. 18B shows a perspective view of the wristwatch type device 4005 removed from the wrist.
[0536] 18C shows a side view of the display portion 4005. FIG. 18C shows a state in which a secondary battery 913 is built in the display portion 4005. The secondary battery 913 is the secondary battery described in Embodiment 4. The secondary battery 913 is provided at a position overlapping with the display portion 4005a, and is small and lightweight.
[0537] 18(D) shows an example of a wireless earphone. Here, the wireless earphone is illustrated having a pair of main bodies 4100a and 4100b, but this does not necessarily have to be a pair.
[0538] The main bodies 4100a and 4100b each have a driver unit 4101, an antenna 4102, and a secondary battery 4103. They may also have a display unit 4104. They also preferably have a substrate on which a circuit such as a wireless IC is mounted, a charging terminal, and the like. They may also have a microphone.
[0539] The case 4110 has a secondary battery 4111. It is preferable that the case 4110 also has a board on which circuits such as a wireless IC and a charge control IC are mounted, and a charging terminal. It may also have a display unit, buttons, and the like.
[0540] The main units 4100a and 4100b can wirelessly communicate with other electronic devices such as smartphones. This allows the main units 4100a and 4100b to play back audio data sent from other electronic devices. If the main units 4100a and 4100b have a microphone, the audio captured by the microphone can be sent to the other electronic device, and the audio data processed by the electronic device can be sent back to the main units 4100a and 4100b for playback. This allows the main units 4100a and 4100b to be used as a translator, for example.
[0541] In addition, the secondary battery 4103 in the main body 4100a can be charged from the secondary battery 4111 in the case 4110. The coin-type secondary battery, the cylindrical secondary battery, or the like in the previous embodiments can be used as the secondary battery 4111 and the secondary battery 4103. A secondary battery using the positive electrode active material particles 100 obtained in the first embodiment as a positive electrode has a high energy density, and by using the secondary battery 4103 and the secondary battery 4111, a configuration that can accommodate space saving associated with miniaturization of wireless earphones can be realized.
[0542] 19A shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 arranged on the top surface of a housing 6301, a plurality of cameras 6303 arranged on the side surface, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, and the like. Although not shown, the cleaning robot 6300 is provided with tires, a suction port, and the like. The cleaning robot 6300 can move by itself, detect dust 6310, and suck up the dust from a suction port arranged on the bottom surface.
[0543] For example, the cleaning robot 6300 can analyze an image captured by the camera 6303 and determine the presence or absence of an obstacle such as a wall, furniture, or a step. When an object that may become entangled in the brush 6304, such as a wire, is detected by image analysis, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 includes a secondary battery 6306 according to one embodiment of the present invention and a semiconductor device or electronic component therein. By using the secondary battery 6306 according to one embodiment of the present invention in the cleaning robot 6300, the cleaning robot 6300 can be an electronic device with long operating time and high reliability.
[0544] Fig. 19(B) shows an example of a robot. The robot 6400 shown in Fig. 19(B) includes a secondary battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.
[0545] The microphone 6402 has a function of detecting the user's voice, environmental sounds, etc. The speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user using the microphone 6402 and the speaker 6404.
[0546] The display unit 6405 has a function of displaying various information. The robot 6400 can display information desired by the user on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may also be a removable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer are possible.
[0547] The upper camera 6403 and the lower camera 6406 have a function of capturing images of the surroundings of the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of an obstacle in the moving direction when the robot 6400 moves forward using the moving mechanism 6408. The robot 6400 can recognize the surrounding environment and move safely using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407.
[0548] The robot 6400 includes a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component inside the robot 6400. By using the secondary battery according to one embodiment of the present invention in the robot 6400, the robot 6400 can be a highly reliable electronic device with a long operating time.
[0549] Fig. 19C shows an example of an aircraft. An aircraft 6500 shown in Fig. 19C includes a propeller 6501, a camera 6502, a secondary battery 6503, and the like, and has a function of flying autonomously.
[0550] For example, image data captured by the camera 6502 is stored in the electronic component 6504. The electronic component 6504 can analyze the image data and detect the presence or absence of an obstacle when moving. The electronic component 6504 can estimate the remaining battery charge from a change in the power storage capacity of the secondary battery 6503. The flying object 6500 includes therein the secondary battery 6503 according to one embodiment of the present invention. By using the secondary battery according to one embodiment of the present invention in the flying object 6500, the flying object 6500 can be an electronic device with a long operating time and high reliability.
[0551] This embodiment mode can be implemented in appropriate combination with other embodiment modes.
[0552] (Embodiment 5) In this embodiment, an example is described in which a secondary battery including the positive electrode active material of one embodiment of the present invention is mounted on a vehicle.
[0553] By installing secondary batteries in vehicles, next-generation clean energy vehicles such as hybrid vehicles (HVs), electric vehicles (EVs), and plug-in hybrid vehicles (PHVs) can be realized.
[0554] FIG. 20 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. An automobile 8400 illustrated in FIG. 20A is an electric automobile using an electric motor as a power source for running. Alternatively, the automobile 8400 is a hybrid automobile that can use an electric motor and an engine as a power source for running. By using one embodiment of the present invention, a vehicle with a long cruising distance can be realized. In addition, the automobile 8400 has a secondary battery. For example, secondary battery modules can be arranged on the floor of the vehicle. The secondary battery can not only drive the electric motor 8406 but also supply power to light-emitting devices such as a headlight 8401 and a room light (not shown).
[0555] The secondary battery can also supply power to display devices such as a speedometer and a tachometer included in the automobile 8400. The secondary battery can also supply power to semiconductor devices such as a navigation system included in the automobile 8400.
[0556] The automobile 8500 shown in FIG. 20(B) can charge the secondary battery of the automobile 8500 by receiving power supply from an external charging facility by a plug-in method and / or a non-contact power supply method. FIG. 20(B) shows a state in which a secondary battery 8024 mounted on the automobile 8500 is being charged from a ground-mounted charging device 8021 via a cable 8022. When charging, the charging method and connector standards may be appropriately performed by a predetermined method such as CHAdeMO (registered trademark) or combo. The charging device 8021 may be a charging station installed in a commercial facility or a home power source. For example, the secondary battery 8024 mounted on the automobile 8500 can be charged by an external power supply using plug-in technology. Charging can be performed by converting AC power to DC power via a conversion device such as an ACDC converter.
[0557] Although not shown, a power receiving device may be mounted on a vehicle, and charging may be performed by supplying power contactlessly from a ground power transmitting device. In the case of this contactless power supply method, by incorporating a power transmitting device in the road and / or an exterior wall, charging may be performed not only while the vehicle is stopped but also while it is moving. This contactless power supply method may also be used to transmit and receive power between vehicles. Furthermore, a solar cell may be provided on the exterior of the vehicle, and a secondary battery may be charged while the vehicle is stopped and / or moving. For such contactless power supply, an electromagnetic induction method and / or a magnetic field resonance method may be used.
[0558] 20C is an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. A scooter 8600 shown in FIG. 20C includes a secondary battery 8602, a side mirror 8601, and a turn signal light 8603. The secondary battery 8602 can supply electricity to the turn signal light 8603.
[0559] 20(C) is capable of storing a secondary battery 8602 in the under-seat storage 8604. Even if the under-seat storage 8604 is small, the secondary battery 8602 can be stored in the under-seat storage 8604. The secondary battery 8602 is removable, and when charging, the secondary battery 8602 can be carried indoors, charged, and stored before riding.
[0560] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the discharge capacity of the secondary battery can be increased. Therefore, the secondary battery itself can be made small and lightweight. If the secondary battery itself can be made small and lightweight, it contributes to reducing the weight of the vehicle, and the cruising distance can be improved. In addition, the secondary battery mounted on the vehicle can be used as a power supply source other than the vehicle. In this case, for example, it is possible to avoid using a commercial power source during peak power demand. If it is possible to avoid using a commercial power source during peak power demand, it is possible to contribute to energy conservation and reduction of carbon dioxide emissions. In addition, if the cycle characteristics are good, the secondary battery can be used for a long period of time, and the amount of rare metals used, including cobalt, can be reduced.
[0561] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES
[0562] In this example, a positive electrode active material containing titanium as an additive element was prepared, and its charge / discharge characteristics were evaluated.
[0563] <Preparation of positive electrode active material> The preparation of the positive electrode active material in this example will be described with reference to the manufacturing method shown in Fig. 11 to Fig. 12(C). In order to study the optimal heating conditions after adding the additive element source (A3 source), multiple heating conditions were set in step S73 in Fig. 11.
[0564] <Sample Preparation> As LiCoO2 in step S14 in Fig. 11, a commercially available lithium cobalt oxide (CellSeed C-10N, manufactured by Nippon Chemical Industry Co., Ltd.) containing no additional elements was prepared. When the particle size distribution of CellSeed C-10N was measured using a laser diffraction particle size distribution analyzer SALD-2200, the median diameter (D50) was 12.5μm. Furthermore, the element concentrations of CellSeed C-10N obtained by GD-MS satisfied the material Sm-1 of the above embodiment, and the lithium cobalt oxide had low concentrations of elements other than cobalt, oxygen, and lithium.
[0565] Next...
Claims
1. heating the lithium cobalt oxide; mixing a first additive element source with the heated lithium cobalt oxide to form a first mixture; heating the first mixture to form a first composite oxide; mixing the first composite oxide with a second additive element source to form a second mixture; heating the second mixture to form a second composite oxide; mixing the second composite oxide with a third additive element source to form a third mixture; and heating the third mixture at 750° C. or more and 850° C. or less for 2 hours or more and 10 hours or less to form a third composite oxide, the first additive element source, the second additive element source, and the third additive element source each contain one or more elements selected from magnesium, titanium, nickel, aluminum, fluorine, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, tungsten, chromium, molybdenum, rhenium, tantalum, phosphorus, and boron.
2. heating the lithium cobalt oxide; mixing a first additive element source with the heated lithium cobalt oxide to form a first mixture; heating the first mixture to form a first composite oxide; mixing the first composite oxide with a second additive element source to form a second mixture; heating the second mixture to form a second composite oxide; mixing the second composite oxide with a third additive element source to form a third mixture; and heating the third mixture at 750° C. or more and 850° C. or less for 2 hours or more and 10 hours or less to form a third composite oxide, The first additive element source has one or two selected from magnesium and fluorine, The second additive element source comprises one or two selected from nickel and aluminum; The method for producing positive electrode active material particles, wherein the third additive element source contains titanium.
3. In claim 2, the third additive element source comprises a titanium compound; The method for producing positive electrode active material particles includes adding the titanium compound to the lithium cobalt oxide in an amount of 0.1 mol % or more and 1 mol % or less.
4. In claim 3, The titanium compound is lithium titanate (Li 2 TiO 3 ) a method for producing positive electrode active material particles.
Citation Information
Patent Citations
Positive electrode active material, method for manufacturing positive electrode active material, and secondary battery
JP2018206747A
Secondary battery and electronic apparatus
JP2022070247A